From embryo to sexual maturity: chronic BPA exposure under elevated contamination scenarios induces multi-organ toxicity in marine medaka (Oryzias melastigma) - Yangmei Li; Zhang Huan; Qin Lin; Junyi Liu; Wenyang Xiao; Ning Zhang; Zailiang Li; Yanping Zhang; Yusong Guo; Zhongduo Wang; Zhongdian Dong (Marine Pollution Bulletin, 2026)

Molecular fingerprinting of biodegradable poly(butylene adipate-co-terephthalate) leaching and toxic effects on coastal phytoplankton - Yanping Li; Yan Wang; Ke Pan; Wen-Xiong Wang; Neng Yan (Water Research, 2026)

Effects of mixed-culture fermentation on bioactive compounds, antioxidant capacity, and flavor metabolomics of red sour soup - Yuke Liu; Yanping Cui; Lan Cheng; Yingying Wang; Yan Ding; Shuhong Ye (International Journal of Food Microbiology, 2026)

Three birds with one stone: a disintegrable fertilizer with rapid fertilization, controlled-loss and detoxification - Xianghai Kong; Chen Sun; Ziyu You; Wanji Zhu; Xinxin Zhai; Yuhao Wang; Yan Wang; Weijian Zhang; Kaimin Zhu; Xiaoshuang Han; Pan Zhao; Yanping Zhu; et al. (Desalination, 2026)

Genome-resolved characterization of candidate thermotolerance traits and predicted protein conformational behavior in Calditerricola during hyperthermophilic composting of organic wastes - Xu Li; Zhengnan Zhu; Youzhao Wang; Yanping Zhang; Xiaoyan Dang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Feng Ma; Liying Hao; Tong Zhu (Bioresource Technology, 2026)

Pressure-mediated mechanosensitive Piezo2 channel is activated in neurogenic bladder and promote bladder fibrosis in children - Lei Lv; Yanping Zhang; Qi Li; Junkui Wang; Shuai Yang; Zhaokai Zhou; Shuai Li; Zhengguang Zhang; He Zhang; Xingchen Liu; Yibo Wen; Jian Guo Wen (Journal of Molecular Medicine, 2026)

Non-equilibrium phase change during CO2 depressurization: a comprehensive review of thermodynamics, experiments, modeling, and safety implications for high-pressure CO2 pipeline rupture - Qifan Wang; Gengyuan Tian; Le Ma; Yanping Huang (Annals of Nuclear Energy, 2026)

Soil quality evolution and constraints in newly reclaimed farmland from gully consolidation in Yuanmou dry-hot valley of Southwest China - Yangqing Luo; Yifan Dong; Yanping Liu; Yingze Wang; Xingwu Duan (Soil and Tillage Research, 2026)

Integrating genomic evolution and reported outbreak occurrence in foot-and-mouth disease in Asia: Cross-border lineage connectivity and exploratory prediction of reported outbreak occurrence - Xiaoyu Ge; Yize Li; Jiaxuan Li; Yanping Jiang; Wen Cui; Xiaona Wang; Lijie Tang (Preventive Veterinary Medicine, 2026)

Sample-level PRRSV RT-PCR prevalence in pigs in mainland China (2004–2025): A systematic review and meta-analysis - Mengke Si; Yiwei Wang; Xiang Li; Junxue Qiu; Xiaoyu Chong; Baolei Yang; Mingfeng Chu; Yuchen Liang; Wei Cheng; Jingyan Zhang; Xuelong Chen; Yanping Qi (Preventive Veterinary Medicine, 2026)

Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

A low-molecular-weight glucan from Lycium barbarum reprograms tumor-associated macrophages involving the Dectin-1/NOX2 axis to suppress hepatoma - Yanping Cai; Yunliang Chen; Chunjing Li; Hongxu Chen; Yi Ji; Shaojie Zhang; Ying Zhu; Shuiling Cao; Rui Xu; Xueqian Xie; Qi Yi; Qing Wang; et al. (Carbohydrate Polymers, 2026)

Abrupt versus progressive CO2 increases: Overestimation of stimulatory effects on iron-driven anaerobic methane oxidation activity in paddy soils - Wangting Yang; Jinghao Jin; Evgenios Agathokleous; Qinan Hu; Yuling Yang; Bingjie Ren; Yanping Wang; Yuhan Jin; Zhenghua Hu; Lidong Shen (Agriculture, Ecosystems & Environment, 2026)

The Scaling Law in remote sensing mapping for model performance forecasting and reference sample optimization - Yuanhong Liao; Yuqi Bai; Shuang Chen; Jie Wang; Yanping You; Zhou Chen; Haoru Wu; Huabing Huang; Wenrui Li; Mingrun Zang; Zimeng Wang; Xinan Zhang; et al. (Remote Sensing of Environment, 2026)

LORE-mediated engineering of enhanced bacterial resistance in Solanaceous crops - Meng Wang; Qing Shan; Xiaohui Yang; Yanping Tian; Bo Zhou; Dan Wen; Biao Gong (Journal of Plant Physiology, 2026)

Waste soy milk-derived biodegradable seed coating agent: Synthesis, growth-promotion and drought resistance - Dongqing Cai; Cun Jiang; Bingbing Fu; Shihu Shu; Dongfang Wang; Pan Zhao; Yanping Zhu (Journal of Environmental Chemical Engineering, 2026)

Fermentation with aspergillus costiformis enhances the anti-migratory activity of Aquilaria sinensis leaves with possible involvement of MAPK-related pathways - Lianqun Wu; Xizhi Zhu; Xinyue Wang; Yanping Wu; Qian Bu; Tonglin Dai; Xing Wen; Kai Zhong; Hongwei Guo; Hong Gao (Food Research International, 2026)

Effects of stir-fried Hemp (Cannabis sativa L.) seed polysaccharides on blood deficiency syndrome in rats based on metabolomics and gut microbiota. - Minghao Sun; Haipeng Tang; Chenxi Bai; Qian Wang; Meng Liu; Yanping Sun; Qiuhong Wang; Haixue Kuang (Food Research International, 2026)

Potential of biofortification with tissue-adhesive exopolysaccharide-producing Lactiplantibacillus plantarum to fine-tune microstructure, stabilize texture and color, and enrich flavor of radish Paocai during fermentation - Yuli Huang; Haimei Lai; Yali Wang; Jiaqi Liu; Mengting Liu; Yanping He; Lihong Ge; Nan Zhao (Food Bioscience, 2026)

Energy window-guided molecular adsorbent for highly selective cesium capture: Breaking the Rb+/Cs+ separation bottleneck - Yanping Wang; Dezhen Fang; Kexin Li; Xiushen Ye; Wenjie Han; Pengrui Zhang; Zhijian Wu; Guosheng Shi; Haining Liu (Chemical Engineering Journal, 2026)

All-weather anti-salt solar desalination using a sandwich evaporator with thermal storage and asymmetric wettability - Yimin Qu; Changliang Lu; Ziyue Zhang; Xi Wen; Xuanli Jing; Tiaohong Zhang; Ting Lv; Dajian Huang; Yanping Wang; Xiaohu Qiang (Chemical Engineering Journal, 2026)

Dual-responsive and CD44-targeted nanotherapy to remodel the fibrotic niche for reversing liver fibrosis - Jingwei Li; Jiahao Chen; Lingling Wang; Wei Zhao; Yan Xia; Jinhang Zhang; Jie Zhou; Haiying Song; Xinghe Ji; Zijing Zhang; Shuting Qiu; Xiandan Jing; et al. (Chemical Engineering Journal, 2026)

Unveiling microbial sulfate reduction in Acid Mine Drainage Treatment using a Chained Environmental-Microbial machine learning approach - Yanping Deng; Beiyi Xiong; Hao Chen; Yongyang Wang; Xin Liu; Chuling Guo; Zhi Dang (Chemical Engineering Journal, 2026)

Spatial heterogeneity of humic acids- and nitrate-driven anaerobic oxidation of methane mediated by ANME-2d in paddy soils - Yanan Bai; Lei Dai; Yanping Wang; Lidong Shen; Bo Shang; Yang Ji; Zhaozhong Feng (Applied Soil Ecology, 2026)

Preparation of the Fe3O4@UIO-66-NH2 for the Removal of Water Pollutants by One-step Method - Meizhi Zhang; Yi Ren; Yutong Wang; Cong Wang; Yanping Li (Water, Air, & Soil Pollution, 2026)

Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

Salinity reduces cadmium bioavailability and toxicity in the Oryzias melastigma: Evidence from fish exposure and cell-based ion-competition assays - Zhongdian Dong; Jinghua Wang; Haozhong Tian; Jiahao Gao; Yue Liu; Nengneng Ding; Yiqing Yuan; Guohua Zhu; Xiaomin Zhao; Zailiang Li; Ning Zhang; Yanping Zhang; et al. (Marine Pollution Bulletin, 2026)

γ-aminobutyric acid (GABA) treatment alleviates off-flavor in postharvest waxed citrus fruit by enhancing peel gas permeance - Zhiquan Wang; Junchao Wang; Lu Qin; Zhen Huang; Xinxin Xu; Zhifeng Zhu; Jingjie Tang; Xiaojie Cui; Rangwei Xu; Feng Zhu; Yanping Fu; Xiuxin Deng; et al. (Postharvest Biology and Technology, 2026)

Anthropogenic dominance of water storage variability in the Yellow River Basin: A machine learning synthesis of multi-source data (1981–2031) - Yanping Cao; Zunyi Xie; Dandan Liu; Chaolin Mu; Jielun Wang; Yihao Chang; Yingjun Pang (Journal of Hydrology, 2026)

Corrigendum to “Spatiotemporal prediction of PM2.5 concentration over the Beijing–Tianjin–Hebei region based on forecasting, interpolation, and correction of ERA5 precipitable water vapor” [J. Atmos. Sol. Terr. Phys. 285 (2026), Article 106859] - Xiangshun Meng; Yanping Liu; Yong Wang; Chunhong Liu; Wei Du; Yingliang Wang (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Controlling the properties of 3D-printed sodium caseinate emulsion gels by tuning starch-induced network architecture - Kangning Zhang; Fangyuan Tian; Xiaojing Li; Shengju Ge; Yanping Wang; Yang Qin; Man Li; Rongbo Fan; Qingjie Sun; Na Ji (Food Research International, 2026)

Integrated transcriptomics and lipidomics provide insights into the stage-specific antifungal mechanisms of eugenol against Fusarium graminearum - Xin Yang; Luzhou Cai; Yueling Luo; Lianqun Wu; Xinyue Wang; Yanping Wu; Kai Zhong; Hong Gao (Food Bioscience, 2026)

Cooling load forecasting for urban district cooling systems using a hybrid multi-scale deep learning approach - Chao Zeng; Yang Feng; Haixia Cao; Jing Wang; Yanping Yuan (Energy and Buildings, 2026)

High-fidelity phase-change transfer platform for laser-induced graphene toward multifunctional flexible electronics - Zhao Li; Yanping Song; Wenjie Shao; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Zhuang Miao; Shudong Zhang; Cui Liu; Min Xi; et al. (Chemical Engineering Journal, 2026)

Short-range and long-range charge transfer based narrowband deep blue organic fluorescence emitters with EQE > 20% and CIEy ≈ 0.04 - Wenyan Zhao; Zijian Chen; Jihua Tan; Zhenyue Duan; Danhong Zhou; Yanping Huo; Jiuyan Li; Ruifang Wang; Pengzhong Chen; Xiaojun Peng (Chemical Engineering Journal, 2026)

Room-temperature photoinduced synthesis of ultrabright silanized polymer dots for ultrasensitive miRNA-21 detection in lung cancer diagnosis - Peipei Hu; Yunpeng Xue; Jianlin Yu; Yang Wu; Haoxuan Xiong; Tingting Miao; Dan Wang; Qinghua He; Yanping Li; Zhenqiang Ning (Chemical Engineering Journal, 2026)

Valorizing jackfruit shell into a hydrothermal liquid seed-priming agent for salinity-stressed crops - Tao Zhang; Yanping Zhu; Yongle Yu; Keyi Zhang; Pan Zhao; Xiaomeng Han; Weigang Wang; Shihu Shu; Dandan Ke; Xiuping Zhan; Xiaoshuang Han; Jiping Shi; et al. (Bioresource Technology Reports, 2026)

Direct screening of multifunctional Bacillus amyloliquefaciens for fiber degradation, antifungal activity, and its role in promoting wheat straw decomposition and peanut seedling growth - Yifei Guan; Miao Zhang; Guofang Wu; Yaoke Duan; Xuan Luo; Emmanuel Afirifa Tenakwa; Naana Mintaah Akufo; Yanping Wang; Lei Wang; Zhongfang Tan (Systems Microbiology and Biomanufacturing, 2026)

In vivo spatiotemporal fate of nanoparticle-incorporated dissolving microneedles: nanoparticle size effects - Ting Zhou; Yanping Fu; Kaitlyn Wu; Ziyang Zheng; Xinyu Wen; Guanlin Wang; Siyuan Peng; Xin Pan; Chuanbin Wu; Zhengwei Huang; Guilan Quan (Drug Delivery and Translational Research, 2026)

Pomelo polysaccharides: A review of the extraction techniques, purification, structural characteristics, interactions, biological activities, applications and future prospects - Jingwei Wang; Ting Yang; Kaiyang Liu; Yuesong Xiao; Xiaoming Wang; Haixue Kuang; Yanping Sun (Trends in Food Science & Technology, 2026)

Cyromazine induces neurotoxicity associated with damage to dopamine, serotonin, glutamate, and GABA neuronal systems through reactive oxygen species (ROS) generation in Caenorhabditis elegans - Zibo Yin; Jusong Liu; Qianmei Pang; Yunfei Zhang; Lanying Wang; Yanping Luo (Pesticide Biochemistry and Physiology, 2026)

Parallel path maneuvering control of cyber–physical autonomous surface vehicles based on model-agnostic meta-learning predictor - Yanping Xu; Nan Gu; Fengbei Xia; Anqing Wang; Zhouhua Peng (Ocean Engineering, 2026)

Electric field-assisted simultaneous microextraction of ultrashort- to long-chain perfluorocarboxylic acids prior to HPLC-MS/MS quantification - Fenghong Wei; Pei Wang; Junjun Hu; Yanping Zheng; Xiaojia Huang (Journal of Hazardous Materials, 2026)

Molecular dynamics evidence for bidirectional feedback between PFAS and humic acid during composting: Interaction mechanisms, conformational reorganization, and diffusion regulation - Shujie Hou; Chaoyue Zhao; Xu Li; Yanping Zhang; Bingzhen Li; Ziwei Dai; Qiyu Gong; Xinchang Zhou; Xiaolong Gao; Feng Ma; Yaonan Zhu; Fuxin Yang; et al. (Journal of Hazardous Materials, 2026)

Early thermal pulses drive interfacial pre-aging and plastisphere pre-shaping: An overlooked pre-conditioning pathway in PLA microplastic aging during composting - Yanping Zhang; Youzhao Wang; Chaoyue Zhao; Fuxin Yang; Xu Li; Shujie Hou; Bingzhen Li; Zhengnan Zhu; Ziwei Dai; Ziqian Wang; Xinchang Zhou; Qiyu Gong; et al. (Journal of Hazardous Materials, 2026)

Enhancement of microbial protein production via hydrogen oxidizing bacteria in microbial electrolytic protein-production cell system - Rui Dong; Hangyu Sun; Yilin Jiang; Haotian Liu; Yue Wang; Xingjia Fu; Yanping Liu; Ziyi Yang (Journal of Environmental Chemical Engineering, 2026)

Aliovalent Mg2+ doping in CdIn2S4 activates sulfur vacancies and promotes p-p orbital hybridization to enhance photocatalytic CO2 reduction - Yi Liu; Raotong Wen; Zuofang Yao; Bing Leng; Zebin Yu; Hongxiang Zhu; Yikai Wang; Xinqiu Tan; Yanping Hou; Shuangfei Wang (Journal of Environmental Chemical Engineering, 2026)

Spatiotemporal prediction of PM2.5 concentration over the Beijing–Tianjin–Hebei region based on forecasting, interpolation, and correction of ERA5 precipitable water vapor - Xiangshun Meng; Yanping Liu; Yong Wang; Chunhong Liu; Wei Du; Yingliang Wang (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Synergistic effects of ultrasound-assisted freezing and NADES on the cryostability of surimi gel: Perspective of quality and molecular structure - Yue Chen; Xindi Zeng; Yanping Wang; Xinyan Li; Xin Du; Xiufang Xia (Food Chemistry, 2026)

Molecular Analysis of a New Alphapartitivirus from Rhizoctonia solani AG-4 HG III Isolate Rs292 - Yangyang Li; Yanping He; Hongyang Chu; Wenli Li; Hongyu Wang; Yi Chen; Churong Wu; Yanqiong Li (Current Microbiology, 2026)

Correction: IGF1 is Reduced in Pregnancies with Preeclampsia and its Influence on Biological Behavior of Trophoblast Cells - Yanping Qin; Shengping Meng; Chunyan Lyu; Sumei Wang (Biochemical Genetics, 2026)

Integrated Application of Iso-Seq and RNA-Seq Analyses to Uncover Genes Involved in Ovarian Development in Platypharodon extremus - Zhuoyu Yang; Yanping Zhang; Wei Ka; Wenjing He; Yujie Yang; Wenlong Jiao; Jianlin Wang (Fishes, 2026)
This study focused on Platypharodon extremus, a species endemic to the Qinghai–Tibet Plateau, and systematically analyzed its reproductive biology, sex steroid hormones, ovarian histology, and transcriptomic characteristics throughout its complete reproductive cycle (August 2020 to June 2021). The results demonstrated that the body length, height, body weight, and gonadal weight of female individuals continuously increased with age, while the Gonadosomatic index (GSI) was lowest during the breeding season (June–August) and gradually rose during the non-breeding period. Serum estradiol (E2) and progesterone (P4) exhibited rhythmic fluctuations corresponding to ovarian development: E2 rose from 25.77 ng/L in stage-I to 146.00 ng/L in stage-V, then declined post-ovulation; P4 increased from 59.88 pmol/L in stage-I to 239.03 pmol/L in stage-V, showing a significant decrease after ovulation. Histological observations classified ovarian development into stages I–VI, clearly delineating the complete process from oogonium proliferation, cortical vesicle formation, yolk accumulation, maturation to postpartum regression. To explore molecular changes during the transition from vitellogenesis to oocyte maturation, we built a reference transcriptome with 30,060 non-redundant transcripts (average length = 1975 bp) using PacBio and Illumina data, and 91.87% of these transcripts received functional annotation hits against public databases. A comparative differential expression analysis was performed between ovarian stage III (active yolk accumulation) and stage V (oocyte fully matured). A total of 11,324 differentially expressed genes were identified (5249 upregulated and 6175 downregulated) between these two stages. GO enrichment analysis revealed predominant involvement in cellular processes, cellular components, and catalytic activities, while KEGG analysis demonstrated significant enrichment in metabolic pathways, PI3K-Akt, MAPK, and calcium signaling pathways. Quantitative PCR (qPCR) validation confirmed that candidate genes, including pik3a, calm, mapk1 map2k ddx49, and igf2 were significantly upregulated at stage V. These differentially expressed genes (DEGs) may represent potential molecular signatures linked to the transition from vitellogenesis to oocyte maturation. Our integrated transcriptomic and qPCR data identify potential gene candidates involved in ovarian maturation; however, these findings reveal correlation rather than direct regulatory causality. This study offers fundamental data and theoretical insights for understanding the reproductive regulatory mechanisms and aquaculture management of this endemic species.

Lipopolysaccharide promotes rheumatoid arthritis by enhancing Wnt7b mediated macrophage-FLS communication - Bing Wang; Yingqiu Song; Wenbo Xu; Jiaqing Chen; Yurong Huang; Xinyue Zhou; Yikang Cai; Aixin Xia; Yanping Li; Liwei Jiang; Faxue Liao; Jian Huang; et al. (Inflammation Research, 2026)

Phage therapy: A novel strategy to combat drug-resistant Salmonella Pullorum infection in chickens - Hongzhe Zhao; Shilong You; Jiahao Fu; Xiaoyu Xiong; Yingying Ma; Xiaona Wang; Rongyan Li; Fei Teng; Mingze Chen; Wei Wu; Guiwei Li; Yanping Jiang; et al. (Veterinary Microbiology, 2026)

RAD23A promotes multiple myeloma cell survival through DNA damage response, proteostasis and enhanced metabolic activity - Hongxiu Liu; Yihua Wang; Xunru Liu; Ni Yang; Senxin Wang; Jie Zhao; Yaqi Shi; Huichao Wang; Yanping Ma (Toxicology and Applied Pharmacology, 2026)

Ethylene responsive transcription factors alleviate browning in fresh in-hull walnut (Juglans regia. L) by modulating GABA metabolism under controlled atmosphere storage - Niu Ye; Guoli Dai; Shizhe Liu; Yongqi Zhang; Shan Liu; Sike Wang; Yuwei Wang; Yuanlin Gou; Ting Zhang; Yanping Ma; Qinggang Zhu; Huiling Ma (Postharvest Biology and Technology, 2026)

Multi-level predictive group maintenance optimization method for multi-component systems: Subsea Christmas tree as a case - Yanping Zhang; Baoping Cai; Chuntan Gao; Chenyushu Wang; Yiliu Liu (Ocean Engineering, 2026)

Urinary volatile organic compound metabolites and depressive symptoms among U.S. adults with cardiovascular-kidney-metabolic syndrome stages 0–3: NHANES-based associations and in silico multi-omics insights - Yulin Tian; Yiyun Wang; Hongsi Cui; Hongjie Wang; Yanping Yang; Yu Chang (NeuroToxicology, 2026)

Corrigendum to “Thermally driven polymer disentanglement: An overlooked Key pathway in PBAT-microplastic aging during composting” [J Hazard Mater 503 (2026) 141080] - Yanping Zhang; Xu Li; Youzhao Wang; Fuxin Yang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Yang Yun; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Molecular mechanism by which high temperature and RecBCD synergistically lower strand-separation barriers and promote destabilization of representative efflux-pump ARG fragments (macB/tetA) during hyperthermophilic composting - Xu Li; Youzhao Wang; Xiaoyan Dang; Yanping Zhang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Antagonistic modulation of myosin conformational dynamics by sanshool and smoke-derived aldehydes: A molecular basis for heterocyclic amine control in thermal processing - Hongyu Deng; Jie Jia; Lihui Feng; Siwei Xiong; Hemei Yuan; Zhiyuan Fang; Qiulan Li; Shengjie Duan; Hongkang Zhu; Ya Wang; Jun Sheng; Yanping Huang; et al. (Food Chemistry, 2026)

Nitrogen doping engineering of Ru nanoparticles/Mo2C MXene for efficient hydrogen production via NH3BH3 hydrolysis - Zhenluo Yuan; Fei Ya; Yang Shi; Shuyan Guan; Pingping Wang; Pei Liu; Shiqian Zhao; Qiuming Peng; Yanping Fan; Baozhong Liu (Chemical Engineering Journal, 2026)

Defensive remodeling of gut microbiota under microplastic stress and its pathogenic mechanism - Penghua Jian; Feng Zhang; Zhihao Chen; Xuan Zhou; Yan Xiong; Qiang Hu; Yingyu Wang; Dan Li; Jiai Yan; Ju Yang; Hong Cao; Ping Wu; et al. (Chemico-Biological Interactions, 2026)

Uncovering time-lagged causal mechanisms in hyperthermophilic composting using Peter–Clark momentary conditional independence algorithm - Yanping Zhang; Youzhao Wang; Ling Zhou; Fuxin Yang; Xu Li; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Ziqian Wang; Xinchang Zhou; Qiyu Gong; et al. (Bioresource Technology, 2026)

Urban Cooling Island Dynamics During the Development of an Ecological Urban Agglomeration in China - Ziwu Pan; Zunyi Xie; Lifei Huang; Fen Qin; Minmin Yu; Shuyu Yang; Zihan Wang; Jinyuan Han; Zenyan Wang; Yanping Cao; Zhihua Shi; Cangyu Li (Chinese Geographical Science, 2026)

The PorV protein as a cross-protective antigen against Riemerella anatipestifer infection - Sen Li; Yanhua Wang; Xiong Liu; Keke Ren; Yanping Deng; Yuncai Xiao; Sishun Hu; Zili Li; Hongbo Zhou; Zhengfei Liu; Zutao Zhou (Veterinary Microbiology, 2026)

A multi-scale assessment of the water–energy–pollution nexus in Sri Lanka’s industrial parks - Yanping Wang; Jingru Liu; Chinthaka Kularathne; Xiuzhi Hua; Shashini Yapa (Resources, Conservation and Recycling, 2026)

Integrative histological and multi-omics analyses reveal hormone-driven cell regeneration mechanisms during postharvest wound healing in melon - Congcong Wang; Yanping Hu; Baibi Zhu; Jihao Chen; Feng Wang; Shiqi Lu; Min Wang (Postharvest Biology and Technology, 2026)

Distribution and potential provenance of metal nanoparticles in sediment core from Daya Bay, northeastern South China Sea - Yumei Song; Dingcheng Wang; Qiaoli Zhong; Shengda Wu; Yanping Zhao; Shuchai Gan; Yulei Xie; Puoengran Guo (Journal of Hazardous Materials, 2026)

Explainable daily warning of algal concentration exceedance from SHAP-guided temperature and light thresholds - Dawei Xu; Yanping Hu; Shouye Yang; Lu Wang; Long Wang (Journal of Environmental Chemical Engineering, 2026)

Characteristics of soil organic carbon and its stability under different vegetation types and restoration years in Hongze lake wetland, China - Yanan Bai; Haikun Wu; Huifeng Lu; Yuling Yang; Yanping Wang; Lei Dai; Yuchun Ma; Jinqi Wang; Yuzhi Song; Lidong Shen (Journal of Environmental Management, 2026)

Environmentally relevant phthalate esters mixture disrupts gut-brain axis homeostasis in Apis cerana with Glu/GABA-Gln-related neurochemical imbalance - Jian Liu; Siwei Wang; Yanping Liu; Xiaonan Wang (Journal of Environmental Sciences, 2026)

Heat transfer and dynamic behavior of wall-adhered carbon dioxide droplets: power-law correlation and the cryogenic ring effect - Qifan Wang; Minyun Liu; Yanping Huang; Shanfang Huang; Ruohan Zheng; Houjun Gong (Annals of Nuclear Energy, 2026)

IGF1 is Reduced in Pregnancies with Preeclampsia and its Influence on Biological Behavior of Trophoblast Cells - Yanping Qin; Shengping Meng; Chunyan Lyu; Sumei Wang (Biochemical Genetics, 2026)

Non-invasive Computational Techniques for Diagnosing Myocardial Ischemia: Challenges and Future of FFRCT/iFRCT - Bao Li; Jincheng Liu; Yang Yang; Hao Sun; Chi Zhu; Leo Hwa Liang; Zijie Wang; Luyao Fan; Suqin Huang; Xueke Li; Guangfei Li; Liyuan Zhang; et al. (Annals of Biomedical Engineering, 2026)

Narirutin Mitigates Dextran Sodium Sulfate-Induced Enteritis in Procambarus clarkii by Modulating Intestinal Microbiota - Jian Li; Yitian Chen; Yanping Cai; Huiling Zhang; Bin Qiu; Xingfei Huang; Yan Wen; Aimin Wang; Bin He; Yude Wang; Shaojun Liu (Fishes, 2026)
Enteritis is a disease that affects Procambarus clarkii, significantly impacting aquaculture due to its high incidence and mortality rates, resulting in economic losses. Currently, the molecular mechanisms behind enteritis in Procambarus clarkii are not well understood. In this study, we established a model of intestinal inflammation induced by dextran sodium sulfate (DSS). Subsequently, histopathological changes, transcriptome analysis, intestinal microbiota analysis and immunofluorescence analysis were conducted. Histopathology showed that after treatment in the DSS + Narirutin (NR) group, there was an improvement in intestinal inflammation, and the structure of the intestinal tissue was partially restored. The intestinal transcriptome analysis revealed that in the DSS + NR group, 234 genes were upregulated and 188 genes were downregulated after treatment. This indicates a significant change in gene expression. KEGG enrichment analysis revealed that the DEGs were significantly enriched in TGF-β signaling pathway and PI3K-Akt signaling pathway. The results from 16S rRNA sequencing showed that in the DSS + NR group, the relative abundance of Akkermansia muciniphila significantly increased. Immunofluorescence results showed that, compared to the control group, the expressions of Occludin, nuclear factor-kB-p65 (NfkB-p65), Zonula occludens-1 (ZO-1), and Claudin-1 decreased following DSS treatment. However, treatment with NR was able to inhibit these changes. This further validated that NR can alleviate enteritis in Procambarus clarkii.

Genetic Basis of α-1,3 Galactose Epitopes in Animal Reservoirs of Coronaviruses - Xinjia Mai; Chenxi Zhu; Yu He; Nian Wang; Yue Ma; Wen Zhang; Yanping Wang; Yunsen Li; Dapeng Zhou (Phenomics, 2026)

Water temperature affects pathogenicity of ranavirus to adult bullfrogs - Yanping Ma; Le Hao; Xi Liang; Gang Wang; Zhenxing Liu (Aquaculture, 2026)

Optimal management of co-location marine activities in three-dimensional space: A Stackelberg game-based framework - Shuo Wang; Jiaju Lin; Chao Liu; Yanping Li; Saiya Xu (Ocean & Coastal Management, 2026)

Adaptive VP1 sites 93 and 97 modulate antigenic evolution and receptor binding of Senecavirus A: Phylogenetic analysis and validation with recombinant viruses - Jing Yang; Zhiliang Zhang; Weijia Sha; Mingyue Peng; Yize Li; Xiaoyu Ge; Jiaxuan Li; Wen Cui; Yanping Jiang; Xiaona Wang; Lijie Tang (Veterinary Microbiology, 2026)

Overcoming gastrointestinal mucosal barriers: Mechanistic innovations and technical advances in mucosal targeting strategies for animal oral vaccines - Meijun Yu; Yue Li; Zhaojun Wang; Ping Han; Yanping Jiang; Wen Cui; Yijing Li; Lijie Tang; Shuo Jia; Hongzhe Zhao; Yingying Ma; Jiaxuan Li; et al. (Veterinary Microbiology, 2026)

Study on multiscale particle motion characteristics in hydraulic lifting pipe under pulsating flow conditions - Desheng Chen; Geng Li; Wenhao Sun; Yuanming Ding; Zhe Lin; Yanping Wang (Ocean Engineering, 2026)

Therapeutic potential of Lactobacillus kefiranofaciens ZW18 postbiotic in alleviating hepatocellular carcinoma - Hanxue Xu; Weitao Geng; Jiangye He; Longgang Jia; Gang Zhao; Yanping Wang (Food Research International, 2026)

Molecular dynamics simulation of polyamide based reverse osmosis for boron removal - Yawei Du; Mengru Cui; Jingxin Wei; Yanping Li; Yize Liu; Shizhao Wang; Zhiyong Ji (Desalination, 2026)

Zwitterionic nanoparticle-mediated interfacial hydration for robust, salt-rejecting, and anti-fouling solar steam generation - Jianbin Zhang; Yuhao Zhai; Zhichao Chen; Ting Lv; Dianming Li; Yanhua Liu; Yanping Wang; Wufang Yang; Baoli Ou; Libang Feng; Feng Zhou (Chemical Engineering Journal, 2026)

Dynamic Variations of Agricultural Drought and its Response to Meteorological Drought Based on a Three-Dimensional Spatiotemporal Clustering Perspective - Fei Wang; Hexin Lai; Ruyi Men; Zipeng Wang; Yanbin Li; Yunzhong Jiang; Kai Feng; Wenxian Guo; Qingqing Tian; Yanping Qu (Water Resources Management, 2026)

Novel Hybrid Peptide ML-2 with Antibacterial and Antibiofilm Activity Against Pseudomonas aeruginosa - Shenghua Wu; Yanping Shi; Yang He; Tao Zhang; Feilong Chen; Yingchun Zhang; Tao Wang (Current Microbiology, 2026)

Analysis of the blowdown of supercritical carbon dioxide from simple vessel - Fengyuan Tian; Minyun Liu; Yanping Huang; Ruohan Zheng; Yangle Wang; Houjun Gong; Yu Tang; Tianzeng Liu; Jinghan Hu; Haohan Yuan; Yuan Zhou (Annals of Nuclear Energy, 2026)

Relative importance of traits, climate, and threats to extinction risk in salamanders - Jiang Wang; Chuanwu Chen; Yuyang Zhang; Yanping Wang (Conservation Biology, 2026)
Caudata (salamanders) is a highly threatened taxonomic group with over 60% of species estimated to be threatened. However, the species traits and extrinsic factors underlying their population decline and high extinction risk remain unclear. We conducted the first global comparative analysis to investigate which factors are associated with an increased risk of decline and extinction in salamanders. We addressed the following questions: Is extinction risk randomly distributed among salamander families, and if not, which families contain more threatened species than would be expected by chance; which species traits and extrinsic factors are important in determining the extinction risk in salamanders; and are the key factors for population decline consistent with those for extinction risk in salamanders? To determine which ecological characteristics and extrinsic factors best predict extinction risk and population decline in salamanders, we employed phylogenetic generalized least squares (PGLS) models and phylogenetic logistic regression (PGLM) models, respectively. Threatened salamanders were nonrandomly distributed across nine families, among which Cryptobranchidae and Hynobiidae contained significantly more threatened species than expected. Key predictors of salamander extinction risk were breeding strategy, geographic range size, minimum elevation, human threat index, and protected area coverage. Although geographic range size, climate change, and human threats were the most important predictors of salamander extinction risk and population decline, the effect of geographic range size was the opposite between the PGLS and PGLM models. Our results suggest that priority management should focus on extinction‐prone families, particularly Cryptobranchidae and Hynobiidae, and salamanders with small range sizes and sensitivity to human disturbance or climate instability.

Evolution of carbon sink patterns and spatial planning suitability in the Qingdao Coastal Zone based on the coupled InVEST–PLUS model - Chunxia Xu; Chunjuan Wang; Dahai Liu; Zhiwei Zhang; Yanping Li; Zheng Li (Frontiers in Marine Science, 2026)
To support the “dual-carbon” strategy and develop a carbon-sink-oriented coastal spatial planning framework, this study applies the coupled InVEST–PLUS model to Qingdao using 30 m resolution land-use data. Six spatial drivers (DEM, slope, GDP, population, road, and water proximity) are used to simulate land-use change and evaluate its impact on carbon storage. Model validation results indicate that the PLUS model shows good performance (Kappa ≈ 0.79, FoM = 0.168). The results indicate that (1) during 2010–2020, land-use patterns in the study area changed markedly, characterized by a decrease in farmland and an expansion of architecture area, while forest increased slightly and overall ecological land declined. (2) Total carbon storage dropped from 5.3174 × 10 7 t (2010) to 5.2749 × 10 7 t (2020), with a net loss of 4.25 × 10 5 t. Spatially, carbon storage showed a “clustered-high, contiguous-medium, radial-low” pattern. (3) DEM and water proximity primarily drove the expansion of farmland, forest, grassland, and waters, while population density and DEM dominated architecture growth; bare land expansion was mainly driven by population. Based on these findings, carbon storage transfer pathways are quantified, providing a scientific basis for low-carbon-oriented territorial spatial governance in coastal zones.

Overall quality maintenance and metabolite changes of fresh Cistanche deserticola Y.C.Ma stems treated by 1-methylcyclopropene during cold storage - Longxia Wen; Shuangxi Qian; Yanping Wang; Mingxing Xu; Yazhou Shao; Xu Zhang; Lijun Zhang; Yongchen Hua; Guolin Chai; Fangdi Hu (Postharvest Biology and Technology, 2026)

AutoML democratizes water quality forecasting: Lowering expertise barriers - Yangyang Chu; Yun Fang; Liangzhi Sun; Yang Zhang; Liujian Wang; XiaoMeng Han; Mou Lv; Haixing Liu; Kunlun Xin; Weigang Wang; Yanping Zhu; Shihu Shu (Journal of Water Process Engineering, 2026)

Estrus synchronization and follicular development patterns in jennies - Naerhulan Ayiken; Yeertai Tuohudashen; Younusi Huojiaabudula; Abudula Abudureyimu; Hongli Wang; Mingyang Geng; Guangdong Hu; Yanping Wang; Weibin Zeng (Journal of Equine Veterinary Science, 2026)

Component-specific microbial degradation and humification mechanisms of typical kitchen waste during winter hyperthermophilic composting in northeastern China - Youzhao Wang; Bingzhen Li; Jiacheng Li; Chaoyue Zhao; Xu Li; Yanping Zhang; Shujie Hou; Feng Ma; Ziwei Dai; Qiyu Gong; Xinchang Zhou; Fuxin Yang; et al. (Journal of Environmental Management, 2026)

Strain-specific impacts of Pichia kudriavzevii on metabolite profiles and microbial community dynamics in Chinese Baijiu fermentation: Integrated metabolomics and metagenomics analysis - Boqin Zhang; Mengbo Wang; Jia Zheng; Chenxi Yu; Chunhui Wei; Junyu Ren; Shouying Sun; Guoming Wang; Jinhua Wang; Yanping Lu; Liangcai Lin; Cuiying Zhang (International Journal of Food Microbiology, 2026)

Surface reflectance in homogeneous regions follows a Gamma distribution: principles, validation and applications - Yuanhong Liao; Yuqi Bai; Yanping You; Jie Wang; Shuang Chen; Ming Lin; Jin Chen; Jing M. Chen; Bing Xu; Peng Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Integrated morphological, transcriptomic, and metabolomic profiling reveals differential development mechanisms in two weeping forsythia genotypes during tissue culture - Yanxia He; Yanping Zheng; Jiaqi Geng; Yue Wang; Na Qi; Xu Lu; Xiaoxiao Wang; Yongjin Sun; Helong Wen; Xiaoya Liu; Xin Sun; Xianping Wang; et al. (Physiology and Molecular Biology of Plants, 2026)

Non-Invasive functional assessment of severity in cerebral arterial stenosis using cerebral flow fraction: A hemodynamic study - Hao Sun; Bao Li; Zijie Wang; Liyuan Zhang; Jun Zhao; Yanping Zhang; Guangfei Li; Jinli Ding; Yanjun Gong; Hwa Liang Leo; Youjun Liu (Medical & Biological Engineering & Computing, 2026)

Evidence for activity of iron-coupled anaerobic methane oxidation along lake sediment profiles - Yanping Wang; Bingjie Ren; Sile Wen; Yuhan Jin; Yanan Bai; Yuzhi Song; Lidong Shen (Journal of Soils and Sediments, 2026)

The dual role of humic acids in driving anaerobic oxidation of methane in paddy soils - Dehong Yang; Yanping Wang; Yuanhao Lan; Yanan Bai; Lidong Shen (Journal of Soils and Sediments, 2026)

Railway CORS GNSS PWV forecasting using normal time-frequency transform and deep learning with transfer learning strategy - Chen Chang; Yanping Liu; Yong Wang; Yunlong Zhang; Xiangshun Meng; Haozhe Chi; Chunrui He (Advances in Space Research, 2026)

The atmospheric residual error model of time-series InSAR based on ERA-5 PWV in Beijing, China - Haozhe Chi; Yong Wang; Yunlong Zhang; Chengwu Yang; Chen Chang; Fei Qiao; Xiangshun Meng; Chunhong Liu; Yanping Liu (Advances in Space Research, 2026)

Inhibition of potato common scab by Bacillus subtilis XT11 and its reshaping of the microbial community in potato geocaulosphere soil - Ning Liu; Minghao Lv; Yongdong Wang; Huimin Ma; Wei Fan; Junjie Ma; Jiguang Wang; Yanping Gao; Jinbiao Ma; Bo Zhou; Wenchong Shi; Zheng Gao (World Journal of Microbiology and Biotechnology, 2026)

Structural equation modeling revealed optimized ridge-furrow configuration integrated with straw-soil crust enhancing carbon sequestration and sainfoin yield in semiarid agroecosystems - Abdul Qadeer; Qi Wang; Rizwan Azim; Xiaole Zhao; Wen Ma; Ibrahim Awuku; Fujia Li; Qinglin Liu; Yanping Liu; Bing Liu; Xuchun Li; Muhammad Sanaullah; et al. (Computers and Electronics in Agriculture, 2026)

A three-dimensional layered model for sea area usage across dimensions of space, functional elements, and time - Saiya Xu; Yanping Li; Qi Yue; Dahai Liu; Heng Hu; Shuo Wang; Yuqing Chen; Yilin Liu (Ocean & Coastal Management, 2026)

Phloretin enhances the efficiency of sheep oocyte IVM and early embryonic development by bolstering antioxidant defenses, inhibiting apoptosis, and promoting development - Xu Li; Shuhong Tang; Yinwei Zheng; Ruiguo Zhao; Feifan Xu; Naerhulan Ayiken; Guangdong Hu; Yanping Wang; Weibin Zeng (Reproductive Biology, 2026)

Identification and validating native biocontrol bacteria Bacillus strain MZ3-12 against bacterial wilt - Xiao Zhou; Yue Qing; Yanping Wang; Haibin Deng; Jun Wang; Mi Kuang; Xuefeng Luo; Chenran Zhao; Zheng Sun; Ye Wang; Liang Yang; Wei Ding (Pesticide Biochemistry and Physiology, 2026)

Characteristics of sediment microbial community structure under different vegetation types with various restoration durations in Hongze Lake - Yuhan Jin; Wangting Yang; Yuling Yang; Yanping Wang; Huaiping Ling; Sile Wen; Bingjie Ren; Xiuling Zhang; Zhenfa Su; Jinghao Jin; Yuzhi Song; Lidong Shen (Journal of Environmental Management, 2026)

A comprehensive assessment of VOCs from multi-story swine farms: Sources, mitigation, and integrated risks - Dongxuan Han; Xue Li; Xiaojie Yan; Shuijiang Fu; Xin Li; Yanping Li; Bin Zhou; Kaiying Wang (Journal of Environmental Management, 2026)

Expansion of the rhizosphere soil and phyllosphere bacterial resistomes following repeated farmland application of high-temperature granulation-treated antibiotic fermentation residues - Ruiqi Wan; Tianyu Chen; Yanping Xun; Yazhuo Chen; Jitao Lv; Lingyi Meng; Kristian Koefoed Brandt; Yawei Wang (Journal of Environmental Sciences, 2026)

GhDREB1B-GhFAD3-2 module mediates drought tolerance by regulating linolenic acid biosynthesis in cotton - Yufei Liang; Luqi Wang; Yuxin Yang; Ronggui Yu; Yanping Shi; Liyong Hou; Xin Zhou; Yan Zhang; Guanghui Xiao (Science China Life Sciences, 2026)

Cytoskeletal control of development and environmental adaptation in plants - Yi Zhang; Jiejie Li; Yun Xiang; Pengwei Wang; Jie Le; Yanping Jing; Ting Wang; Xiangfeng Wang; Lei Zhu; Dong Qian; Guangda Wang; Peiwei Liu; et al. (Science China Life Sciences, 2026)

Immunoenhancing Effect of Lactobacillus Kefiranofaciens ZW18 Postbiotic On Cyclophosphamide-induced Immunosuppressed Mice - Hanxue Xu; Xinyuan Li; Weitao Geng; Longgang Jia; Yanping Wang; Jinju Wang (Probiotics and Antimicrobial Proteins, 2026)

Quasi-real-time retrieval of ERA5 precipitable water vapor over mainland China - Xiangshun Meng; Yong Wang; Yunlong Zhang; Wei Du; Yanping Liu; Xiao Liu (Advances in Space Research, 2026)

Genome characterization of a novel chrysovirus infecting Aspergillus Niger - Li Wang; Futao Huang; Jia Mi; Changfeng Long; Yelin Xu; Xiaolan Qi; Yanping Jiang; Tom Hsiang; Yinhui Jiang (Archives of Virology, 2026)

Bypassing Typhoons Cause Three-dimensional Dramatic Changes in Temperature and Ocean Heat Content of the Yellow Sea and Bohai Sea: A Case Study with Super Typhoon Maysak (2020) - Fangguo Zhai; Junyan Zhang; Yucheng Wang; Yujie Dong; Yanping Ma; Cong Liu; Zizhou Liu (Advances in Atmospheric Sciences, 2026)

Assessing Coastal Ecological Restoration Effectiveness in Qingdao Based on a Multi-Dimensional Entropy-Weighted TOPSIS Model - Chunxia Xu; Chunjuan Wang; Dahai Liu; Yanping Li; Chao Liu; Zheng Li (Journal of Marine Science and Engineering, 2026)
Coastal ecological restoration is a key approach to enhancing ecosystem resilience; however, the stage-wise evolution of restoration outcomes and the underlying driving mechanisms remain insufficiently quantified. Using Qingdao City as the study area, this research integrates remote sensing inversion, the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model, and time-series data from 2010 to 2020 to develop a comprehensive evaluation system for ecological restoration effectiveness, comprising 17 indicators across five dimensions: vegetation, biology, hydrology, economy, and climate. Based on this system, the entropy-weighted method is applied to conduct a dynamic assessment of restoration outcomes. The results indicate that (i) the composite evaluation score in the study area decreased from 0.36 in 2010 to 0.19 in 2015 and then increased to 0.74 in 2020, forming a “V-shaped” nonlinear trajectory with 2015 as a turning point, which is temporally consistent with a delayed response of ecological restoration outcomes following the implementation of major anthropogenic interventions. (ii) Dimension-specific analysis indicates that the decline in the composite score during 2010–2015 was mainly associated with the hydrological dimension, within which chemical oxygen demand (COD) and ammonia nitrogen emissions showed marked increases and were among the highest-weighted indicators. After 2015, following the intensive implementation of regional and system-oriented restoration projects such as the Blue Bay Initiative, pollutant emissions were observed to be effectively controlled, and Bare land area showed a continuous decline. These changes coincided with the rapid rebound of the composite score, within which Bare land area, as the highest-weighted indicator, played a prominent regulatory role. Marked differences were observed among dimensional responses: the biological and vegetation dimensions showed sustained improvement throughout the study period, whereas the hydrological dimension exhibited greater variability over time and stronger temporal alignment with policy-related phases. (iii) Robustness tests indicate that, after completely excluding climate-related variables, the composite score still increased from 0.36 and 0.24 to 0.77, with the “V-shaped” recovery pattern remaining unchanged. This result suggests that the observed improvement in restoration effectiveness in 2020 was more closely associated with systematic human interventions, rather than with short-term climatic fluctuations. This study provides a quantitative and transferable methodological framework for the dynamic evaluation and stage-oriented analysis of coastal ecological restoration effectiveness.

Sargassum-inspired multifunctional adsorbent by grafting cyanopyridine ionic liquid on down fiber: achieving integrated enhancement of adsorption selectivity and efficiency - Yanping Wang; Longfang Ren; Xinqing Han; Huaqing Liu; Bing Shi; Taotao Qiang (Water Research, 2026)

Thermally driven polymer disentanglement: An overlooked Key pathway in PBAT-microplastic aging during composting - Yanping Zhang; Xu Li; Youzhao Wang; Fuxin Yang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Yang Yun; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Hour-level humification of papermaking waste residue to produce honeycomb-like controlled-release fertilizer - Dongqing Cai; Shuang Wang; Linying Wang; Zerong Song; Yanping Zhu; Ziyu You; Jinjing Xu; Yan Wang; Wanji Zhu; Rongjun Zhang; Pan Zhao; Xiaofeng Lu; et al. (Journal of Cleaner Production, 2026)

Spatially stratified humification mechanisms in industrial-scale negative-pressure aerated thermophilic composting: Dominant pathways driven by temperature gradients and microbial succession - Shujie Hou; Youzhao Wang; Xu Li; Yanping Zhang; Xiaolong Gao; Jiedong Hao; Bingzhen Li; Ziwei Dai; Feng Ma; Fuxin Yang; Chaoyue Zhao; Tong Zhu (Journal of Environmental Chemical Engineering, 2026)

Preparation of sawdust-based degradable mulch film and nutrient slow-release performance evaluation - Xianghai Kong; Rongxi Hu; Zerong Song; Xinxin Zhai; Ziyu You; Yuhao Wang; Pan Zhao; Xiaofeng Lu; Rongjun Zhang; Yanping Zhu; Dongfang Wang; Dongqing Cai (Journal of Environmental Chemical Engineering, 2026)

Deciphering the spatiotemporal dynamics and source characteristics of nutrients under anthropogenic pressure in Taipu River, China - Tong Wang; Jiayi Kou; Fengjunxi Chen; Yalong Li; Yaojen Tu; Yanping Duan (Journal of Contaminant Hydrology, 2026)

An R2R3-MYB transcription factor TgMYB44 positively regulates petal senescence by enhancing ABA biosynthesis in tulip - Haipo Yang; Yikun Wu; Chengxiao Yuan; Hongqing Yin; Lin Xiang; Xuewei Wu; Honglin Deng; Bo Sun; Zhulong Chan; Yanping Wang (Plant Cell Reports, 2026)

Molecular Epidemiology, Mating Types, Clinical, and Physiological traits of Microsporum canis in Humans and Companion Animals (Cats and Dogs) in the Guiyang Region, Southwest China - Hao Hu; Bin Jiao; Yanni Deng; Wanglan Luo; Jing Zhou; Wei Lei; Zhengling Shang; Yinhui Jiang; Zhengrong Wang; Zhu Zeng; Yanping Jiang (Mycopathologia, 2026)

Comammox Nitrospira dominates autotrophic nitrification in paddy fields under long-term fertilization - Bingjie Ren; Yanping Wang; Yuchao Wang; Yuling Yang; Zhenfa Su; Haikun Wu; Wangting Yang; Yuhan Jin; Jinghao Jin; Shuai Liu; Lidong Shen; Xu Zhao (Agriculture, Ecosystems & Environment, 2026)

Analysis of atmospheric residual error and construction of correction model for GACOS-Corrected PS+DS time-series InSAR based on ERA5 PWV - Fei Qiao; Yong Wang; Yunlong Zhang; Chen Chang; Haozhe Chi; Chunhong Liu; Xiangshun Meng; Yanping Liu; Chengwu Yang (International Journal of Remote Sensing, 2026)

The Evolution and Development of Integrated Coastal Zone Management in China Since the 1950s - Yanping Li; Wenjing Zheng; Tuanxi Dong; Yingzi Yang; Shuo Wang; Yinuo Kang; Yilin Liu; Yuqing Chen; Dahai Liu (Coastal Management, 2026)

Transcriptome analysis of possible genetic-level defects in the use of large-sized Chinese mitten crab ( Eriocheir sinensis ) parents for breeding - Fujun Xuan; Jinghao Hu; Lei Gao; Ruifang Wang; Yanping Yang; Ying Pan; Jun Zhou; Rongchen Liu (Invertebrate Reproduction & Development, 2026)

Ethylene production from chlorinated organic hazardous wastes by thermal plasma pyrolysis - Yanping Yu; Hao Li; Wenlong Dong; Jiachen Zhu; Jiaqi Xu; Chen Wang; Baogen Su; Wenjun Zhang; Zhongbiao Wu; Qilong Ren; Qiwei Yang (Journal of Hazardous Materials, 2026)

Breaking the cycle of resistance: Hyperthermophilic composting establishes a multi-layered defense against ARG dissemination - Xu Li; Yanping Zhang; Chaoyue Zhao; Xiaoyan Dang; Bingzhen Li; Shujie Hou; Xiaolong Gao; Jiedong Hao; Zhenning Lyu; Youzhao Wang; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Sustainable upcycling of solid waste into heterogeneous peroxymonosulfate activators for degrading emerging organic contaminants in wastewater - Shuhua Wang; Yanping Zhong; Yiping Chen; Zhenguo Chen (Journal of Environmental Management, 2026)

CoOOH-based colorimetric aptasensor with dual cascade amplification for ultrasensitive monitoring of fleroxacin in honey - Yanping He; Peixuan Li; Xin Zhao; Dongmei Wang; Fuqiang Zhang (Food Control, 2026)

One-step microwave fabrication of waste potato-derived bifunctional film: sustainable mulch-fertilizer for plastic substitution - Dongqing Cai; Weijia Liu; Dongfang Wang; Shihu Shu; Pan Zhao; Tao Zhang; Yi Qiao; Xiaoshuang Han; Weijian Zhang; Kaimin Zhu; Rongjun Zhang; Yanping Zhu (Environmental Research, 2026)

Quantifying heavy metal(loid)s sources in subtropical soils and assessing key determinants of their bioavailability: insights from the Yangtze River Delta, China - Minqi Shi; Cheng Wang; Jianhua Wang; Cong Zhong; Yanping Zhao (Plant and Soil, 2026)

Unvegetated Tidal Flats: A Critical Yet Vulnerable Coastal Blue Carbon Sink - Yanping Wang; Changchun Li; Zhaoliang Peng; Jing Luo; Senlin Zhu; Yumeng Sun; Ruping Liu; Dongcheng Jiang; Xiangqian Zhou; Faming Wang (Global Change Biology, 2026)
Unvegetated tidal flats, despite accounting for approximately 24.9% of global blue carbon ecosystem area, remain underrepresented in blue carbon budgets. Here, we synthesize data from 184 sites across 23 countries to quantify their carbon stocks, carbon accumulation rate (CAR) and greenhouse gas (GHG, CO 2 and CH 4 ) emissions. Our results reveal that tidal flats sequester 8.6 (4.5–9.9) Tg C yr −1 and store 1.2 (0.7–2.0) Pg C in the top meter of sediments, increasing global blue carbon estimates by 6%–17%. However, they simultaneously emit 0.073 Tg CH 4 yr −1 (3.3 Tg CO 2 eq yr −1 ), 27.9% of the CH 4 emissions from salt marshes, offsetting 14.1% (1.8%–20.4%) of their carbon sequestration benefits. Mudflats exhibit the highest carbon stocks and CO 2 fluxes among different sediment types, primarily due to their abundant binding sites of fine‐grained particles and stronger microbial activities. Both CAR and CH 4 fluxes decline poleward, with tropical zone as hotspots. Our findings highlight the urgency of integrating tidal flats into climate mitigation strategies, particularly given their vulnerability to land‐use changes and sea‐level rise. Conservation efforts must balance carbon sequestration gains against CH 4 trade‐offs to optimize their climate regulation potential.

Rhizosphere drives microbial necromass carbon accumulation via enhanced carbon use efficiency: Evidence from a common garden experiment - Beibei Wang; Kun Yan; Chao Ji; Kun Li; Yanping Wang; Qitong Wang (Rhizosphere, 2025)

A new method of consistency evaluation of brain drugs: a case study of edaravone - Liqiang Gu; Yanping Hu; Yinfang Lai; Sheng Zhang; Haoran Wang; Xiaozhen Xu; Lingfang Chen; Yuhua Shi; Jiechao Chen; Xiaochun Sun; Yuan Zhang; Lingzhi Hu (Regulatory Toxicology and Pharmacology, 2025)

The discovery of marine natural product Streptochlorin and its inhibition of Banana fusarium wilt by targeting the GPI pathway - Xian Xiao; Renwei Xu; Wenjie Wu; Xiaojia Zhang; Yunfei Zhang; Lanying Wang; Yanping Luo (Pesticide Biochemistry and Physiology, 2025)

Dynamic response analysis of topside transportation using SPMT - Ming Qiu; Min Zeng; Mingzhi Li; Yibin Lv; Changwei wan; Zhengang Wang; Yanping He (Ocean Engineering, 2025)

A synergistic maintenance optimization method driven by integrated-resilience: Subsea Christmas tree as a case - Yanping Zhang; Baoping Cai; Chuntan Gao; Chenyushu Wang; Zhaoyi Pan; Zhen Qin (Ocean Engineering, 2025)

Stage-specific bacterial-fungal synergy in industrial-scale hyperthermophilic composting: Community assembly dynamics and modular networks drive humification - Chaoyue Zhao; Youzhao Wang; Feng Ma; Xu Li; Yanping Zhang; Shujie Hou; Bingzhen Li; Xiaodan Zhang; Fuxin Yang; Liying Hao; Tong Zhu (Journal of Environmental Management, 2025)

Stimulation of nitrate-driven AOM potential in paddy soils under elevated atmospheric CO2 concentration - Jinghao Jin; Yuling Yang; Bingjie Ren; Yanping Wang; Yuhan Jin; Wangting Yang; Qinan Hu; Lidong Shen; Zhenghua Hu (Journal of Environmental Management, 2025)

Research on hourly precipitation prediction along railways based on ERA5 reanalysis and post-processing correction - Xiangshun Meng; Yong Wang; Yunlong Zhang; Chengwu Yang; Chen Chang; Haozhe Chi; Yanping Liu (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Postbiotics alleviate cognitive impairment and neuroinflammation via gut-brain axis and TLR4/MyD88/NLRP3 pathway - Longgang Jia; Ling Xiao; Xiaoyan Song; Xiaoxiao Zhang; Xuemei Han; Wu Liang; Tianmin Fu; Yufeng Xie; Yanping Wang; Weitao Geng (Food Research International, 2025)

Revealing the polyphenol modulation mechanism for in vitro gastric digestion properties of myofibrillar proteins via noncovalent interaction - Yan Lu; Chaoqun Chen; Yu Chen; Shuaiqian Wang; Yanping Hu; Ping Liu; Hongbin Lin; Jie Tang; Jie Zhao (Food Chemistry, 2025)

Interfacially synergistic Photothermal enhancement for solar evaporation by palygorskite-carbon nanotube/chitosan aerogels - Yimin Qu; Changliang Lu; Gaofeng Zhang; Zhu Hu; Dajian Huang; Xiaohu Qiang; Yanping Wang (Desalination, 2025)

Fabrication of a nonwoven fabric-based multifunctional mulch film with Cr(VI) remediation capacity - Dongqing Cai; Jinjing Xu; Jiangshan Li; Xianghai Kong; Maowei Wu; Yan Wang; Wanji Zhu; Pan Zhao; Xiaofeng Lu; Xiaoli Tang; Yanping Zhu; Dongfang Wang (Chemical Engineering Journal, 2025)

Multifunctional groups improved photoluminescence efficiency of hot exciton materials for blue OLEDs with a maximum external quantum efficiency exceeding 12 % - Xiaofen Zhuang; Yuwei Xu; Ruicheng Wang; Tingting Cao; Jinxiang Li; Zhiju Chen; Yueling Ma; Dehua Hu; Yaocheng Jin; Wen-cheng Chen; Xianwei Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

Interpenetrating twin ZIF-8/carbon nanofiber aerogel independent electrochemical sensor for the detection of heavy metal ions in soil and crops - Jieqiong Wang; Boxin Yu; Fengshuo Wang; Zhe Wang; Ming Xu; Yanping Wu; Hongyuan Zhang (Chemical Engineering Journal, 2025)

Trophic status impacts the potential significance of anaerobic methane oxidation driven by multiple electron acceptors in Lake Taihu sediments - Wangting Yang; Qinan Hu; Hechen Huang; Jinghao Jin; Bingjie Ren; Sile Wen; Yuling Yang; Yefan He; Yanping Wang; Yanan Bai; Yuzhi Song; Lidong Shen (CATENA, 2025)

Selenium-Enriched Lactiplantibacillus plantarum ZZU 8–12 Regulates Intestinal Microbiota and Inhibits Acute Liver Injury - Yanping Wang; Hengyu Ma; Haolong Li; Yuhang Huang; Yupeng Tang; Xiaoxue Tang; Pintian Sun; Zhongfang Tan; Huili Pang; Fengyuan Yang (Probiotics and Antimicrobial Proteins, 2025)

Synthesis and antifungal activity of arecoline derivatives containing amino acid fragments - Xianwu Liu; Jianwen Zhang; Zefang Qin; Chengcheng Zhang; Huaxin Liu; Ting Zhou; Lanying Wang; Yanping Luo; Zhigang Zeng (Molecular Diversity, 2025)

Biochar-Amended Composting Transforms Chicken Manure Waste Into a Resource: Enhancing Extra-Rhizosphere Soil Fertility and Shaping Microbial Communities - Longjun Chen; Haiping Fan; Lulong Zhong; Yuncai Wang; Cheng Chen; Xin Chen; Yanping Chen; Jiaolin Zhang; Yu Lin (Journal of Soil Science and Plant Nutrition, 2025)
This study elucidates the synergistic regulatory mechanisms of biochar-amended chicken manure and mushroom residue compost (BCM) on soil microbial communities and nutrient cycling in the extra-rhizosphere, while evaluating its potential for sustainable agricultural waste recycling. Methods: We conducted a 50-day composting trial using five biochar application rates (0–7%). Assessed parameters included compost maturity (C/N ratio), nutrient content (NO 3 − -N, available phosphorus [AP], soil organic matter [SOM]), phosphatase and catalase activities, microbial community composition, and metabolic pathways. We performed Redundancy analysis (RDA) to correlate SOM/AP dynamics with microbial diversity and functional pathways. Results: At 5–7% biochar, compost maturity improved significantly, with C/N ratios of 15.6–18.2 and 2.2-4.0-fold increases in NO 3 − -N (1.41 mg/g), AP (50.09 mg/kg), and SOM (166.11 g/kg). Enzymatic activities (phosphatase: 9.81 mg/g·24 h; catalase: 83.08 µmol/g·24 h) correlated strongly with SOM/AP (R 2 = 0.71–0.82). Biochar enriched Proteobacteria (34.1%) and Actinobacteriota (15.2%), suppressed Halophiles ( Halomonas reduced by 52%), and enhanced carbon metabolism and oxidative phosphorylation pathways. RDA identified SOM/AP as a key driver of microbial diversity (R 2 = 0.91). The 5% biochar dose optimized nutrient retention (37–59% increases in AP, Available potassium [AK], NO 3 − -N) while maintaining microbial diversity, outperforming higher doses. Conclusions: This study demonstrates biochar’s dual role in reshaping extra-rhizosphere microbial ecology and nutrient dynamics, offering a precision agriculture strategy for sustainable waste recycling and circular economy practices. The 5% biochar dosage proved optimal, enhancing nutrient cycling and microbial activity while mitigating halophilic microbial suppression. Graphical Abstract

Genome-wide identification and expression pattern analysis of the dehydrin gene family in Eriobotrya japonica - Yanping Zhang; Xudong Zhu; Shuang Zhao; Mengqing Ge; Pengkai Wang; Tariq Pervaiz; Weizhong You (Horticulture, Environment, and Biotechnology, 2025)

Carbon dioxide bubble dynamics and wall heat transfer in flash chambers: Nucleation departure and cold bubble effects - Qifan Wang; Yansong Han; Ailing Fu; Shanfang Huang; Ruohan Zheng; Yanping Huang; Houjun Gong (Annals of Nuclear Energy, 2025)

Demand for small‐ and large‐ranged reptiles in worldwide wildlife trade - Songqi Zhang; Shai Meiri; Marcel Holyoak; Jiang Wang; Yanping Wang; Chuanwu Chen (Conservation Biology, 2025)
Wildlife trade poses a major threat to biodiversity, yet the drivers determining which species are traded are not fully understood. Through a comprehensive collection of official and online trade data, we applied a binomial test to identify families that contain an unexpectedly large or small number of traded species. We also analyzed which factors predispose reptile species to be traded and explored whether traded species were more likely to be threatened with extinction. Of the 10,919 reptile species in our dataset, 3889 species (35.6%) were traded. There was strong evidence for taxonomic biases in trade risk. In particular, all turtle and crocodilian families had higher trade risk than other reptiles. Species with large body sizes, habitat generalists, insular endemics, and those found in regions with high gross domestic product were traded in greater quantities and more frequently. Species with small and large ranges were more frequently involved in trade, suggesting a demand for rare and common species in wildlife trade. When connecting trade risk to extinction risk, data‐deficient and not‐evaluated species had fewer traded species and were less likely to be traded than threatened or nonthreatened ones. Nonetheless, these species warrant special conservation attention considering their rarity, limited range size, and insufficient legal protection. Given the increased attention given to wildlife trade, we suggest implementing stronger regulatory measures to monitor and control the trade of reptile species, particularly those belonging to families with a high risk of being traded. Efforts should also prioritize the protection of species exhibiting traits that make them highly susceptible to exploitation. Finally, promoting international collaboration for stricter enforcement of wildlife trade regulations and support of sustainable trade practices can help mitigate the negative impacts on biodiversity.

A potent and selective PROTAC degrader of CDK9 as effective inhibitor of HIV-1 RNA synthesis - Bo Yang; Ling Ma; Xiaotang Yang; Jiajia Wen; Weiyi Yin; Siqi Li; Yingjie Ji; Ying Wang; Shan Cen; Yanping Li (Molecular Diversity, 2025)

Polysaccharides from Actinidia Lindl.: Extraction, bioactivities, and emerging applications in food and pharmaceutical industries - Lihao Wang; Chenqing Dong; Qian Wang; Chi Teng; Wuyou Gao; Yujia He; Jun Liang; Yonggang Xia; Haixue Kuang; Yanping Sun (Trends in Food Science & Technology, 2025)

New interpretation of the Rb/Sr ratio of the Ili loess, northeastern Central Asia - Yanping Wang; Yougui Song; Yue Li; Hamid Gholami; Haoru Wei; Mengxiu Zeng; Xiuling Chen; Li Han (Quaternary Science Reviews, 2025)

P, N co-doped spherical graphitic carbon as metal-free peroxymonosulfate activator for diclofenac degradation: Non-radical pathway mechanism, performance and toxicity - Yanping Xiao; Jinping Mei; Haoqing Wang; Haobin Zhong; Qi Xu; Qiufang Yao; Hongxia Liu (Journal of Water Process Engineering, 2025)

Absorptive and transport roots of two tree species respond differently to soil salinity along soil depth - Yan Wang; Xiaohui Guo; Qiulin Bi; Wen Zhou; Hongxi Yao; Jiacun Gu; Yanping Wang (Flora, 2025)

Yeast-biomineralized MnOx modulates electron flux: Diverting carbon from methanogens to denitrifiers in carbon-limited wastewater - Yingying Liu; Xinshan Song; Xiaoxiao Hou; Yanping Xiao; Yuhui Wang; Xin Cao; Xiangzhou Meng (Environmental Research, 2025)

Nesting-inspired versatile bionic aerogel with special microstructure and photothermal conversion to strengthen durable uranium extraction from seawater - Yanping Wang; Longfang Ren; Xinqing Han; Sijie Yu; Taotao Qiang (Desalination, 2025)

Quaternized chitosan/Salvianolic acid B multifunctional hydrogel with ROS/glucose dual responsive properties for diabetic wound healing - Yanping Li; Xin Wang; Chenjiao Miao; Miao Song; Zheng Cao (Carbohydrate Polymers, 2025)

A multivariate framework for assessing propagation thresholds from meteorological to hydrological drought across indus river Basins-South Asia - Irfan Ullah; Xin-Min Zeng; Sidra Syed; Jiefeng Wu; Xiaoye Yang; Shadab Syed; Ning Wang; Yanping Li (Stochastic Environmental Research and Risk Assessment, 2025)

Suitable ridge width and straw length for alfalfa production under ridge-furrow rainwater harvesting compacted with chopped straw-soil crust in semiarid regions - Rizwan Azim; Qi Wang; Xuchun Li; Abdul Qadeer; Xiaole Zhao; Ibrahim Awuku; Wen Ma; Qinglin Liu; Yanping Liu; Bing Liu (Plant and Soil, 2025)

High-resolution profiling observation of carbon source dynamics in a mussel farm in the Changjiang River estuary during early autumn - Dawei Xu; Di Wu; Shouye Yang; Yanping Hu; Kui Wang (Journal of Oceanology and Limnology, 2025)

Assessing Spatiotemporal Characteristics, Health Impacts and Related Economic Losses of PM2.5, PM10 and O3 in Beijing-Tianjin-Hebei Region from 2015 to 2020 - Ran Gao; Qin Li; Yanping Zhang; Fei Che; Xiaorui Zhang; Yijie Wang; Yijun Zhang; Xite Zheng; Quanmei Li; Fengyi Huang; Chuning Luo; Wanqi Liu; et al. (Environment, Development and Sustainability, 2025)

The mechanisms of MTOCs maturation in human and mouse oocytes - Hao Gu; Ling Wu; Mingru Yin; Xingzhu Du; Jing Fu; Fangzhou Xu; Zhiqi Ye; Xuelin Zhang; Huixia Jing; Yuxi Luo; Wenzhi Li; Xiaoxi Sun; et al. (Science Bulletin, 2025)

Insights into stress response pathways and potential triterpene accumulation mechanisms induced by friction damage in kiwifruit - Fan Yang; Yuchun Wang; Fangzhi Wu; Sike Wang; Yuduan Ding; Yue Chen; Qinggang Zhu; Yanping Ma (Postharvest Biology and Technology, 2025)

Treating waste with waste: 1 h deep-drying of sewage sludge by secondary aluminum ash - Xianghai Kong; Zerong Song; Jie Wu; Ziyu You; Xiaofeng Lu; Bin Huang; Rongjun Zhang; Xiaoshuang Han; Xuemei Yu; Weijian Zhang; Yanping Zhu; Dongfang Wang; et al. (Journal of Cleaner Production, 2025)

Honeycomb-like slow-release fertilizer based on drinking water treatment sludge - Yanping Zhu; Shaofeng Dun; Yajuan Li; Tao Zhang; Xianghai Kong; Xiaomeng Han; Shihu Shu; Dongfang Wang; Weigang Wang; Cun Jiang; Kaili Li; Dongqing Cai (Journal of Environmental Chemical Engineering, 2025)

Bioaugmentation with Caldibacillus thermoamylovorans improved methane production of thermophilic anaerobic digestion via enhancing hydrolysis and acidification processes - Mengyao Xiao; Na Wang; Lin Xu; Dongqing Cai; Yanping Zhu; Jiping Shi; Siying Zhang; Li Liu (Journal of Environmental Chemical Engineering, 2025)

Efficient activating peracetic acid by copper-aluminum composites to degrade sulfathiazole: The critical role of Cu(III) species - Yuxiao Mu; Yanping Ding; Linli Tan; Qiulin Shi; Lei Chen; Jiaqi Ding; Jingwen Wang; Yong Liu; Pengchao Xie (Journal of Environmental Chemical Engineering, 2025)

Metabolic basis of resveratrol biosynthesis in P. megaterium PH3: Key roles of phenylpropanoid precursors and enzymatic feedback inhibition - Xiaohan Zhang; Dong Zhang; Junbo Liang; Liang Wang; Yanping Cui; Dingding Feng; Shuhong Ye (Food Chemistry, 2025)

The rhizosphere as a hotspot for nitrite- and nitrate-dependent anaerobic oxidation of methane in paddy fields - Yanping Wang; Yanan Bai; Lidong Shen; Bo Shang; Yang Ji; Xupeng Miao; Bingjie Ren; Yuling Yang; Wangting Yang; Zhaozhong Feng (Environmental Pollution, 2025)

Laser-engineered carbon hierarchies with multiscale attenuation mechanisms for ultrabroadband microwave absorption - Zhao Li; Nian Li; Yanping Song; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Shudong Zhang; Cui Liu; Min Xi; Congfa Song; et al. (Chemical Engineering Journal, 2025)

Synergistic bulk and back interface passivation enabled by in situ Ag-doping and Nb-engineering for efficient kesterite solar cells - Wenjie Zhu; Sisi Jia; Jingyi Meng; Chun Guo; Xinyu Zhang; Linxin Gao; Yixiang Xiao; Yanping Song; Jiayong Zhang; Huanhuan Sun; Jin Wang; Shihua Huang; et al. (Chemical Engineering Journal, 2025)

Unraveling the determinants of body size shifts in a rodent species in the Zhoushan Archipelago, China - Chengxiu Zhan; Yanping Wang (Oecologia, 2025)

Evolution and prediction of drought-flood abrupt alternation in mainland China using an improved index - Yiming Tong; Yu Chen; Yanping Qu; Virgílio A. Bento; Hongquan Song; Han Qiu; Wei Shui; Jingyu Zeng; Qianfeng Wang (Climate Dynamics, 2025)

Electron beam/persulfate-induced second-scale upcycling of wastewater polyvinyl alcohol with ultra-low chemical input - Tao Zhang; Yanping Zhu; Yongle Yu; Xiaoya Pan; Pan Zhao; Shihu Shu; Dongfang Wang; Jiping Shi; Li Liu; Weijian Zhang; Bin Huang; Xiaofeng Lu; et al. (Water Research, 2025)

Tobacco smoking exposure-mediated ELAVL1 regulates bladder cancer cell senescence via autophagy activation - Qiuyi Pu; Fang Gao; Yanping Xiao; Jiajin Wu; Chao Wang; Xiaoxiao Mo; Zhengdong Zhang; Rui Zheng; Dongmei Wu (Toxicology, 2025)

Synergistic bioaugmentation: Serratia sp. WKD and carboxymethyl cellulose-modified nano-zero-valent iron enhance malachite green decolorization by activated sludge - Linna Du; Xinjiao Dong; Huan Wu; Gang Li; Jiacheng Zhou; Yiqing Wu; Yanping Xiao; Jing Qin; Xiu Wang (Journal of Water Process Engineering, 2025)

Dual regulation of microbial denitrification and methane mitigation with manganese-humic chelates - Yingying Liu; Xinshan Song; Xiaoxiao Hou; Yanping Xiao; Yuhui Wang; Xin Cao (Journal of Environmental Management, 2025)

Comparative analysis of sheep, goat, and cow milk based on non-targeted metabolomics - Jiaxin Liu; Zhongshi Zhu; Yanping Huang; Jianping Qin; Li Wang; Mengyao Wei; Xiaorui Liu; Liang Xu; Hao Yuan; Xiaopeng An; Lei Zhang; Yuxuan Song (International Dairy Journal, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Hydroxyl-driven homogeneous and robust SAM anchoring on NiOx for high-performance inverted perovskite solar cells - Xiao Wu; Haoran Yang; Ziyao Yue; Yunfan Wang; Manting Liu; Jie Zeng; Leyu Bi; Qing-Dan Yang; Yanping Huo; Liming Ding; Alex K.-Y. Jen; Sai-Wing Tsang; et al. (Chemical Engineering Journal, 2025)

Stem nematode disease resistance-conferring gene identification in sweet potato using combined BSA-Seq and BSR-Seq analyses - Shouchen Qiao; Jingwei Chen; Yawei Li; Yannan Wang; Jukui Ma; Zhihe Kang; Qianqian Bian; Guozheng Cao; Guorui Zhao; Guohong Yang; Yanping Fan; Houjun Sun; et al. (Planta, 2025)

Enhanced therapeutic efficacy of Dioscorea cirrhosa Lour. n -butanol fractions in ulcerative colitis: a dual administration approach with comprehensive mucosal protection and anti-inflammatory effects - Mei Wang; XingJu Peng; CanJiao Yang; XinLong Yu; HaiChuan Tai; YanPing Li (Natural Product Research, 2025)

Mn-doped copper slag with oxygen vacancies boosts peroxymonosulfate activation for ofloxacin rapid removal - Linjin Li; Yaoze Wang; Guangfei Qu; Nanqi Ren; Yanping Liu; Jiao Wei; Dehui Kong; Changyi He; Minhua Cheng; Yingying Cai; Xiaofei Li; Rui Xu (Journal of Water Process Engineering, 2025)

Hydroxyl-tunable type I photosensitizer based on curcumin for photodynamic therapy against hypoxic tumor cells - Yanping Wang; Tong Mu; Xuewei Li; Xiuli Zheng; Jie Sha; Zhe Yu; Yuanyuan Qin; Haohui Ren; Ying Wang; Weimin Liu; Pengfei Wang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Variations in Central Asian dust activity and potential driving mechanisms over the past 80 kyr - Haoru Wei; Yougui Song; Yanping Wang; Mingyu Zhang; Hamid Gholami; Shugang Kang; Yue Li; Shukhrat Shukurov; Nosir Shukurov; Rustam Orozbaev (Gondwana Research, 2025)

Titanium dioxide nanoparticles disturb glucose homeostasis in association with impaired enteroendocrine cell differentiation - Kai Zou; Linna Du; Jing Qin; Jiacheng Zhou; Yanping Xiao; Xixi Song; Hongxia Liu; Xiu Wang (Food and Chemical Toxicology, 2025)

DNA damage repair (DDR) related prognostic risk model in multiple myeloma based on single-cell and bulk sequencing - Hongxiu Liu; Zhihua Li; Yihua Wang; Can Li; Kaiqing Yan; Yanping Ma (DNA Repair, 2025)

Cobalt doping modulation of Cs4MnBi2Cl12 double perovskite induces spin polarization for boosting photocatalytic reduction of CO2 - Yan Huang; Yujia Liu; Yi Liu; Xinqiu Tan; Yikai Wang; Qian Xiao; Xiaoyu Tong; Jinghui Pan; Zebin Yu; Zuofang Yao; Yanping Hou (Chemical Engineering Journal, 2025)

OCCMNet: Occlusion-Aware Class Characteristic Mining Network for multi-class artifacts detection in endoscopy - Chenchu Xu; Yu Chen; Jie Liu; Boyan Wang; Yanping Zhang; Jie Chen; Shu Zhao (Medical & Biological Engineering & Computing, 2025)

The impact of season, temperature, and direct normal irradiance on IVF pregnancy outcomes: a retrospective cohort study - Chao Wang; Jiehua Chen; Zhong Lin; Li Shi; Qiuyan Ruan; Jiamin Long; Yanping Lao; Xiangli Niu (International Journal of Biometeorology, 2025)
Objective . This study assessed associations between season, temperature, direct normal irradiance (DNI), and clinical pregnancy outcomes in first fresh in vitro fertilization (IVF) cycle. Methods . We conducted a retrospective cohort study (June 2021-October 2023) of 1179 patients undergoing fresh IVF cycles. Inclusion criteria required age ≤ 45 years, first-time fresh embryo transfer cycles (long/antagonist protocol), excluding preimplantation genetic testing, frozen cycles, or incomplete data. Temperature and DNI were recorded from gonadotropin (Gn) initiation to oocyte retrieval. Binary logistic regression assessed seasonal impacts on clinical pregnancy, while restricted cubic splines (RCS) independently modeled temperature/DNI effects. Results . Compared to winter, clinical pregnancy likelihood was 1.74-fold higher in spring (95% CI:1.11–2.71, P = 0.015) and 1.53-fold in summer (95% CI:1.02–2.30, P = 0.042). Stratified analysis revealed a 2.02-fold increased likelihood in summer cycles using the long protocol (95% CI:1.07–3.82, P = 0.031), whereas no seasonal variation was observed in antagonist protocol. RCS regression analysis indicated a nonlinear relationship between temperature and clinical pregnancy outcomes, which was confirmed in the long protocol group. No significant correlations were observed with DNI or in patients treated with the antagonist protocol. Conclusions . Season and ambient temperature significantly impact IVF clinical pregnancy, especially in the long protocol, with the highest increase in pregnancy rates observed in summer, as well as within the 26.13℃ to 29.68℃ temperature range. No significant effects were observed with DNI or the antagonist protocol. These findings suggest that summer treatment may optimize IVF outcomes, but future studies should prioritize multi-center prospective designs with continuous temperature monitoring to define precise optimal ranges.

The poleward expansion of the Hadley Cell has weakened the winter circulation in a midlatitude semi-enclosed shelf sea over the past six decades - Fangguo Zhai; Hao Li; Yanping Ma; Yucheng Wang; Yujie Dong; Zizhou Liu; Yanzhen Gu; Peiliang Li (Climate Dynamics, 2025)

Dynamics of wall bubbles in flash evaporation systems: Heterogeneous expansion and microlayer development - Qifan Wang; Junren Hou; Shanfang Huang; Fangbei Chen; Minyun Liu; Ruohan Zheng; Yanping Huang; Lie Quan; Houjun Gong; Yu Tang (Annals of Nuclear Energy, 2025)

Persistent Wnt signaling affects IVF embryo implantation and offspring metabolism - Yanping Jia; Yingdong Liu; Yanhe Li; Xiaohong Guan; Junting Xu; Zihui Yan; Kuisheng Liu; Yalin Zhang; Dandan Bai; Jiani Xiang; Yan Zhang; Shangyu Hou; et al. (Science Bulletin, 2025)

Dust supply to the West Philippine Sea since the Middle Pleistocene and distinct influences of the Westerlies after the Mid-Brunhes Event - Yun Cai; Dong Xu; Haifeng Wang; Yanping Chen; Haiyan Jin; Yibing Li; Weiwei Chen; Liang Yi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Hydrothermal reduction and phase transformation of Fe(III) minerals induced by rice straw to improve the heterogeneous Fenton degradation of metolachlor - Jingyi Liu; Yu Zhao; Liulong Cheng; Zhuoye Lu; Haojie Liang; Runliang Zhu; Yue Wang; Fangxin Deng; Zhuobiao Ni; Yaying Li; Guangwei Yu; Jing Zhang; et al. (Journal of Hazardous Materials, 2025)

Assessing the impact of climate variability on total factor productivity in African agriculture: Insights from non-parametric and parametric analyses - Boima M. Bernard; Yanping Song; Sumiati; Xin Wang (Journal of Cleaner Production, 2025)

Polyphenylene molecular engineering enables highly efficient multi-resonance thermally activated delayed fluorescence emitters with quenching resistance - Longjiang Xing; Xiaofeng Wang; Xiaolong Liu; Wen-Cheng Chen; Shihao Liu; Siwei Chen; Mengke Li; Ji-Hua Tan; Jia-Ming Jin; Ruicheng Wang; Shangru Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

Rewiring the methanol assimilation pathway in the methylotrophic yeast Pichia pastoris for high-level production of erythritol - Shuxian Wang; Jiayu Fang; Meiyu Wang; Sijie Yu; Yan Xia; Guoxia Liu; Yanping Zhang; Yin Li; Taicheng Zhu (Bioresource Technology, 2025)

Disentangling Direct and Indirect Effects of Temporal Isolation on the Multifaceted Diversity of Small Mammals on Land‐Bridge Islands - Chengxiu Zhan; Yunhao Xu; Huiwen Zhu; Yanping Wang (Journal of Biogeography, 2025)
Aim A major goal of island biogeography is to understand how island communities are assembled over time, and temporal isolation has been shown to affect species diversity. However, our knowledge of the indirect effect of temporal isolation on species diversity through other island characteristics is still limited, constraining our understanding of assembly processes on islands, particularly land‐bridge islands. The purpose here was to disentangle the direct and indirect effects of temporal isolation on three dimensions of diversity (taxonomic, phylogenetic and functional diversity) of small mammals on land‐bridge islands. Location Zhoushan Archipelago, China. Taxon Small mammals. Methods We performed small mammal censuses on 39 land‐bridge islands and a nearby mainland site. We first used univariate linear regressions to test the relationships between diversity indices of small mammals and island characteristics, and then built piecewise structural equation models (SEMs) to disentangle direct and indirect effects of temporal isolation on multifaceted diversity. Results In line with our expectation, temporal isolation directly affected taxonomic diversity and indirectly affected all three dimensions of diversity. The indirect effects of temporal isolation arose because young islands have larger island area and lower spatial isolation than old ones, and larger or remoter islands suffer stronger human activities, all of which affect species diversity. Importantly, the indirect effects of temporal isolation were strong for all three dimensions of diversity. Conclusion The diversity indices respond differently to island characteristics, with mechanisms that directly and/or indirectly relate to temporal isolation. Future studies on temporal isolation effects should attempt to quantify indirect effects rather than only direct effects. Furthermore, considering multifaceted diversity will contribute to identifying the underlying processes for community assembly and planning effective conservation strategies for species diversity.

Treatment of kiwifruit with Lactiplantibacillus pentosus CW5 cell-free supernatant maintains postharvest quality and alters the surface microbiome - Yuxuan Hao; Huili Pang; Haoxin Lv; Guofang Wu; Jianbo Zhang; Xuan Luo; Miao Zhang; Yaoke Duan; Yuting Hou; Yanping Wang; Lei Wang; Yimin Cai; et al. (Postharvest Biology and Technology, 2025)

Redox-active ligands for oxygen evolution reactions activity: Modulation of metal valence states in synthesis and accelerated reconstruction by rapid hydrolysis in alkaline electrolytes - Pengxin Sun; Jing Liu; Li Wang; Cheng Wu; Ronghua Jiang; Jun Huang; Yanping Hou; Mingjie Li; Boge Zhang; Zebin Yu (Journal of Environmental Chemical Engineering, 2025)

Effects of Fe3O4 on production of even-carbon volatile fatty acids by anaerobic fermentation of kitchen waste under ultrasonic-alkali pretreatment: Performance, metabolic functions, and metabolic pathways - Ziang Wang; Rufei Liu; Yue Cui; Zhihan Zhang; Huiyan Jing; Zhiling Chen; Shen Tian; Ziyi Yang; Yanping Liu (Journal of Environmental Chemical Engineering, 2025)

Research on PWV fusion based on ERA5 PWV and FY-4A PWV in Chinese mainland - Wei Du; Yong Wang; Xiao Liu; Jing Huang; Yanping Liu; Xiangshun Meng (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

A gut bacterial supplement for Asian honey bee (Apis cerana) enhances host tolerance to nitenpyram: Insight from microbiota–gut–brain axis - Chonghui Zhao; Yehua Peng; Muhammad Fahad Raza; Wenbo Wang; Yi Zhang; Yanping Chen; Richou Han; Jun Guo; Shaokang Huang; Wenfeng Li (Environmental Research, 2025)

Synergizing lattice matching and transient N–Li bonds to boost sulfur redox kinetics and regulate uniform lithium deposition in practical Li–S batteries - Yantao Wang; Huiqin Chen; Wenjuan Wu; Jinlong Li; Guangxin Zhang; Chunyan Wei; Shiyu Wang; Linlin Zhang; Yanping Zheng; Huanhuan Li (Chemical Engineering Journal, 2025)

Overcrowded steric engineering of through-space interactions for anti-quenching multi-resonance TADF materials - Ru-Jia Wang; Fan Zheng; Jie Hu; Yu-Lan Wu; Xiao-Long Liu; Jia-Xiong Chen; Longjiang Xing; Qiao-Er Wu; Yanping Huo; Wen-Cheng Chen (Chemical Engineering Journal, 2025)

Fabrication of biodegradable mulch film based on polylactic acid waste liquid - Dongfang Wang; Zerong Song; Xianghai Kong; Jie Wu; Jinjing Xu; Jinghong Ye; Yanping Zhu; Rongjun Zhang; Xiaoli Ma; Gang Li; Shifang Xu; Dongqing Cai (Chemical Engineering Journal, 2025)

Alkaline-thermal synergistic activation of persulfate for sawdust hour-level humification to prepare fulvic-like-acid fertilizer - Dongfang Wang; Xinyan Chen; Jing Zhang; Jia Xu; Xianghai Kong; Jinghong Ye; Rongjun Zhang; Huiqun Fan; Li Liu; Xiuping Zhan; Yan Qin; He Xu; et al. (Bioresource Technology, 2025)

Translocation coefficients of heavy metals in the soil-rice system and their environmental implication - Cheng Wang; Minqi Shi; Jianhua Wang; Cong Zhong; Yanping Zhao (Plant and Soil, 2025)

Topping-induced transcriptome changes reveal PaSPL-mediated regulation of plant architecture in Platanus acerifolia - Yanping Zhang; Yali Guan; Yongkang Lu; Lin Wang; Yuqing Chen; Manzhu Bao (Plant Molecular Biology, 2025)

Impact of conversion of coastal wetlands into paddy fields on the process of nitrite-dependent anaerobic methane oxidation - Qinan Hu; Weiqi Wang; Wangting Yang; Yuling Yang; Yanan Bai; Yefan He; Bingjie Ren; Yanping Wang; Jinghao Jin; Lidong Shen (Soil Ecology Letters, 2025)

Trait segregation and growth characteristics of the F2 generation hybrids between Crassostrea dianbaiensis and C. iredalei - Jiangwei Li; Ying Pan; Qinggan Xing; Jinhui Wu; Haitao Ma; Weitao Wan; Chao Yue; Zhongyu Wang; Jun Li; Ziniu Yu; Yanping Qin; Yuehuan Zhang (Aquaculture International, 2025)

Spatiotemporal Evolution and Multi-Driver Dynamics of Sea-Level Changes in the Yellow–Bohai Seas (1993–2023) - Lujie Xiong; Fengwei Wang; Yanping Jiao; Yunqi Zhou (Journal of Marine Science and Engineering, 2025)
This study analyzes sea-level changes in the Yellow and Bohai Seas from 1993 to 2023 based on satellite altimetry data. After reconstructing the gridded sea-level data using local mean decomposition (LMD), the annual mean sea level was estimated at 28.86 mm, with an average rise rate of 2.21 mm per year (mm/a). Temporal and spatial variations were examined through nonlinear least squares fitting to capture interannual variability and decadal amplitude distributions. Empirical orthogonal function (EOF) analysis identified the first three modes, explaining 90.40%, 2.78%, and 1.47% of the total variance, respectively, and their spatial patterns and temporal coefficients were derived. The first mode was strongly correlated with sea surface temperature (SST) and precipitation, showing distinct spatial structures. Temperature and salinity profiles revealed a decadal-scale trend of increasing temperature and decreasing salinity with depth. Seasonal variations of sea-level anomaly (SLA) were evident, with mean values and trends of −11.47 mm (2.19 mm/a) in spring, 57.12 mm (2.29 mm/a) in summer, 75.68 mm (2.24 mm/a) in autumn, and −13.90 mm (2.11 mm/a) in winter. Seasonal correlations among SLA, SST, salinity, and precipitation were assessed, highlighting interannual amplitude variations. This integrated analysis provides a comprehensive understanding of the dynamics and drivers of sea-level fluctuations, offering insights for future research.

Recognition and classification techniques of marine mammal calls based on LSTM and expanded causal convolution - Wanlu Cheng; Hao Chen; Jiaming Jiang; Shuang Li; Jingjing Wang; Yanping Zhou (Frontiers in Marine Science, 2025)
Marine mammal calls play a vital role in navigation, localization, and communication. Effectively classifying these calls is essential for ecological monitoring, species conservation, and military biomimetic applications. However, traditional machine learning methods struggle to capture complex acoustic patterns, while most existing deep learning approaches rely solely on frequency-domain features and require large datasets, which limits their performance on small-scale marine mammal datasets. To address these challenges, we propose a hybrid architecture combining a time-attention Long Short-Term Memory (LSTM) network and a multi-scale dilated causal convolutional network. The model comprises three modules: (1) a frequency-domain feature extraction module employing dilated causal convolutions at multiple scales to capture multi-resolution spectral information from Mel spectrograms; (2) a time-domain feature extraction module that inputs Mel-frequency cepstral coefficients (MFCCs) into an LSTM enhanced with a time-attention mechanism to highlight key temporal features; and (3) a classification module leveraging transfer learning, where a pre-trained neural network is fine-tuned on real marine mammal call data to improve performance. Extensive experiments were conducted on vocalizations from four marine mammal species. Our proposed method outperformed existing baseline models across four evaluation metrics: accuracy, precision, recall, and F1 score, with improvements of 3%, 7%, 2%, and 4%, respectively. The results confirm the effectiveness of combining frequency- and time-domain features along with attention mechanisms and transfer learning. This hybrid approach enhances the accuracy and robustness of marine mammal call classification, especially under limited data conditions.

Effects of trigonelline, diosgenin, and Cistanche deserticola polysaccharide on the culture of female germline stem cells in vitro - Xiaoli Yu; Yikai Qiu; Jinhua Li; Yanping Zhang; Qian Wang; Zehua Jin; Xinrui Liu; Xiuying Pei (Natural Product Research, 2025)

Global prevalence of Porcine Astrovirus: A systematic review and meta-analysis - Xiaoyu Ge; Yize Li; Feipeng Zhao; Xin’ao Ma; Jiaxuan Li; Yanping Jiang; Wen Cui; Xiaona Wang; Lijie Tang (Preventive Veterinary Medicine, 2025)

Unveiling insecticidal compounds from the invasive weed Tithonia diversifolia against Spodoptera litura and elucidating mechanisms via transcriptomic analysis - Zhandi Wang; Xiaocui Zhuang; Kaixiang Chao; Yanping Li; Lin Jia; Caiyun Zi; Yuanqing Zhou (Pesticide Biochemistry and Physiology, 2025)

2,4,6-trinitrotoluene induces neurotoxicity by affecting the G protein pathways in Caenorhabditis elegans - Ying Li; Yanping Zhou; Chunyan Wang; Yaguang Nie; Yongbing Zhu; Sanping Zhao; Lijun Wu; An Xu (NeuroToxicology, 2025)

Suppressing sediment nutrient release via electrokinetic drainage of porewater: apparent paradox and underlying mechanisms - Danyang Wang; Xianqiang Tang; Rui Li; Yanping Hu; Junjun Gu; Zhenhua Wang (Journal of Environmental Management, 2025)

Multi-objective decision-making considering future demands helps to delineate key areas for ecological restoration in Changsha-Zhuzhou-Xiangtan urban agglomeration, China - Tao Li; Sheng Li; Yanping Zhao; Hua Zheng; Kuan Wang; Mi Yi (Journal of Environmental Management, 2025)

Preparation of a polysulfone loose nanofiltration membrane with gradient structure via hybrid-induced phase separation for the efficient separation of dyes/salts - Yuanhui Tang; Huifang Yu; Yuwenyao Zhang; Juan Liu; Jihao Zhu; Yakai Lin; Hedi Chen; Yanping Hu; Jianqing Zhang; Song Hu; Hai Xie; Lixin Yu; et al. (Desalination, 2025)

Selective adsorption of Rb+ and Cs+ by a superparamagnetic Fe₃O₄@FeMn-MOF from brine - Yanping Wang; Qiongyuan Zhang; Dezhen Fang; Kexin Li; Zhongmei Song; Wenjie Han; Junwei Li; Xiushen Ye; Haining Liu; Huifang Zhang; Xi Zhang; Zhijian Wu (Desalination, 2025)

Influencing Factors on Oyster Recruitment and Performance Evaluation for Oyster Reef Restoration in Tianjin Coastal Zones - Yuxuan Zhao; Chen Yang; Bo Zhang; Yanping Li; Jianbo Tu; Fuxin Niu; Wenliang Kong; Zhiyun Wang; Xianhua Liu (Oceans, 2025)
Global oyster reefs have suffered severe degradation due to human activities, environmental pollution, and climate change. The construction of artificial reefs offers a promising strategy to enhance oyster recruitment and mitigate population decline. However, the factors influencing oyster recruitment in artificial frameworks remain largely unclear, and it is still challenging to evaluate the effectiveness of different restoration methods. In this study, a series of oyster reef restoration experiments were conducted in the Tianjin coastal zone to identify key factors affecting recruitment success. These factors included restoration methods (shell string, mesh bag, and mesh cage), seeding with juvenile oysters, oyster shell orientation, and cultch hanging height. Our results indicated that the mesh bag method achieved the highest oyster settlement density in the intertidal zone, while the shell string method supported the fastest growth rates of oysters in the subtidal zone. The lower hanging height of cultches in the artificial frames increased oyster settlement density; however, hanging the cultches too close to the sediment negatively impacted oyster growth rates. Additionally, seeding with juvenile oysters and orienting the rough side of the shell upward enhanced recruitment performance. Oyster settlement density was greater in the intertidal zone (Bagua Shoal) compared to the subtidal zone (Dashentang), while oysters in the subtidal zone exhibited faster growth rates. Using redundancy analysis, the influence of environmental factors on the oyster recruitment performance was assessed. Oyster growth in the subtidal zone was positively correlated with dissolved oxygen and pH, whereas oyster settlement density in the intertidal zone was positively associated with water temperature, chlorophyll a concentration, and salinity. Finally, we evaluated the effectiveness of different restoration methods by considering factors including reef construction costs, oyster settlement abundance, average daily shell growth rate, water purification potential, and reef subsidence. Our results demonstrated that the shell string method was the most effective in the Dashentang subtidal zone, while the mesh bag method with oyster seeding was optimal in the Bagua Shoal intertidal zone. Our findings can provide valuable insights and guidance for oyster reef restoration projects.

Offspring performance of backcrossing between hybrid line of Crassostrea dianbaiensis ♀ × Crassostrea iredalei ♂ and their parental species - Jiangwei Li; Yanping Qin; Qinggan Xing; Jinhui Wu; Haitao Ma; Weitao Wan; Chao Yue; Zhongyu Wang; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Aquaculture, 2025)

Postharvest fragrance dynamics of different scented cut lilies: Insights from HS–SPME–GC–MS and electronic nose - Yiwei Zhou; Yiwei Chen; Jinfeng Dong; Qin Wang; Fulong Yan; Jianjun Tan; Yechun Xu; Genfa Zhu; Yanping Fan; Yuanjun Ye (Postharvest Biology and Technology, 2025)

Mechanism and application of the Lagrangian flow network method to indicate practical material distribution patterns in the tide-dominated Bohai Sea with multi-frequency tides - Jinzhen Yu; Xueqing Zhang; Xiaoxuan Sheng; Fangjing Deng; Yanping Wang; Wensheng Jiang; Jihong Zhang (Ocean Modelling, 2025)

Tannin-modified down keratin fibers to construct an all-biomass-based adsorbent for efficient uranium extraction from seawater - Yanping Wang; Longfang Ren; Yadong Pu; Tian Wang; Bing Shi; Taotao Qiang (Journal of Environmental Chemical Engineering, 2025)

Proteomic insights from extracellular vesicles into the molecular mechanisms of health effects induced by Per- and polyfluoroalkyl substances - Yanping Li; Yadan Luo; Yang Liu; Na Li; Kai Huang; Lingxiangyu Li; Zhigang Li; Chao Han; Nali Zhu; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2025)

Study of the interaction between polysaccharides and liposomes based on low-field nuclear magnetic resonance - Tingting Zhang; Heng Yu; Chenping Li; Yanping Wang; Chenxi Zheng; Yingli Hu; Jianzhong Han; Jianhua Liu; Weilin Liu (Food Bioscience, 2025)

Interpretation of the Budyko framework for monthly evapotranspiration prediction of individual basins - Hao Sun; Xingwang Wang; Yanping Qu; Juan Lyu; Hehe Cai; Xuejun Zhang (Atmospheric Research, 2025)

Identification of candidate genes associated with resistance to aflatoxin production in peanut through genetic mapping and transcriptome analysis - Dongxin Huai; Li Huang; Xiaomeng Xue; Bolun Yu; Yingbin Ding; Gaorui Jin; Hao Liu; Manish K. Pandey; Hari Kishan Sudini; Huaiyong Luo; Xiaojing Zhou; Nian Liu; et al. (Theoretical and Applied Genetics, 2025)

Research on the fusion of PWV over the Beijing-Tianjin-Hebei region based on ERA5 PWV and FY-4A PWV - Wei Du; Yong Wang; Xiangshun Meng; Yanping Liu; Xiao Liu (Advances in Space Research, 2025)

Growth performance of two brackish oysters (Crassostrea iredalei and Crassostrea dianbaiensis) and their hybrids in subtropical sea area - Jiangwei Li; Ying Pan; Jinhui Wu; Haitao Ma; Weitao Wan; Chao Yue; Shengyong Li; Zhongyu Wang; Jun Li; Ziniu Yu; Yanping Qin; Yuehuan Zhang (Aquaculture, 2025)

Lycorine provides antiviral activities against mandarin fish ranavirus via suppressing apoptosis and activating type I interferon pathway - Mengyan Jia; Yanping Ma; Le Hao; Ziqian Tao; Jingya Wang; Sentai Liao; Hui Guo; Zhenxing Liu (Aquaculture, 2025)

Chinese chestnut did not induce negative plant soil feedback during centuries of growth - Xu Cheng; Zhichun Yan; Qian Li; Lucas Schmitz; Jundi Yan; Yueyang Ge; Yanping Lan; Yaceng Zhao; Yiyang Wang; Guangdong Li; Yang Liu; Martinus Schneijderberg; et al. (Science of The Total Environment, 2025)

Prenatal high-sucrose diet affects pulmonary artery contractile functions via MT receptors - Xueqin Feng; Hongwei Fu; Xiao Sun; Hua Shu; Yongning Zhu; Yanyan Bai; Qinggui Ren; Xinying Liu; Meng Liu; Fanyong Zhang; Yanping Wang (Reproductive Toxicology, 2025)

Self-healing physiological monitoring epidermal sensors of dual conductivity pathway with self-adaptive transformation - Liao Ziming; Zhu Ximing; Zhang Shuquan; Liu Tingting; Song Jiamei; Wang Yuhong; Guo Yanping; Li Xiaohong; Ji Xiaoyuan; Yao Bin (Chemical Engineering Journal, 2025)

Enhancing humification in high-temperature composting: Insights from endogenous and exogenous heating strategies - Chaoyue Zhao; Feng Ma; Youzhao Wang; Xu Li; Yanping Zhang; Zhipeng Wang; Wei Xiong; Xiaolong Gao; Yongguang Ma; Fuxin Yang; Tong Zhu (Bioresource Technology, 2025)

Aquaporin ZmPIP2;4 promotes tolerance to drought during arbuscular mycorrhizal fungi symbiosis - Ying Ni; Hui Bao; Ruifan Zou; Yanping Wang; Kailing Xie; Beijiu Cheng; Xiaoyu Li (Plant and Soil, 2025)

Suyin Detoxification Prescription Regulates the Klotho and ERK/NF-κB Signaling Pathways to Alleviate Renal Injury - Lianghui Shu; Li Quan; Yanping Wang; Yanlin Chen; Chen Yong; Fang Tian; Kun Gao; Enchao Zhou (Cell Biochemistry and Biophysics, 2025)

Genetic diversity and genetic structure in successive mass selected generations of tetraploid Pacific oysters (Crassostrea gigas), diploid Portuguese oysters (C. angulata) and their allotriploid oysters - Haitao Ma; Yanping Qin; Yinjie Zhang; Weitao Wan; Jingyue Huang; Na Mi; Zhen Zhao; Zhongyu Wang; Jiangwei Li; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2025)

Neurotoxicity study of cenobamate-induced zebrafish early developmental stages - Jiahao Liu; Liya Fang; Chao Gong; Jiawei Li; Yuanyuan Liu; Pei Zeng; Yanping Fan; Yao Liu; Jin Guo; Luchuan Wang; Yue Li (Toxicology and Applied Pharmacology, 2025)

Microtopography-induced hydrological heterogeneity promotes the co-assembly of vascular plant and biocrust communities, providing synergistic protective functions for the Great Wall - Yanping Liu; Wanfu Wang; Jing Ren; Yanhong Gao; Fasi Wu; Yafei Shi; Hongtao Zhan; Chengxu Chi; Rongliang Jia (Science of The Total Environment, 2025)

A scale for evaluating the willingness of national forest farm to participate in forest carbon sink project - Guanqing Wu; Degang Fu; Yingchao Xing; Huizhen Duan; Yifan Wang; Jihuai Hu; Yanping Wang; Fengjuan Zhang (Journal of Environmental Management, 2025)

New insights into interfacial dynamics and mechanisms of biochar–derived dissolved organic matter on arsenic redistribution in Schwertmannite - Xiaofei Li; Tianfu Li; Yanfu Wei; Xiaohu Jin; Suresh C. Pillai; Jun Zhang; Dian Chen; Xiaolian Wu; Yanping Bao; Xueding Jiang; Hailong Wang (Environmental Pollution, 2025)

Identification and characterization of Morganella morganii strain YC12-C3 and Enterococcus faecalis strain YC12-C10 and elucidation of its deoxynivalenol-degrading potential - Jiuchun An; Yefei Chen; Shihua Zhou; Yanping Gao; Changgui Yang; Jinqiang Zhang; Xiaohong Ou; Yanhong Wang; Weike Jiang; Tao Zhou; Qing-Song Yuan (Mycotoxin Research, 2025)

Unraveling the risk perception paradox: How benefits, self-efficacy, and social networks drive farmers’ landslide mitigation efforts in Gansu, China - Jue Wang; Yanping Wang; Rui Wang (Journal of Mountain Science, 2025)

Temporal dynamics of summer phytoplankton communities and their response to environmental changes in the northern Yellow Sea (2011-2020) - Yibo Wang; Zhiliang Liu; Yanping Qi; Yang Chen; Haibo Zhang; Xihan Liu; Du Su (Frontiers in Marine Science, 2025)
Research on phytoplankton distribution and dynamics is crucial for understanding marine ecosystem functions and evaluating their status. The northern Yellow Sea (NYS), a marginal sea of the Pacific Ocean, has experienced significant anthropogenic impacts since the late 20 th century, resulting in an increased nitrogen-to-phosphorus (N/P) ratio and heightened phosphorus limitation. These changes are considered critical factors affecting the phytoplankton community structure in the NYS over recent decades. This study analyzed the temporal dynamics of environmental factors and phytoplankton community structure in the NYS during the summers from 2011 to 2020, aiming to elucidate recent changes in phytoplankton community structure and their driving forces. The results indicated a significant decrease in dissolved inorganic nitrogen (DIN) concentration after 2011, resulting in a decreased N/P ratio, while phosphorus limitation persisted. Temperature, temperature gradient (reflecting stratification intensity) and salinity exhibited upward trends, whereas pH, nitrogen-to-silicon (N/Si) ratio, and chlorophyll- a concentration showed downward trends. The abundances of total phytoplankton, Bacillariophyta, and Dinoflagellata, as well as the Dia/Dino index, fluctuated annually and correlated with temperature, temperature gradient, and nutrient structure. Diversity indices remained stable throughout the study period. The Yellow Sea Cold Water Mass prominently influenced summer phytoplankton community structure, exhibiting lower phytoplankton abundance, Dia/Dino index, and species richness in the cold water mass region, where adaptable species such as Tripos muelleri and Paralia sulcata predominated. Our results emphasized the impact of environmental changes associated with climate change, including rising temperatures, increased salinity, and enhanced stratification, on the phytoplankton community structure in recent years, particularly concerning the dominant species composition and the Dia/Dino index. Therefore, ongoing attention to the effects of climate change on coastal environments and phytoplankton communities is essential.

Corrigendum to “Hybridization and growth characteristics of interspecific crosses between Crassostrea hongkongensis and Crassostrea iredalei” [Aquaculture, Volume 595, Part 2, 30 January 2025, 741656] - Jiangwei Li; Ying Pan; Qinggan Xing; Haitao Ma; Chao Yue; Weitao Wan; Jinhui Wu; Zhongyu Wang; Shengyong Li; Jun Li; Ziniu Yu; Yanping Qin; et al. (Aquaculture, 2025)

First successful inducing gynogenesis in Crassostrea angulata by inactivated tetraploid Crassostrea gigas sperm - Weitao Wan; Yanping Qin; Jinhui Wu; Haitao Ma; Chao Yue; Shengyong Li; Jiangwei Li; Zhongyu Wang; Jun Li; Anning Suo; Dewen Ding; Ziniu Yu; et al. (Aquaculture, 2025)

Mass mortality associated with carpione rhabdovirus in golden pompano (Trachinotus ovatus) in China: First report - Heng Sun; Jie Huang; Haoyu Wang; Yule Zhang; Qing Fei; Jie Zhou; Lindi Yang; Yanping Li; Jichang Jian; Yishan Lu; Shuanghu Cai; Yucong Huang (Aquaculture, 2025)

Hybridization and growth characteristics of interspecific crosses between Crassostrea hongkongensis and Crassostrea iredalei - Jiangwei Li; Ying Pan; Qinggan Xing; Haitao Ma; Chao Yue; Weitao Wan; Jinhui Wu; Zhongyu Wang; Shengyong Li; Jun Li; Ziniu Yu; Yanping Qin; et al. (Aquaculture, 2025)

Enhancing electrochemical reductive defluorination of PFASs using ZIF-67 modified cathode: Mechanistic insights and performance optimization - Xing Zhang; Han Wu; Yue Wang; Yafei Wang; Yangyang Deng; Yanping Zhu; Shengsen Zhang; Huub Rijnaarts; Harry Bruning; Junhao Qin; Qingqi Lin; Zhuobiao Ni; et al. (Water Research, 2025)

Facile fabrication of porous fluorinated polyurethane membranes for organic solvent adsorption based on thiol-ene click reaction within high internal phase emulsions - Aili Wang; Yuyang Liu; Yanping Yu; Minxin Song; Jinyue Li; Yutong Wang; Caiyang Zhang; Nan Lou; Fang Qi; Xueyi Han (Process Safety and Environmental Protection, 2025)

Forest transformation increases soil N2O fluxes in an unmanaged Moso bamboo forest - Yibo Yan; Xueying Tu; Hui Zhang; Yang Lv; Yihui Zhao; Ao Hu; Yanping Wu; Caixian Tang; Yixiang Wang (Forest Ecology and Management, 2025)

Phosphorus-oxygen modified anthracene-based emitters for high-efficiency deep-blue OLEDs approaching the BT.2020 blue standard - Ruicheng Wang; Yihong Zhu; Dehua Hu; Jie Hu; Si-wei Chen; Jieying Lin; Longjiang Xing; Yanping Huo; Shaomin Ji (Chemical Engineering Journal, 2025)

Engineered ADSCs and doxycycline encapsulated antibacterial, immunomodulatory and proangiogenic hydrogels for infected burn wound healing - Yanan Gu; Zhen Liang; Yanping Wang; Zhou Yu; Yubo Shi; Jinlong Luo; Xianghao Xu; Ke Fang; Hanli Wang; Baolin Guo; Baoqiang Song; Xin Zhao (Chemical Engineering Journal, 2025)

Bisulfite-free detection of DNA methylation in early-stage lung cancer with a multiplex SERS immunoassay - Dechan Lu; Yanping Chen; Longfeng Ke; Zufang Huang; Yudong Lu; Jing Wang (Chemical Engineering Journal, 2025)

A portable microfluidic platform for ultra-sensitive detection of ovarian cancer biomarkers via cascade signal amplification - Yuzhen Wang; Wenxiu Long; Yanping Wang; Yuanyue Han; Fei Zeng; Jingjing Li; Bangshun He; Yujun Song; Yanfeng Gao (Chemical Engineering Journal, 2025)

Highly degradable bio-based plastic with water-assisted shaping process and exceptional mechanical properties - Jingjing Wang; Yuan Liang; Yuhan Chen; Hai Wan; Wenbin Jin; Ting Luo; Yuwei Chen; Peng Wei; Shuohan Huang; Yong He; Yanping Wang; Yumin Xia (Carbohydrate Polymers, 2025)

Synthesis and Characterization of Efficient Adsorbents for Methylene Blue Based on Graphene Oxide/β-cyclodextrin Composites - Yanping Qu; Hongcui Li; Ibrahim Yakub; Wen He; Wenchan Dong; Mohamad Hardyman Barawi; Sirui Wang; Huimin Ma; Zhenpeng Zhu (Water, Air, & Soil Pollution, 2025)

Effects of cloprostenol and oxytocin on ultrasonographic changes of uterine horns in postpartum primiparous Hu sheep - Yixuan Li; Zongling Liu; Wenqian Zhang; Chunhao Zhu; Xi Chen; Yukun Zhao; Lei Liu; Ting Ting Zhu; Mingyang Geng; Yanping Wang; Weibin Zeng (Animal Reproduction Science, 2025)

Recovery of Coilia nasus resources after implementation of the 10-year fishing ban in the Yangtze River: implied from the Yangtze River Estuary and its adjacent sea areas - Shuyan Wang; Ying Xiong; Hushun Zhang; Dade Song; Yanping Wang; Hui Ge; Chengbin Zhang; Long Liang; Xiaming Zhong (Frontiers in Marine Science, 2024)
Introduction The implementation of the 10-year fishing ban in the Yangtze River has provided a crucial opportunity for the recovery of rare and endangered diadromous species, such as Coilia nasus . Methods In this study, we utilized electronic length–frequency analysis (ELEFAN) and length-based Bayesian biomass estimation (LBB) method to fit the body length data of C. nasus from the Yangtze River Estuary and its adjacent sea areas before and after the fishing ban (2019-2023), and the resource changes of C. nasus population were evaluated. Additionally, combined the catch production monitoring data from 2020 to 2022, we comprehensively analyzed the impact of the Yangtze River fishing ban on the recovery of C. nasus resources. Results The results showed that: (1) The proportion of quantity, weight and occurrence frequency of C. nasus in catches showed a significant increasing trend year by year. (2) 4,994 C. nasus were caught from 2021–2023, with body lengths ranging from 13–410 mm. In 2023, the average body length and weight of C. nasus had increased by 39.93% and 133.89%, respectively, from those in 2021. (3) ELEFAN estimated that the growth parameters after fishing ban, including asymptotic length, growth coefficient, and the theoretical age at length zero, were determined to be 42.92 cm, 0.43 year -1 , and -0.31 year, respectively. The total mortality rate, fishing mortality rate, and exploitation rate were determined to be 1.47 year -1 , 0.79 year -1 , and 0.54, respectively. (4) LBB estimated that the relative fishing mortality of C. nasus before the fishing ban increased from 1.22 in 2019 to 2.65 in 2020, while the relative biomass decreased from 0.34 to 0.22. After the fishing ban, the relative fishing mortality decreased from 0.85 in 2021 to 0.06 in 2023, and the relative biomass increased from 0.26 in 2021 to 0.90 in 2023, with a significant increase in 2022, indicating a clear recovery trend in C. nasus resources. Discussion By quantifying the resource characteristics of C. nasus before and after the 10-year fishing ban on the Yangtze River, this research revealed the impact of the ban and provided a reference for future systematic evaluations of the C. nasus population.

Monoclonal antibody development and antigenic epitope identification of infectious bursal disease virus VP5 - Jinze Han; Xinxin Niu; Chengfei Ge; Ziwen Wu; Guodong Wang; Mengmeng Huang; Yulong Zhang; Runhang Liu; Mengmeng Xu; Hangbo Yu; Jingzhe Han; Suyan Wang; et al. (The Veterinary Journal, 2024)

Unveiling the impact of exposed mineral facets on chromium repartitioning in aging lepidocrocite - Xiaofei Li; Chuling Guo; Xiaohu Jin; Qian Yao; Yanping Bao; Xueding Jiang; Guining Lu; Suresh C. Pillai; Hailong Wang; Zhi Dang (Science of The Total Environment, 2024)

Assessing the feasibility of adjusting the dry matter content utilizing corn grits and cottonseed meal and inoculating with Lactiplantibacillus plantarum in the production of fermented feed from kitchen waste - Yupeng Tang; Fengyuan Yang; Huili Pang; Shanshan Zhao; Hengyu Ma; Haolong Li; Yuhang Huang; Pintian Sun; Xiaoxue Tang; Yanping Wang (Process Safety and Environmental Protection, 2024)

Dynamic aromatics: Evaluating fragrance quality shifts and implementation of real-time rapid detection in Hedychium cut flowers during senescence - Yiwei Zhou; Qin Wang; Xue Wei; Ting Gao; Farhat Abbas; Fulong Yan; Jingjuan He; Yunyi Yu; Rangcai Yu; Yanping Fan (Postharvest Biology and Technology, 2024)

Research on parametric roll of the polar environmental transport ship based on time-domain Rankine panel method - Wei Zhang; Yadong Liu; Yanping He; Yan Zhou; Dong Wang; Yuying Tang; Jianmei Chen (Ocean Engineering, 2024)

A solar thermoelectric system by temperature difference for efficient removal of chromium (VI) in water and soil - Dongqing Cai; Rongxi Hu; Minxue Guo; Dongfang Wang; Yanping Zhu; Chen Sun; Xinyan Chen; Jinghong Ye; Xianghai Kong; He Xu (Journal of Hazardous Materials, 2024)

Insights into the interactions of plant-associated bacteria and their role in the transfer of antibiotic resistance genes from soil to plant - Yanping Shen; Baiyu Zhang; Ye Yao; Hanbo Wang; Zhilu Chen; Anjing Hao; Ping Guo (Journal of Hazardous Materials, 2024)

An evaluation method for synergistic effect of air pollutants and CO2 emission reduction in the Chinese petroleum refining technology - Dandan Liu; Xueying Li; Dong Wang; Hao Wu; Yanping Li; Yanjun Li; Qi Qiao; Zhou Yin (Journal of Environmental Management, 2024)

Effect of Cd2+ and Cu2+ on Desulfovibrio vulgaris strain ATCC 7757: Insights from sulfur isotope fractionation - Qinglin Zhuang; Chuling Guo; Siyu Zhang; Meihui Ren; Yanping Deng; Chaoping Wang; Han Ye; Zhi Dang (Journal of Environmental Chemical Engineering, 2024)

Ferrihydrite optimizing Feammox inoculum to enhance ammonia removal from concentrate wastewater through continuous upflow anaerobic sludge blanket (UASB) - Linji Xu; Lin Li; Jianxi Liu; Xingzu Wang; Yanping Zhao; Jujiao Zhao; Li Gu; Qiang He; Xinzhu Wang; Jinhua Zhang (Journal of Environmental Chemical Engineering, 2024)

Characteristics of volatile organic compounds under different operating conditions in a petrochemical industrial zone and their effects on ozone formation - Yanping Yang; Xianhong Meng; Qiang Chen; Qiang Xue; Lina Wang; Jian Sun; Wenkai Guo; Huijie Tao; Lili Yang; Feifei Chen (Environmental Pollution, 2024)

Effect of rebar ratio, rebar diameter, cover thickness, and fiber shape on flexural and cracking behavior of rebar-reinforced UHPC beams - Minghong Qiu; Xudong Shao; Kay Wille; Yanping Zhu; Yan Wang; Yang Zhang; Zhenyu Tao (Engineering Structures, 2024)

Protonated polyethyleneimine enables synchronous crosslinking of polyimide nanofiltration membranes for dye desalination - Qing Fang; Sudan Lan; Xiuxiu Mu; Yanping Zhang; Ya Li; Yajuan Wang; Lihui Yao; Yuyun Chen; Dan Qiu; Linghui Wang (Desalination, 2024)

A 3D self-floating evaporator loaded with phase change energy storage materials for all-weather desalination - Yuqin Teng; Shuai Li; Yanxia Luo; Xin Yi; Libang Feng; Dianming Li; Yanping Wang (Desalination, 2024)

Unveiling the adsorption behavior and mass transfer mechanism of Rb+ and Cs+ adsorption on FeMn-MOF - Yanping Wang; Xiushen Ye; Qiongyuan Zhang; Wenjie Han; Xing Liu; Huifang Zhang; Haining Liu; Zhijian Wu; Guosheng Shi (Chemical Engineering Journal, 2024)

Outstanding enhancement of caproate production with microwave pyrolyzed highly reductive biochar addition - Qinglian Wu; Lin Deng; Tian Lan; Hui Wang; Kaiming Wang; Huacheng Zhu; Yanping Zhou; Wanqian Guo (Bioresource Technology, 2024)

Biological invasion is eroding the unique assembly of island herpetofauna worldwide - Weishan Tu; Yuanbao Du; Yoel E. Stuart; Yanxia Li; Yanping Wang; Qingfa Wu; Baocheng Guo; Xuan Liu (Biological Conservation, 2024)

Enhanced 3D dose prediction for hypofractionated SRS (gamma knife radiosurgery) in brain tumor using cascaded-deep-supervised convolutional neural network - Nan Li; Jinyuan Wang; Yanping Wang; Chunfeng Fang; Yaoying Liu; Chunsu Zhang; Dongxue Zhou; Lin Cao; Gaolong Zhang; Shouping Xu (Physical and Engineering Sciences in Medicine, 2024)

Auxin Receptor TRANSPORT INHIBITOR RESPONSE1 Promotes Tulip Plant Growth and Bulb Swelling - Qi Sun; Bei Zhang; Lin Xiang; Yanping Wang; Zhulong Chan (Journal of Plant Growth Regulation, 2024)

Salidroside Reduced Ca2+-CaM-CAMKII-Dependent eNOS/NO Activation to Decrease Endothelial Cell Injury Induced by Cold Combined with Hypoxia - Hongjin Wang; Xianzhen Wang; Yanping Feng; Kewei Zhang; Maodongzhi Peng; Xiaowei Wu; Yi Li (Cell Biochemistry and Biophysics, 2024)

A prediction method for favorable hydrocarbon accumulation areas in carbonate oil reservoirs based on machine learning and driven by formation water chemical characteristic data - Zhiwei Chen; Jianbo Gao; Hong Pang; Zhipeng Huo; Ningliang Sun; Yanping Lv; Yan Wang; Bo Wu (Carbonates and Evaporites, 2024)

Sedimentary dynamics in southern Mariana Trench and its controlling factors in past 440 kyr - Zhongshan Shen; Haifeng Wang; Yanping Chen; Yun Cai; Liang Yi (Frontiers in Marine Science, 2024)
Understanding sediment dynamics and their controlling factors is essential for Quaternary studies, yet they remain poorly documented in the Mariana Trench. In this work, we examine this basic character from a sediment core collected at a depth of 6470 m from the southern part of the Mariana Trench, documenting changes in sedimentary dynamics over the past ~440 kyr. Our primary findings are as follows: (1) The median grain size is 13.6 ± 12.0 μm, and minimal changes in clay (30.9 ± 9.4%) and silt (56.6 ± 4.0%) contents, indicating a low-dynamic depositional environment; (2) Three grain-size components were identified, characterized by modal changes of ~4/60 μm, ~20 μm, and >100 μm. By comparing these results with various environmental proxies, including glacial-interglacial alternations, eolian input, and bottom-water intensity, we suggest that marine productivity has a dominant influence on deep-sea sediment dynamics, though post-depositional processes also contribute. Additionally, topographical conditions and sea-water chemistry appear to be related to the presence of coarse particles, possibly through coarse transport and micro-nodule development. Overall, grain-size parameters provide a valuable investigative tool for understanding the various influences on sediment dynamics in this region.

Three birds with one stone: Sewage sludge deep-drying in 1 hour using secondary aluminum ash to fabricate bricks - Xianghai Kong; Yanping Zhu; He Xu; Jinghong Ye; Shuang Wang; Heliang Xu; Rongjun Zhang; Hongxia Tang; Dongfang Wang; Dongqing Cai (Water Research, 2024)

The modulation of proteomics and antioxidant stress is involved in the effect of nitazoxanide against Japanese encephalitis virus in vitro - Yu Su; Yanping Wang; Chengeng Xiong; Xiaoyang Wang; Chunmei Wang; Wen Zhou; Donghai Zhou; Keyu Zhang (Veterinary Microbiology, 2024)

Recombinant Marek’s disease virus type 1 provides full protection against H9N2 influenza A virus in chickens - Yuntong Chen; Qingqing Yu; Wenrui Fan; Xianying Zeng; Zibo Zhang; Guobin Tian; Changjun Liu; Hongmei Bao; Longbo Wu; Yanping Zhang; Yongzhen Liu; Suyan Wang; et al. (Veterinary Microbiology, 2024)

Mobilization of phosphorus in sediments of eutrophic lakes induced by elevated sulfate levels - Lanqing Zhang; Miaotong Yu; Simin Yu; Huaizhi Chen; Mengmeng Xiao; Guoxiang Wang; Yanping Zhao (Science of The Total Environment, 2024)

Microplastics distribution, ecological risk and outflows of rivers in the Bohai Rim region of China - A flux model considering small and medium-sized rivers - Xin Hou; Jiayao Li; Hongyu Li; Shuyun Du; Sitong Liu; Shipu Jiao; Fuxin Niu; Jianbo Tu; Yanping Zong; Xiaotong Wang; Xianhua Liu (Science of The Total Environment, 2024)

Vascular plants and biocrusts ameliorate soil properties serving to increase the stability of the Great Wall of China - Yanping Liu; Jing Ren; Wanfu Wang; Yafei Shi; Yanhong Gao; Hongtao Zhan; Yayong Luo; Rongliang Jia (Science of The Total Environment, 2024)

Sustainable upcycling of copper from waste printed circuit boards with the assistance of tannic acid and Fe3+ to a magnetic heterogeneous catalyst - Yanping Zhong; Sisi Hu; Jinghua Xu; Zhenguo Chen; Shuhua Wang (Journal of Environmental Management, 2024)

Rapid redox-response featured visual ascorbic acid sensor based on simple-assembled europium metal-organic framework - Lin-Lin Zhang; Li Li; Dan Wang; Yanping Hong; Kaijie Tang; Jiaxin Hong; Zeng Chen; Wuying Yang; Limin Lu; Lu-Ying Duan (Food Chemistry, 2024)

Dynamic of phytoplankton community during varying intensities of the northeast monsoon in the Taiwan Strait - Yanping Zhong; Peixuan Wang; Jinxin Chen; Xin Liu; Edward A. Laws; Bangqin Huang (Acta Oceanologica Sinica, 2024)

Early diagenesis, sedimentary dynamics and metal enrichment reveal deep-sea ventilation in Magellan Seamounts during the middle Pleistocene - Zhongshan Shen; Yanping Chen; Pavel Mikhailik; Yun Cai; Haifeng Wang; Liang Yi (Frontiers in Marine Science, 2024)
Seamounts are ubiquitous topographic units in the global oceans, and the Caiwei Guyot in the Magellan Seamounts of the western Pacific is a prime example. In this study, we analyzed a well-dated sediment core using magnetic properties, sediment grain size, and metal enrichment to uncover regional ventilation history during the middle Pleistocene and explore potential linkages to global climate changes. Our principal findings are as follows: (1) The median grain size is 3.3 ± 0.2 μm, and clay and silt particles exhibit minimal variation, with average values of 52.8 ± 1.8% and 38.2 ± 1.6%, respectively, indicating a low-dynamic process; (2) Three grain-size components are identified, characterized by modal patterns of ~3 μm (major one), ~40 μm, and 400–500 μm, respectively; (3) Magnetic coercivity of the deep-sea sediments can be classified into three subgroups, and their coercivity values are 6.1 ± 0.5 mT, 25.7 ± 1.0 mT, and 65.2 ± 2.1 mT. Based on these results, we propose a close linkage between magnetic coercivity and metal enrichment, correlating with changes in deep-sea circulation intensity. Conversely, sediment grain-size changes seem to be more strongly influenced by eolian inputs. Consequently, we suggest that regional ventilation has weakened since ~430 ka, likely linked to a reduction in Antarctic bottom water formation.

Successive selection responses of tetraploid Crassostrea angulata: Comparison of growth, survival, sex ratio and ploidy composition between selected and unselected groups - Yanping Qin; Weitao Wan; Jiangwei Li; Chao Yue; Zhongyu Wang; Qinggan Xing; Haitao Ma; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Facile in-situ fabrication of graphene oxide/poly(ionic liquid) composites and their adsorption performance for methyl orange - Xiaoying Wang; Yuyang Liu; Xiuzhi Liu; Caiyang Zhang; Minxin Song; Yanping Yu; Xueyi Han; Jinyue Li; Aili Wang (Process Safety and Environmental Protection, 2024)

PhERF71 regulates petunia flower senescence by modulating ethylene biosynthesis - Xiaotong Ji; Yanxiang Mao; Yanping Yuan; Meiling Wang; Yike Zhao; Lei Zhang; Daoyang Sun (Postharvest Biology and Technology, 2024)

Prediction of drought hydrological and water scarcity based on optimal artificial intelligence by developing a metaheuristic optimization algorithm - Yanping Wang; Saeid Razmjooy (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Prediction and empirical formula correction for brash ice resistance using CFD-DEM based on invisible bulbous bow ship - Jianmei Chen; Zhe Chen; Dong Wang; Yuqing Zhang; Yanping He (Ocean Engineering, 2024)

New role of radical-induced polymerization: Base/self-heating synergistically activate persulfate to boost food waste humification - Dongqing Cai; Xiaoya Pan; Chengjin Wang; Shihu Shu; Pengjin Zhu; Chunhuo Zhou; Dongfang Wang; He Xu; Yanbiao Liu; Wenhai Chu; Xiang Li; Yanping Zhu (Journal of Cleaner Production, 2024)

Virtual screening reveals fluorescent probes for detecting Pan-Zinc center activity in serum MMPs: A potential biomarker for early tumor screening - Shang Ju; Yi Xiang; Yajun Xie; Lei Zuo; Juqiong Li; Xiaorong Li; Yanping Wang; Qin Huang; Min Zhang; Xiaomian Wu; Yuanyuan Wang; Qiong Shi; et al. (Chemical Engineering Journal, 2024)

Waste milk-derived biodegradable mulch film fabrication and nutrient slow-release performance evaluation - Yanping Zhu; Bingbing Fu; Pengjin Zhu; Shihu Shu; Dongfang Wang; He Xu; Dongqing Cai (Chemical Engineering Journal, 2024)

Quinary metal oxide NiCoMnCeCaOx nanorod as a multifunctional catalyst towards hydrogen production from ethanol steam reforming: Synergistic effect of polymetallic component - Mingzheng Liao; Chunrun Qin; Liujie Xu; Sihan Guo; Chao Wang; Yi Li; Wei Liu; Qingbin Song; Ying Chen; Yanping Du (Chemical Engineering Journal, 2024)

Understandings in surface metal exsolution of NiFeZn ternary alloy/spinel in ethanol steam reforming: The key to hydrogen production - Mingzheng Liao; Wei Liu; Congkang Li; Sihan Guo; Yanyu Chen; Chao Wang; Ying Chen; Yanping Du (Chemical Engineering Journal, 2024)

Heterostructure-anchored 3D CNT-bridged graphene architecture via layer-by-layer structural engineering for thick electrodes of supercapacitors - Yanping Song; Nian Li; Jun Kang; Zhao Li; Na Hong; Shuai Han; Liqing Chen; Shudong Zhang; Cui Liu; Congfa Song; Jiakuan Zhang; Zhenyang Wang (Chemical Engineering Journal, 2024)

Adsorption mechanism and remediation of heavy metals from soil amended with hyperthermophilic composting products: Exploration of waste utilization - Feng Ma; Tong Zhu; Youzhao Wang; Shuichi Torii; Zhipeng Wang; Chaoyue Zhao; Xu Li; Yanping Zhang; Haoyu Quan; Chunli Yuan; Liying Hao (Bioresource Technology, 2024)

Cellular Senescence-Related Long Non-coding RNA Signatures Predict Prognosis in Juvenile Osteosarcoma - Peng Zhao; Junli Chang; YeKai Chen; Xingyuan Sun; Xiaoping Ma; Chujie Zhou; Lei Zhou; Yongjun Wang; Yanping Yang (Phenomics, 2024)
Osteosarcoma is the most common malignant bone tumor and is frequently diagnosed in juvenile. Cellular senescence is a fundamental hallmark of osteosarcoma and plays a vital role in the initiation and progression of aging and tumorigenesis. Long non-coding RNAs (lncRNAs) are implicated in tumorigenesis. In this study, six cellular senescence-related lncRNAs with independent prognostic significance in juvenile osteosarcoma patients were identified through univariate Cox regression analysis, least absolute shrinkage and selection operator (LASSO) regression analysis, and multivariate Cox regression analysis. Prognostic significance was further confirmed by Kaplan–Meier (KM) survival curves, co-expression interaction networks, and sankey diagrams. A prognostic model of cellular senescence-related genes in juvenile osteosarcoma patients was then constructed using multivariate Cox regression analysis based on these six genes. High- and low-risk groups were identified according to the median risk score calculated by the prognostic model. The favorable prognostic significance of this model was demonstrated through survival curves, receiver operating characteristic (ROC) curves, distribution scatter plots and lncRNA expression heatmaps. Furthermore, cellular senescence-related lncRNAs were validated by enrichment analysis, immunological correlation analysis, m 6 A correlation analysis, and drug sensitivity correlation analysis. These findings are important for improving the prognosis of juvenile osteosarcoma patients and understanding the mechanisms underlying cellular senescence in juvenile osteosarcoma development.

Targeting PI3K/Akt in Cerebral Ischemia Reperfusion Injury Alleviation: From Signaling Networks to Targeted Therapy - Ting Zheng; Taotao Jiang; Hongxiang Ma; Yanping Zhu; Manxia Wang (Molecular Neurobiology, 2024)

DGA ameliorates severe acute pancreatitis through modulating macrophage pyroptosis - Xiyue Yue; Lunmeng Lai; Ruina Wang; Lulu Tan; Yanping Wang; Qing Xie; Yunsen Li (Inflammation Research, 2024)

Bi-allelic missense variants in MEI4 cause preimplantation embryonic arrest and female infertility - Zhiqi Pan; Weijie Wang; Ling Wu; Zhongyuan Yao; Wenjing Wang; Yao Chen; Hao Gu; Jie Dong; Jian Mu; Zhihua Zhang; Jing Fu; Qiaoli Li; et al. (Human Genetics, 2024)

Numerical simulation on staggered grids of three-dimensional brinkman-forchheimer flow and heat transfer in porous media - Wei Liu; Yingxue Song; Yanping Chen; Gexian Fan; Pengshan Wang; Kai Li (Computational Geosciences, 2024)

Response of phytoplankton communities to environmental changes in the Bohai Sea in late summer (2011–2020) - Yibo Wang; Zhiliang Liu; Yanping Qi; Xiao Chen; Yang Chen; Du Su; Xiaobo Yuan; James Klippel-Cooper (Acta Oceanologica Sinica, 2024)

Design of Auto-Adaptive Drug Delivery System for Effective Delivery of Peptide Drugs to Overcoming Mucus and Epithelial Barriers - Ruihuan Ding; Yanping Li; Wei Zheng; Yiying Sun; Zhenyu Zhao; Houqian Zhang; Ranran Yuan; Aiping Wang; Kaoxiang Sun; Hongbo Wang; Yanan Shi (The AAPS Journal, 2024)

Regional Sea Level Changes in the East China Sea from 1993 to 2020 Based on Satellite Altimetry - Lujie Xiong; Fengwei Wang; Yanping Jiao (Journal of Marine Science and Engineering, 2024)
A comprehensive analysis was carried out to investigate the driving factors and influencing mechanisms of spatiotemporal variation of sea level at multiple scales in the East China Sea (ECS) via satellite altimetry datasets from 1993 to 2020. Based on the altimetry grid data processed by the local mean decomposition method, the spatiotemporal changes of ECS sea level are analyzed from the multi-scale perspective in terms of multi-year, seasonal, interannual, and multi-modal scales. The results revealed that the ECS regional mean sea level change rate is 3.41 ± 0.58 mm/year over the 28-year period. On the seasonal scale, the regional mean sea level change rates are 3.45 ± 0.66 mm/year, 3.35 ± 0.60 mm/year, 3.39 ± 0.71 mm/year, and 3.57 ± 0.75 mm/year, for the four seasons (i.e., spring, summer, autumn, and winter) respectively. The spatial distribution analysis showed that ECS sea level changes are most pronounced in coastal areas. The northeast sea area of Taiwan and the edge of the East China Sea shelf are important areas of mesoscale eddy activity, which have an important impact on regional sea level change. The ECS seasonal sea level change is mainly affected by monsoons, precipitation, and temperature changes. The spatial distribution analysis indicated that the impact factors, including seawater thermal expansion, monsoons, ENSO, and the Kuroshio Current, dominated the ECS seasonal sea level change. Additionally, the ENSO and Kuroshio Current collectively affect the spatial distribution characteristics. Additionally, the empirical orthogonal function was employed to analyze the three modes of ECS regional sea level change, with the first three modes contributing 26.37%, 12.32%, and 10.47%, respectively. Spatially, the first mode mainly corresponds to ENSO index, whereas the second and third modes are linked to seasonal factors, and exhibit antiphase effects. The analyzed correlations between the ECS sea level change and southern oscillation index (SOI), revealed the consistent spatial characteristics between the regions affected by ENSO and those by the Kuroshio Current.

Effect of biochar-derived DOM on contrasting redistribution of chromate during Schwertmannite dissolution and recrystallization - Xiaofei Li; Tianfu Li; Paramsothy Jeyakumar; Jiayi Li; Yanping Bao; Xiaohu Jin; Jun Zhang; Chuling Guo; Xueding Jiang; Guining Lu; Zhi Dang; Hailong Wang (Journal of Hazardous Materials, 2024)

Corrigendum to “Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake” [Journal of Contaminant Hydrology 261 (2024) 104306] - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Dynamic relationships and propagation characteristics between meteorological drought and vegetation drought based on a three-dimensional identification algorithm - Fei Wang; Hexin Lai; Zipeng Wang; Ruyi Men; Yanbin Li; Yunzhong Jiang; Kai Feng; Qingqing Tian; Xuefang Du; Yanping Qu (Global and Planetary Change, 2024)

Accumulation and ecological risk assessment of diazinon in surface sediments of Baiyangdian lake and its potential impact on probiotics and pathogens - Yaping Wang; Rong Xiao; Yanping Hu; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Wenbin Pan (Environmental Pollution, 2024)

High recoverable energy storage density and efficiency achieved in doped NaNbO3 ceramics via composition design strategy for pulsed power capacitor - Renkai Zhao; Kaiyuan Wang; Wenhua Li; Yujia Yuan; Xingui Tang; Jia Hu; HuaXiang Fan; Kaijie Chen; Wanglai Song; Yanping Jiang; Xiaobing Guo (Chemical Engineering Journal, 2024)

A numerical method for two-dimensional transient nonlinear convection-diffusion equations - Xiangyuan Meng; Mei Huang; Boxue Wang; Xiaoping Ouyang; Yanping Huang; Denggao Chen; Yanting Cheng; Yaodi Li (Annals of Nuclear Energy, 2024)

The applicability of a SIF-based mechanistic model for estimating GPP at the canopy scale - Yanping Liu; Zhaoyong Hu; Genxu Wang; Arthur Gessler; Shouqin Sun (Agricultural and Forest Meteorology, 2024)

An explainable integrated machine learning model for mapping soil erosion by wind and water in a catchment with three desiccated lakes - Hamid Gholami; Mehdi Jalali; Marzieh Rezaei; Aliakbar Mohamadifar; Yougui Song; Yue Li; Yanping Wang; Baicheng Niu; Ebrahim Omidvar; Dimitris G. Kaskaoutis (Aeolian Research, 2024)

A global assessment of nested patterns in insular mammal assemblages - Virginie Millien; Chengxiu Zhan; Yanxia Li; Jiang Wang; Yanping Wang (Global Ecology and Biogeography, 2024)
Aim A nested pattern (nestedness) in species composition is a frequent signature of insular communities. However, it remains unclear whether the drivers of nestedness are consistent across multiple island systems. Here, we investigated the pattern and drivers of taxonomic, functional and phylogenetic nestedness in terrestrial mammal assemblages from 10 distinct island systems (archipelagos). Location Global. Time period Contemporary. Major taxa studied Terrestrial mammals. Methods We compiled occurrence data and species traits of terrestrial mammals from 228 islands in 10 distinct island assemblages. We assembled a dataset of island biogeographic characteristics for each of these islands, including island area, isolation index and maximum elevation. For all 10 assemblages, we first tested for significant patterns of taxonomic, functional and phylogenetic nestedness. We then examined the associations between nestedness, island biogeographic characteristics and species traits. Results We detected significant patterns of taxonomic, functional or phylogenetic nestedness in mammal assemblages from all 10 archipelagos. Biogeographic characteristics of islands affecting the rate of extinction in island species, namely, island area and elevation, were significantly associated with the degree of nestedness in these assemblages. Traits associated with the extinction probability of a species, such as litter size, further drove the nested pattern in some assemblages. Main conclusions All analyses pointed to selective extinction as a main mechanism shaping the observed nested patterns in island mammal assemblages. From a conservation point of view, different management strategies should be implemented for mammal assemblages in these island systems by identifying the drivers of species extinction rates specific to each island system and species occurring on these islands.

Feasibility exploration and comparative analysis of interspecific hybridization between Crassostrea hongkongensis and Crassostrea dianbaiensis - Jiangwei Li; Yanping Qin; Zhongli Peng; Weitao Wan; Chao Yue; Zhongyu Wang; Haitao Ma; Qinggan Xing; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Aquaculture, 2024)

Spatial heterogeneity and driving mechanisms of carbon storage in the urban agglomeration within complex terrain: Multi-scale analyses under localized SSP-RCP narratives - Hongyi Zhang; Xin Li; Yanping Luo; Lu Chen; Minxi Wang (Sustainable Cities and Society, 2024)

Corrigendum to “Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors” [Sci. Total Environ. 913 (2024) 169628] - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Enhanced ofloxacin degradation in water by a novel integrated photocatalysis and rotating magnetic field system - Ning Ding; Sijia Zhang; Jianxin Zhang; Yang Zhan; Bokang Wang; Hong Liu; Yanping Zhang; Yingxue Sun (Journal of Water Process Engineering, 2024)

Comparison of anaerobic co-digestion of vacuum toilet blackwater and kitchen waste under mesophilic and thermophilic conditions: Reactor performance, microbial response and metabolic pathway - Ziang Wang; Haixiang Li; Pingbo Wang; Jia Zhu; Ziyi Yang; Yanping Liu (Journal of Environmental Management, 2024)

Simultaneous removal of tetracycline hydrochloride and hexavalent chromium by heterogeneous Fenton in a photocatalytic fuel cell system - Jinghong Ye; He Xu; Xianghai Kong; Yong Zhang; Yuhan Chen; Benji Zhou; Yanping Zhu; Dongqing Cai; Dongfang Wang (Journal of Environmental Management, 2024)

Preparation of ternary composite film TiO2/Fe2O3/Ti3C2 for photoelectrocatalytic degradation of organic pollutants and bacterial inactivation in water - Yanping Ma; Jialin Gu; Xinshang Li; Wenquan Zhou; He Wang; Rui Zhang; Jiangang Jiang (Journal of Environmental Chemical Engineering, 2024)

Leaf morpho-anatomy and taxonomic significance in five Dendrobium sect. Stachyobium species from China - Yunxi Xie; Yanping Wang; Lei Tao; Wenhao Liu; Yan Luo; Lu Li (Flora, 2024)

Self-assembled multifunctional Prussian blue analogues nanocomposite for MRI-guided multimodal therapy for breast cancer - Min Zhang; Yanping Wu; Xingchen Lu; Yuhan Qin; Cong Zhang; Wenjie Gu; Ruochen Gao; Yuanyuan Qi; Meng Wang; Qingli Huang (Chemical Engineering Journal, 2024)

Potential modulation strategy on bismuth vanadate-based semiconductor to enhance antibiotic degradation in heterogeneous electro-Fenton system - Jinghui Pan; Zimu Zhang; Zuofang Yao; Songyu Fan; Tingting Zhu; Chenchen Xing; Yujia Liu; Jianhua Chen; Hongxiang Zhu; Yanping Hou; Shuangfei Wang (Chemical Engineering Journal, 2024)

An EEG-based marker of functional connectivity: detection of major depressive disorder - Ling Li; Xianshuo Wang; Jiahui Li; Yanping Zhao (Cognitive Neurodynamics, 2024)

Differences in Precipitation and Related Wind Dynamics and Moisture and Heat Features in Separate Areas of the South China Sea before and after Summer Monsoon Onset - Chunyan Zhang; Donghai Wang; Kaifeng Zhang; Wanwen He; Yanping Zheng; Yan Xu (Advances in Atmospheric Sciences, 2024)

Connotation analysis and path discussion of China’s land-sea coordination policy: based on the interregional externality theory - Yanping Li; Yuping Wang; Dahai Liu; Yuting Hou (Frontiers in Marine Science, 2024)
As two spatial geographic units that are both independent of each other and closely linked, the land and sea have complex spatial interactions. Therefore, China implements the land-sea coordination policy (LSC) needs to be approached from a more macroscopic, systematic and comprehensive perspective. Based on the interregional externality theory, this study takes the land-sea coordination policy of China as an example, and focuses on the interaction process and manifestation between land and sea, and then explores the connotation and realization path of LSC. Firstly, we delineated the spatial unit and analyzed the land-sea interactions (LSI) using Vensim software. Secondly, the characteristics and manifestations of LSI are summarized from the perspective of interregional externalities. Finally, this study elucidates the foundational concept of implementing LSC and further propose actionable pathways for promoting land and sea development in a coordinated way, aimed at offering supportive decision-making insights for achieving LSC within the broader framework of China’s territorial spatial planning. Initiating LSC implementation involves strategies such as source control, process management, and interaction interface optimization. Deepening LSC effectiveness entails strengthening positive interregional externalities while mitigating negative interregional externalities.

Dominant microbiome iteration and antibiotic resistance genes propagation way dictate the antibiotic resistance genes contamination degree in soil-plant system - Yanping Shen; Cancan Jiang; Baiyu Zhang; Hongjie Gao; Xu Wang; Ping Guo (Journal of Cleaner Production, 2024)

A strategy to assess the use-phase carbon footprint from energy losses in electric vehicle battery - Boran Yang; Chenran Du; Hang Zhang; Xiaoli Ma; Xueling Shen; Dong Wang; Zhanglong Yu; Qian Huang; Danni Gao; Yanping Yin; Yanyan Fang; Ran Xu (Journal of Cleaner Production, 2024)

Prioritizing the multifaceted community and species uniqueness for the conservation of lacustrine fishes in the largest subtropical floodplain, China - Yang Liu; Yang Yan; Li Lin; Linlong Wang; Yanping Zhang; Bin Kang (Journal of Environmental Management, 2024)

2,4,6-trinitrotoluene causes mitochondrial toxicity in Caenorhabditis elegans by affecting electron transport - Yanping Zhou; Chunyan Wang; Yaguang Nie; Lijun Wu; An Xu (Environmental Research, 2024)

Highly stable ultralong organic phosphorescence from a 3D organic supramolecule constructed by halogen bonding and π–π interactions - Aiping Yao; Jing Gao; Yingxiao Mu; Guangfu Li; Kuizhan Shao; Guogang Shan; Yun Geng; Yanping Huo; Zhongmin Su; Xinlong Wang (Chemical Engineering Journal, 2024)

Identification and functional analysis of floral terpene synthase genes in Curcuma alismatifolia - Zihan Cao; Lan Wang; Di Huang; Guilan Wu; Xinyue Li; Yuechong Yue; Yunyi Yu; Rangcai Yu; Yanping Fan (Planta, 2024)

Involvement of a rice mutation in storage protein biogenesis in endosperm and its genomic location - Huaidong Tian; Ying Li; Yanping Guo; Yajuan Qu; Xiaoye Zhang; Xiaoxian Zhao; Xinya Chang; Baohua Tian; Guangyuan Wang; Xiangmei Yuan (Planta, 2024)

Knocking out Selenium Binding Protein 1 Induces Depressive-Like Behavior in Mice - Yi Jia; Xin Zhang; Yongmei Wang; Yang Liu; Jie Dai; Liangliang Zhang; Xian Wu; Jie Zhang; Hongxi Xiang; Yanping Yang; Zhu Zeng; Yulian Chen (Biological Trace Element Research, 2024)

AKR1C2 genetic variants mediate tobacco carcinogens metabolism involving bladder cancer susceptibility - Yanping Xiao; Yang Shen; Hui Song; Fang Gao; Zhenguang Mao; Qiang Lv; Chao Qin; Lin Yuan; Dongmei Wu; Haiyan Chu; Meilin Wang; Mulong Du; et al. (Archives of Toxicology, 2024)

Loop PDE of viral capsid protein is involved in immune escape of the emerging novel variant infectious bursal disease virus - Guodong Wang; Nan Jiang; Hangbo Yu; Xinxin Niu; Mengmeng Huang; Yulong Zhang; Wenying Zhang; Jinze Han; Mengmeng Xu; Runhang Liu; Ziwen Wu; Jingzhe Han; et al. (Veterinary Microbiology, 2024)

Enhanced Sb(V) removal of sulfate-rich wastewater by anaerobic granular sludge assisted with Fe/C amendment - Qi Li; Yanping Zhu; Nan Jiang; Jun Li; Yanbiao Liu; Xiaoguang Chen; Xiaoyang Xu; Huangyingzi Wang; Yimeng Ma; Manhong Huang (Science of The Total Environment, 2024)

A SCYL2 gene from Oryza sativa is involved in phytosterol accumulation and regulates plant growth and salt stress - Minyan Xu; Ying Ni; Yaling Tu; Yanping Wang; Zhi Zhang; Yuhuan Jiao; Xin Zhang (Plant Science, 2024)

Estimating and partitioning evapotranspiration in a film mulched cropland with shallow groundwater by the improved dual source model - Xingwang Wang; Qiangli Wei; Weishu Wang; Shuai Wang; Zailin Huo; Yanping Qu; Juan Lyu; Huimin Lei (Journal of Hydrology, 2024)

Gold-copper-doped lanthanide luminescent metal-organic backbone induced self-enhanced molecularly imprinted ECL sensors for ultra-sensitive detection of chlorpyrifos - Yishan Fang; Yanping Li; Xufeng Zang; Yingxue Chen; Xinran Wang; Na Wang; Xiangying Meng; Bo Cui (Food Chemistry, 2024)

Recent advances in the authentication (geographical origins, varieties and aging time) of tangerine peel (Citri reticulatae pericarpium): A review - Yanxin Li; Wenhong Zhao; Min Qian; Zhiyi Wen; Weidong Bai; Xiaofang Zeng; Hong Wang; Yanping Xian; Hao Dong (Food Chemistry, 2024)

Electron transfer mediated photo-Fenton-like synergistic catalysis of Fe,Cu-doped MIL-101 coupled with Ag3PO4: Quantitative evaluation and DFT calculations - Xiaojuan Chen; Liang Yao; Song Xu; Juhua He; Ning Li; Jiaxin Li; Bin Liu; Yanping Zhu; Xin Chen; Hailong Wang; Runliang Zhu (Environmental Pollution, 2024)

Multifunctional Ac@ZIF-8/AgNPs nanoplatform with pH-responsive and ROS scavenging antibacterial properties promotes infected wound healing - Yipeng Pang; Maofang Zhao; Yuhan Xie; Yanping Wang; Yuxin You; Yongding Ke; Chaoyi Zhang; Xiaohan Chen; Yijia Yang; Chunlei Zhang; Xi Chen; Yi Liu; et al. (Chemical Engineering Journal, 2024)

Sequence and epigenetic variations of R2R3-MYB transcription factors determine the diversity of taproot skin and flesh colors in different cultivated types of radish (Raphanus sativus L.) - Qingbiao Wang; Yanping Wang; Xiangyu Wu; Wenyu Shi; Ningjie Chen; Yuanting Pang; Li Zhang (Theoretical and Applied Genetics, 2024)

Correction to: Changes in the characteristics of soil dissolved organic matter over time since inter-planting with white clover (Trifolium repens L.) in apple orchards on the Loess Plateau in China - Rongqin Zhang; Ming Li; Xiaodong Gao; Yumin Duan; Yaohui Cai; Huike Li; Xining Zhao; Yanping Wang (Plant and Soil, 2024)

Changes in the characteristics of soil dissolved organic matter over time since inter-planting with white clover (Trifolium repens L.) in apple orchards on the Loess Plateau in China - Rongqin Zhang; Ming Li; Xiaodong Gao; Yumin Duan; Yaohui Cai; Huike Li; Xining Zhao; Yanping Wang (Plant and Soil, 2024)

A NAC Transcription Factor RsSND1 Regulating Secondary Cell Wall Deposition Involves in Fleshy Taproot Formation in Radish (Raphanus sativus L.) - Yanping Wang; Qingbiao Wang; Xiangyu Wu; Yuanting Pang; Yu Guo; Zixiong Li; Li Zhang (Journal of Plant Growth Regulation, 2024)

Characterization of a membrane Fcγ receptor in largemouth bass (Micropterus saloumoides) and its response to bacterial challenge - Jingya Wang; Jing Wu; Yanping Ma; Le Hao; Wen Huang; Zhenxing Liu; Yugu Li (Fish Physiology and Biochemistry, 2024)

A within-subject voxel-wise constant-block partial least squares correlation method to explore MRI-based brain structure–function relationship - Xiaoyu Zhao; Kewei Chen; Hailing Wang; Yufei Gao; Xiangmin Ji; Yanping Li (Cognitive Neurodynamics, 2024)

D-Limonene Alleviates Oxidative Stress Injury of the Testis Induced by Arsenic in Rat - Yanping Yang; Yan Hong; Jing Han; Zhe Yang; Nanmin Huang; Binwei Xu; Qi Wang (Biological Trace Element Research, 2024)

Environmental fate and safety analysis of methoxyfenozide application to control litchi and longan pests - Yanping Liu; Xiaonan Wang; Siwei Wang (Environmental Science and Pollution Research, 2024)
Litchi and longan pests significantly affect crop yield and quality. Chemical prevention and control are very effective for production; therefore, it is crucial to study fate assessment and appropriate field efficacy before pesticide application on crops to appropriately assess the health and ecological risks linked with these agents. This study conducted Good Agricultural Practice (GAP) field trials and laboratory experiments to elucidate the dissipation, terminal residues, and efficacy of methoxyfenozide on litchi and longan in six locations throughout China. To detect methoxyfenozide residues on litchi and longan, a QuEChERS/UPLC-MS/MS-based method was designed. The initial methoxyfenozide levels in litchi and longan ranged from 2.21–2.86 to 0.83–0.95 mg kg −1 and indicated half-lives of 5.1–5.3 and 5.3–5.7 days, respectively. After 7 days of foliage treatment, the concentrations of terminal methoxyfenozide residue were 0.78–2.61 and 0.02–1.01 mg kg −1 , which were less than the established maximum residue limit for methoxyfenozide in litchi and longan. The chronic (acceptable daily intake = 0.0055–0.0331%) dietary intake risk analysis for methoxyfenozide in longan and litchi indicated acceptable concentrations of terminal residue for the general population. Methoxyfenozide in litchi and longan was readily degraded in first-order kinetics models, the degradation rate on longan was higher than that on litchi, and their dietary risks were negligible to consumers. Two hundred forty grams per liter of methoxyfenozide suspension concentrate (SC) represents a highly efficacious insecticidal dose to control litchi and longan pests and indicates a significant application potential as it is rapidly degraded and linked with reduced post-treatment residue levels.

Unlocking the potential of biochar: an iron-phosphorus-based composite modified adsorbent for adsorption of Pb(II) and Cd(II) in aqueous environments and response surface optimization of adsorption conditions - Xu Li; Yuan Chi; Feng Ma; Xiaoxin Wang; Rui Du; Zhipeng Wang; Xiaoyan Dang; Chaoyue Zhao; Yanping Zhang; Shumin He; Youzhao Wang; Tong Zhu (Environmental Science and Pollution Research, 2024)

Growth, survival and reproductive traits of chemical induced and tetraploid-derived triploid Hong Kong oysters (Crassostrea hongkongensis) - Yanping Qin; Weitao Wan; Jiangwei Li; Zhongyu Wang; Haitao Ma; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Single-cell and multi-omics analyses highlight cancer-associated fibroblasts-induced immune evasion and epithelial mesenchymal transition for smoking bladder cancer - Jiajin Wu; Fang Gao; Rui Meng; Huiqin Li; Zhenguang Mao; Yanping Xiao; Qiuyi Pu; Mulong Du; Zhengdong Zhang; Qiang Shao; Rui Zheng; Meilin Wang (Toxicology, 2024)

New insights into functional divergence and adaptive evolution of uncultured bacteria in anammox community by complete genome-centric analysis - Yi-Cheng Wang; Yanping Mao; Hui-Min Fu; Jin Wang; Xun Weng; Zi-Hao Liu; Xiao-Wei Xu; Peng Yan; Fang Fang; Jin-Song Guo; Yu Shen; You-Peng Chen (Science of The Total Environment, 2024)

Fabrication of a straw-based degradable mulch film with magnetically controlled-release glyphosate - Dongqing Cai; Mengjia Cui; Linying Wang; Jinghong Ye; Xianghai Kong; Ruobing Mu; He Xu; Yanping Zhu; Dongfang Wang (Chemical Engineering Journal, 2024)

The impact of microbial inoculants on large-scale composting of straw and manure under natural low-temperature conditions - Yanping Wang; Qi Yu; Chuang Zheng; Yanbo Wang; Heshu Chen; Shijia Dong; Xiaomei Hu (Bioresource Technology, 2024)

Genome-wide identification of nitrate transporter 1/peptide transporter family (NPF) induced by arbuscular mycorrhiza in the maize genome - Qiang Xu; Yanping Wang; Wen Sun; Yuanhao Li; Yunjian Xu; Beijiu Cheng; Xiaoyu Li (Physiology and Molecular Biology of Plants, 2024)

Changes of MRGs and ARGs in Acinetobacter sp. SL-1 used for treatment of Cr(VI)-contaminated wastewater with waste molasses as carbon source - Hui Wu; Rongxiao Wang; Yanping Ma; Tian C. Zhang; Yexing Yu; Jirong Lan; Yaguang Du (Science of The Total Environment, 2024)

Controlled atmosphere storage alleviates the browning of walnut (Juglans regia L.) fruit through enhancing GABA-mediated energy metabolism - Niu Ye; Dongli Zhang; Shan Liu; Yongqi Zhang; Yifan Wang; Yan Tang; Xiangna Yang; Jiahao Chai; Yanping Ma; Huiling Ma (Postharvest Biology and Technology, 2024)

V2O5·3H2O/N-doped graphite felt cathode efficiently produced H2O2 and ·OH in the electro-Fenton system for enhanced antibiotics degradation - Songyu Fan; Yanping Hou; Jiaxiang Liang; Tingting Zhu; Shiming Zhang; Ting Liang; Jinghui Pan; Yuxiang Shen; Zebin Yu; Hongxiang Zhu; Shuangfei Wang (Journal of Environmental Chemical Engineering, 2024)

Metabolomics reveals factors affecting the radical reaction of sulfides during thermal processing for meaty aroma - Zeyu Zhang; Huiyu Kuang; Bei Wang; Yanping Cao (Food Research International, 2024)

Aralianudaside A, an unusual skeleton triterpenoid saponin with anti-airway inflammatory activity from Aralia elata - Pengcheng Yin; Haishan Qian; Shaohua Li; Benqin Tang; Juan Wang; Shuai Chen; Guanghui Ni; Fawu Dong; Yanping Li; Feng Huang; Rongping Zhang; Hongping He; et al. (Natural Product Research, 2024)

Phenotypic traits of reciprocal tetraploid hybrids derived from tetraploid Crassostrea gigas and tetraploid Crassostrea angulata - Chao Yue; Yanping Qin; Weitao Wan; Gongpengyang Shi; Shengyong Li; Jiangwei Li; Zhongyu Wang; Haitao Ma; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Vascular plant communities and biocrusts act as controlling factors in mitigating soil erosion on the Great Wall in a semi-humid area of Northwestern China - Yanping Liu; Rongliang Jia; Wanfu Wang; Yuchen Wan; Yanhong Gao; Hongtao Zhan; Jing Ren; Zhang Chen; Fei Qiu; Jing Zhu (Science of The Total Environment, 2024)

Structures and ion transport mechanisms of plant high-affinity potassium transporters - Jiangqin Wang; Yanping Luo; Fan Ye; Zhong Jie Ding; Shao Jian Zheng; Shuai Qiao; Yong Wang; Jiangtao Guo; Wei Yang; Nannan Su (Molecular Plant, 2024)

Effects of wastewater treatment plant effluent on microbial risks of pathogens and their antibiotic resistance in the receiving river - Zijian Xiao; Yuanyuan Qin; Li Han; Yifan Liu; Ziyi Wang; Yanping Huang; Yujing Ma; Yina Zou (Environmental Pollution, 2024)

Evaluating the environmental impact of agri-food waste reduction: A bibliographic analysis and conceptual framework - Haorui Wang; Na Luo; Yanping Liu; Yu Gong (Environmental Impact Assessment Review, 2024)

High voltage, toughness and improved interfacial ion deposition through a dual-crosslinked and self-healable hydrogel electrolyte for green zinc-ion batteries - Yanping Yang; Luwei Shi; Yaqi Wu; Zhehua Chen; Xinyuan Zhu; Lijun Du; Youfu Wang (Chemical Engineering Journal, 2024)

Rational design and fabricate of protonated crosslinked chitosan adsorbent for boosting the removal of nitrite in water - Wenbin Chen; Yanping Feng; Xiaoming Wang; Chenchen Zhang; Suyao Liu; Yibing Song; Yiwen Fang (Chemical Engineering Journal, 2024)

Online LC-ESI-MS/MS comparative analysis of N/O-glycopatterns in human colostrum from different ethnic groups in Northwest China - Xiaoqin Wang; Jing Liu; Shukai Wang; Yutao Xie; Yipei Liu; Jiangbo Fan; Yanping Li; Yu Lu; Linjuan Huang; Zhongfu Wang (Carbohydrate Polymers, 2024)

Detection of two homologous major QTLs and development of diagnostic molecular markers for sucrose content in peanut - Zhihui Wang; Yue Zhang; Dongxin Huai; Yuning Chen; Xin Wang; Yanping Kang; Liying Yan; Huifang Jiang; Kede Liu; Yong Lei; Boshou Liao (Theoretical and Applied Genetics, 2024)

Non‐linear thresholds in the effect of area on three dimensions of diversity of herpetofauna in the West Indies - De Gao; Yanping Wang (Journal of Biogeography, 2024)
Aim The small‐island effect (SIE) describes an anomalous feature of the species–area relationship (SAR) on smaller compared to larger islands. However, previous studies on SIEs mainly focused on taxonomic diversity and overlooked phylogenetic and functional diversity. In this study, we explored SIEs in three dimensions of diversity. We expect to see the non‐linear thresholds in the effect of area on three dimensions of diversity as well as on community structures, because the dominant assembly processes vary across spatial scales. Location The West Indies. Taxon Herpetofauna. Methods We derived data on the presence/absence of 199 amphibian species on 163 islands and 614 reptile species on 748 islands in the West Indies. We built a species‐level phylogenetic tree and a species‐level functional tree to estimate six taxonomic, phylogenetic and functional diversity indices. Four community metrics on behalf of the phylogenetic and functional community structure of each island were calculated using a null modelling framework and was quantified using the standardized effect size (SES). We explored the non‐linear thresholds in the effect of area for each of the diversity indices and SES values of community metrics by comparing six piecewise regression models with a linear regression model and a null model. Results We found evidence of SIEs in four diversity indices representing all three dimensions of diversity. Besides, area thresholds were also found in the phylogenetic and functional community structure for both amphibians and reptiles. Random extinction, competitive exclusion and adaptive radiation are the dominant processes structuring reptile communities on small, intermediate and large islands respectively. Main Conclusions To conduct a comprehensive biodiversity conservation plan concerning taxonomic, phylogenetic and functional diversity, we suggest it is necessary to explore the SIEs in various diversity indices representing all three dimensions of diversity and apply the lowest threshold value to make management strategies.

Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Equal importance of humic acids and nitrate in driving anaerobic oxidation of methane in paddy soils - Yanan Bai; Yanping Wang; Lidong Shen; Bo Shang; Yang Ji; Bingjie Ren; Wangting Yang; Yuling Yang; Zhiguo Ma; Zhaozhong Feng (Science of The Total Environment, 2024)

SlCNR regulates postharvest water loss and wax accumulation in tomato fruit and directly represses the transcription of very-long-chain (VLC) alkane biosynthesis-related genes SlCER1-2 and SlCER6 - Di Chen; Tingyu Wang; Hua Huang; Qiaoli Zhang; Xue Chen; Zongyan Sun; Yanping Song; Yuetong Yi; Chengxia Liu; Donald Grierson; Jiankang Cao; Daqi Fu; et al. (Postharvest Biology and Technology, 2024)

Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Niacin alleviates extracellular matrix deposition in ethanol + CCl4-induced liver fibrosis through the HSP90/JAK1/STAT3 axis - Yanping Fan; Meilan Xue; Tianhu Shan; Yixian Bai; Huaqi Zhang; Man Liu; Peng Wang; Xi Liang; Hui Liang (Food Bioscience, 2024)

Identification of QTLs associated with very-long chain fatty acid (VLCFA) content via linkage mapping and BSA-seq in peanut - Xiaomeng Xue; Jianguo Li; Jie Wu; Meiling Hu; Nian Liu; Liying Yan; Yuning Chen; Xin Wang; Yanping Kang; Zhihui Wang; Huifang Jiang; Yong Lei; et al. (Theoretical and Applied Genetics, 2024)

Identification, characterisation and expression analysis of peanut sugar invertase genes reveal their vital roles in response to abiotic stress - Tingting Mao; Yaru Zhang; Wenwen Xue; Yu Jin; Hongfei Zhao; Yibo Wang; Shengnan Wang; Shengjie Zhuo; Feifei Gao; Yanping Su; Chunyan Yu; Xiaotong Guo; et al. (Plant Cell Reports, 2024)

Exogenous Epigallocatechin-3-Gallate Alleviates Pesticide Phytotoxicity and Reduces Pesticide Residues by Stimulating Antioxidant Defense and Detoxification Pathways in Melon - Yaxian Wu; Golam Jalal Ahammed; Zhengzhen Li; Yameng Wang; Qianying Wang; Mingya Fang; Yanping Zhang; Haihe Liu; Xin Li (Journal of Plant Growth Regulation, 2024)

Effects of saline water with different concentrations of calcium and magnesium ions on emitter clogging in drip irrigation integrated water–fertilizer system - Long Zhou; Chenchen Wei; Peiling Yang; Yunkai Li; Lili Zhangzhong; Yanping Su; Xin Wang; Xin He (Irrigation and Drainage, 2024)
The application of saline water in drip irrigation is severely constrained due to its high salt content, which causes precipitation and emitter clogging. Therefore, the effects of calcium and magnesium ions at 100, 150 and 200 mg/L in saline water coupled with humic acid nitrogen fertilizer on emitter clogging were studied. Compared with ground saline water, all treatments significantly increased the emitter clogging risk. In the calcium and magnesium ion treatment groups, clogging fouling increased by 23.94–58.35 and 14.55–51.21 mg/cm 2 , the discharge variation ratio (Dra) decreased by 22%–59% and 14%–49%, and the Christiansen coefficient of uniformity (CU) decreased by 29%–79% and 15%–74%, respectively. Higher ion concentrations caused more clogging. Saline water with a high calcium content caused more clogging. Under similar concentration conditions, the Dra and CU in high magnesium saline water were 9%–32% and 8%–51% higher, respectively. In addition, the increase in magnesium ion concentration changed the crystal form of carbonate, slowed the formation rate of precipitated dirt and significantly reduced the carbonate content by 19%–40%. Our results provide support for the popularization of saline water drip irrigation systems.

Modelling selenium behavior in aquatic systems: a review of status, challenges, and opportunities - Senlin Zhu; Yanping Wang; Andrew Hursthouse; Wenguang Luo; William A. Maher (Environmental Science and Pollution Research, 2024)

Molecularly imprinted polymer sheathed mesoporous silica tube as SPME fiber coating for determination of tobacco-specific nitrosamines in water - Yuemei Chen; Yang Yu; Shaohan Wang; Jiajia Han; Mengge Fan; Yanping Zhao; Junlang Qiu; Xin Yang; Fang Zhu; Gangfeng Ouyang (Science of The Total Environment, 2024)

Two-stage method recovery of metals from copper slag: Realize the resource utilization of all components - Lanbin Wang; Yangming Xu; Liang Tian; Yu Chen; Anju Yang; Guixiang Gan; Yanping Ma; Yaguang Du (Minerals Engineering, 2024)

Impact of cobalt recycling on China's electrification process: Assessing the potential reduction in cobalt demand from battery recycling - Lilong Chen; Xin Li; Yanping Luo; Wenli Tan; Qiaoying Ma; Minxi Wang; Jianbo Yang (Journal of Cleaner Production, 2024)

Fully space-confined donor-acceptor interaction for highly efficient thermally activated delayed fluorescence emitters - Wen-Cheng Chen; Ming-Hui Zheng; Yu-Lan Wu; Ru-Jia Wang; Jia-Ming Jin; Si-Wei Chen; Bo Liu; Jia-Xiong Chen; Yanping Huo; Shaomin Ji (Chemical Engineering Journal, 2024)

Tungsten and oxygen dual vacancies regulation of the S-scheme ZnSe/ZnWO4 heterojunction with local polarization electric field for efficient CO2 photocatalytic reduction - Ting Liang; Zebin Yu; Yuejing Bin; Shiming Zhang; Jingwen Wei; Yujia Liu; Tingting Zhu; Songyu Fan; Yuxiang Shen; Shuangfei Wang; Yanping Hou (Chemical Engineering Journal, 2024)

A multifunctional emitter with synergistical adjustment of rigidity and flexibility for high-performance data-recording and organic light-emitting devices with “hot exciton” channel - Guowei Chen; Wen-Cheng Chen; Yaozu Su; Ruicheng Wang; Jia-Ming Jin; Hui Liang; Bingxue Tan; Dehua Hu; Shaomin Ji; Hao-Li Zhang; Yanping Huo; Yuguang Ma (Chemical Engineering Journal, 2024)

Fibroblast growth factor-21 alleviates proteasome injury via activation of autophagy flux in Parkinson’s disease - Yufei Shen; Zhuoying Zhu; Yanping Wang; Shuxia Qian; Congying Xu; Baorong Zhang (Experimental Brain Research, 2024)
Parkinson’s disease (PD) is one of the most common and complex Neurodegeneration, with an inherited metabolic disorder. Fibroblast growth factor 21 (FGF21), an endocrine hormone that belongs to the fibroblast growth factor superfamily, plays an extensive role in metabolic regulation. However, our understandings of the specific function and mechanisms of FGF21 on PD are still quite limited. Here, we aimed to elucidate the actions and the underlying mechanisms of FGF21 on dopaminergic neurodegeneration using cellular models of parkinsonism. To investigate the effects of FGF21 on dopaminergic neurodegeneration in vitro, proteasome impairment models of PD were utilized. Human dopaminergic neuroblastoma SH-SY5Y cells were treated with the proteasome inhibitor lactacystin (5 μmol/L) for 12 h, then with 50 ng/ml FGF-21 with or without 5 mmol/L of 3-methyladenine.The cells were dissected to assess alterations in autophagy using immunofluorescence, immunoblotting and electron microscopy assays. Our data indicate that FGF21 prevents dopaminergic neuron loss and shows beneficial effects against proteasome impairment induced PD syndrome, indicating it might be a potent candidate for developing novel drugs to deal with PD.

Testing a biocontrol agent consortium for suppression of tomato bacterial wilt through rhizosphere microecological regulation - Xuefang Zheng; Jieping Wang; Meichun Chen; Yanping Chen; Zheng Chen; MingKuang Wang; Bo Liu (Applied Soil Ecology, 2024)

Miniaturized ascorbic acid assay platform based on point discharge atomic emission spectrometry coupling with gold filament enrichment - Yanping Wang; Yuemei Chen; Kejun Li; Jinrong Zhou; Xin Yuan; Mei Zhang; Ke Huang (Analytica Chimica Acta, 2024)

Spatial–Temporal Variations in Regional Sea Level Change in the South China Sea over the Altimeter Era - Lujie Xiong; Yanping Jiao; Fengwei Wang; Shijian Zhou (Journal of Marine Science and Engineering, 2023)
This study utilizes 27 years of sea level anomaly (SLA) data obtained from satellite altimetry to investigate spatial–temporal variations in the South China Sea (SCS). The local mean decomposition (LMD) method is applied to decompose the sea level data into three components: high-frequency, low-frequency, and trend components. By removing the influence of high-frequency components, multiple time series of regular sea level changes with significant physical significance are obtained. The results indicate that the average multi-year SLA is 50.16 mm, with a linear trend of 3.91 ± 0.12 mm/a. The wavelet analysis method was employed to examine the significant annual and 1.5-year periodic signals in the SCS SLA series. At the seasonal scale, the sea level rise in coastal areas during autumn and winter surpasses that of spring and summer. Moreover, there are generally opposing spatial distributions between spring and autumn, as well as between summer and winter. The linear trends in multi-year SLA for the four seasons are 3.70 ± 0.13 mm/a, 3.66 ± 0.16 mm/a, 3.49 ± 0.16 mm/a, and 3.74 ± 0.33 mm/a, respectively. The causes of SCS sea level change are examined in relation to phenomena such as monsoons, the Kuroshio Current, and El Niño–Southern Oscillation (ENSO). Based on the empirical orthogonal function (EOF) analysis of SCS SLA, the contributions of the first three modes of variance are determined to be 34.09%, 28.84%, and 8.40%, respectively. The temporal coefficients and spatial distribution characteristics of these modes confirm their associations with ENSO, monsoons, and the double-gyre structure of SCS sea surface temperature. For instance, ENSO impacts SCS sea level change through atmospheric circulation, predominantly affecting the region between 116° E and 120° E longitude, and 14° N and 20° N latitude.

Targeted degradation of naphthalene by peroxymonosulfate activation using molecularly imprinted biochar - Xueji You; Chaomeng Dai; Zeyu Wang; Yanping Duan; Jun Bo Zhang; Xiaoying Lai; Jiajun Hu; Jixiang Li; Maisideke Maimaitijiang; Yalei Zhang; Shuguang Liu; Rongbing Fu (Chemosphere, 2023)

Transfer of antibiotic resistance genes from soil to wheat: Role of host bacteria, impact on seed-derived bacteria, and affecting factors - Yanping Shen; Yibo Liu; Yutong Du; Xu Wang; Jiunian Guan; Xiaohui Jia; Fukai Xu; Ziwei Song; Hongjie Gao; Baiyu Zhang; Ping Guo (Science of The Total Environment, 2023)

Improving food security and farmland carbon sequestration in China through enhanced rock weathering: Field evidence and potential assessment in different humid regions - Fuxing Guo; Haowei Sun; Jing Yang; Linsen Zhang; Yan Mu; Yanping Wang; Fuyong Wu (Science of The Total Environment, 2023)

Engineering redirected NF-κB/OIP5 expression programs to enhance tumor responses to chemotherapy in bladder cancer - Binbin Zheng; Liman Niu; Haibo Xu; Yubin Yang; Yanping Chen; Chenguang Wang; Wei Chen; Weiren Huang (Science Bulletin, 2023)

Proportion of dead cells in phytoplankton modulates community structure - Peixuan Wang; Edward A. Laws; Xin Liu; Jixin Chen; Yanping Zhong; Chao Xu; Bangqin Huang (Progress in Oceanography, 2023)

Advancements in technology and innovation for sustainable agriculture: Understanding and mitigating greenhouse gas emissions from agricultural soils - Muhammad Qayyum; Yanping Zhang; Mansi Wang; Yuyuan Yu; Shijie Li; Wasim Ahmad; Saleh N. Maodaa; Shaban R.M. Sayed; Jiawei Gan (Journal of Environmental Management, 2023)

Gas-expanded pore MOF derived Sm/MnOx catalysts enable ultralow-temperature selective catalytic reduction of NOx - Shengchen Li; Dan Zhao; Shunli Shi; Fangyu Zhu; Yanping Yang; Shuhua Wang; Shunmin Ding; Chao Chen (Journal of Environmental Chemical Engineering, 2023)

A novel antibacterial mechanism of atmospheric cold plasma against Staphylococcus aureus through degradation of cellular staphyloxanthin - Yupan Zhu; Hangbo Xu; Dongjie Cui; Renwu Zhou; Yanping Wang; Aswathi Soni; Gale Brightwell; Jie Zhuang; Ruonan Ma; Zhen Jiao (Innovative Food Science & Emerging Technologies, 2023)

Walnut green husk extract enhances the effect of chlorine dioxide on kernel quality and antioxidant properties of fresh-eating walnuts during their shelf life - Dongli Zhang; Niu Ye; Mingrui Li; Guoli Dai; Yanping Ma; Yifan Wang; Chaobin Liu; Huiling Ma (Food Chemistry, 2023)

Carcass meat quality, volatile compound profile, and gene expression in Tan sheep under different feeding regimes - Xingang Zhao; Shuxian Zuo; Yanping Guo; Can Zhang; Yuejun Wang; Sijia Peng; Ming Liu; Bing Wang; Hao Zhang; Hailing Luo (Food Bioscience, 2023)

Multi-omics analysis of oxidative stress and apoptosis in hepatopancreas cells induced by Polyascus gregaria parasitizing the Eriocheir sinensis - Shiwei Zhao; Qingbiao Hu; Hongbo Jiang; Yingying Zhao; Yanping Wang; Chengcheng Feng; Xiaodong Li (Fish & Shellfish Immunology, 2023)

Precise diagnosis of breast phyllodes tumors using Raman spectroscopy: Biochemical fingerprint, tumor metabolism and possible mechanism - Yifan Wu; Yaohui Wang; Chang He; Yan Wang; Jiayi Ma; Yanping Lin; Liheng Zhou; Shuguang Xu; Yumei Ye; Wenjin Yin; Jian Ye; Jingsong Lu (Analytica Chimica Acta, 2023)

Co-recovery of Mn and Fe from pyrolusite and copper slag with hydrometallurgy process: Kinetics and leaching mechanisms - Lanbin Wang; Yu Chen; Yangming Xu; Yanping Ma; Yaguang Du (Environmental Science and Pollution Research, 2023)

Drought characteristics and dominant factors across China: Insights from high-resolution daily SPEI dataset between 1979 and 2018 - Lingling Wan; Virgílio A. Bento; Yanping Qu; Jianxiu Qiu; Hongquan Song; RongRong Zhang; Xiaoping Wu; Feng Xu; Jinkuo Lu; Qianfeng Wang (Science of The Total Environment, 2023)

Spatio-temporal evolution and teleconnection factor analysis of groundwater drought based on the GRACE mascon model in the Yellow River Basin - Fei Wang; Hexin Lai; Yanbin Li; Kai Feng; Qingqing Tian; Wenxian Guo; Yanping Qu; Haibo Yang (Journal of Hydrology, 2023)

T4PPVB-COP composite-driven innovative electrochemiluminescence aptasensor for ultra-sensitive detection of chlorpyrifos - Yanping Li; Qiong Hu; Jihui Zhang; Hong Zhou; Na Wang; Yishan Fang; Bo Cui (Food Chemistry, 2023)

Characterization of potent odorants causing meaty odor reduction in thermal process flavorings with beef-like odor by the sensomics approach - Zeyu Zhang; Bei Wang; Yanping Cao (Food Chemistry, 2023)

Study on thermal properties of bio-char prepared by photo-thermal pyrolysis - Dexin Huang; Yankui Wang; Gongxiang Song; Song Hu; Hanjian Li; Yanping Zhang; Yi Wang; Sheng Su; Saad A. El-Sayed; Jun Xiang (Biomass and Bioenergy, 2023)

Nanopore Structure and Multifractal Characteristics of Continental Shale Oil Reservoir: A Case Study from Ziliujing Shales in the Sichuan Basin - Youzhi Wang; Wei Li; Xiandong Wang; Zhiguo Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Lijuan Cheng; Xiaofei Fu (Journal of Marine Science and Engineering, 2023)
Thermal maturity of the shales from the Ziliujing Formation of the Jurassic age in the Sichuan Basin is in the hydrocarbon generation window, which makes it a candidate for shale oil and gas development. The meso- and macropore characteristics and heterogeneity of shales are important factors affecting the occurrence and development of oil and gas. However, the meso- and macropores of the Ziliujing shales have not been systematically studied. Thus, the mineral compositions and total organic carbon (TOC) of samples from this formation, as well as its pore structure, are analyzed by low-temperature N2 adsorption technique. Moreover, the heterogeneity of the pores was determined by multifractal analysis. The results show that the Ziliujing shales can be classified into three types according to the distributions of mineral compositions of carbonate and mixed and argillaceous shales. Results revealed that the smallest meso- and macropore volume (PV), the smallest specific surface area (SSA), and the largest average pore diameter (APD) occur in the carbonate shales. However, the largest PV and SSA and the smallest APD are observed in the argillaceous shales. The porosity of carbonate shales is mainly concentrated between 5 nm and 30 nm. Compared with carbonate shales, the porosity with pore sizes less than 30 nm of mixed and argillaceous shales shows a rapid increase. Furthermore, inorganic minerals are the main factors affecting the pore distributions, while TOC shows a weak effect. Herein, clay minerals significantly increase the mesopore volume and the pore number with a size of less than 30 nm. The Dq-q curves reveal that the meso- and macropore distributions of Ziliujing shales show multifractal behavior, but the multifractal characteristics of pores of various shales are distinctly different. The information dimension D1, the Hurst exponent H, and the width of the right side D0–D10 are key indicators to distinguish the local variations within the pore structure of different types of shales. The carbonate shales have the largest multifractal spectra width and the smallest D1 and H, while the opposite trend is found for the argillaceous shales. Clay minerals reduce the heterogeneity of the meso- and macropore distributions and increase the pore connectivity. Nevertheless, the carbonate minerals exhibit a reverse trend. Finally, it was found that TOC does not impact pore complexity as much. Collectively, this study supports our understanding of the occurrence of shale oil within various reservoir facies, thereby providing a guideline for future explorations in the Ziliujing Formation of the Jurassic age in the Sichuan Basin.

Resource utilization of rice straw to prepare biochar as peroxymonosulfate activator for naphthalene removal: Performances, mechanisms, environmental impact and applicability in groundwater - Jun Bo Zhang; Chaomeng Dai; Zeyu Wang; Xueji You; Yanping Duan; Xiaoying Lai; Rongbing Fu; Yalei Zhang; Maisideke Maimaitijiang; Kah Hon Leong; Yaojen Tu; Zhi Li (Water Research, 2023)

Stream restoration can reduce nitrate levels in agricultural landscapes - Xiangqian Zhou; Seifeddine Jomaa; Xiaoqiang Yang; Ralf Merz; Yanping Wang; Michael Rode (Science of The Total Environment, 2023)

Divergent temporal changes of heavy metals in the soil induced by natural versus anthropogenic forces: A case study in the Yangtze River delta area, China - Cheng Wang; Jianhua Wang; Cong Zhong; Yanping Zhao (Science of The Total Environment, 2023)

Insight into the plant-associated bacterial interactions: Role for plant arsenic extraction and carbon fixation - Yibo Liu; Baiyu Zhang; Ye Yao; Bo Wang; Yiqi Cao; Yanping Shen; Xiaohui Jia; Fukai Xu; Ziwei Song; Chengpeng Zhao; HongJie Gao; Ping Guo (Science of The Total Environment, 2023)

Extraction of rubidium and cesium from oilfield brine by the two-step adsorption–flotation method - Dezhen Fang; Miao Lu; Yanping Wang; Liang Ma; Kexin Li; Haining Liu; Huifang Zhang; Guosheng Shi; Zhijian Wu; Xiushen Ye (Minerals Engineering, 2023)

Enhancing alkali-activated materials with low quality fly ash: A novel mixing approach for robust construction materials - Reza Mirmoghtadaei; Lin Shen; Yanping Li; Mo Li; Baomin Wang (Journal of Cleaner Production, 2023)

Factors influencing on the formation of dimethyl disulfide and dimethyl trisulfide in model systems - Zeyu Zhang; Bei Wang; Yanping Cao (Food Research International, 2023)

ZIF-8-derived hollow carbon polyhedra with highly accessible single Mn-N6 sites as peroxymonosulfate activators for efficient sulfamethoxazole degradation - Yue Zhao; Rui Gao; He Wang; Yanping Sun; Xiaohui Zhan; Lei Chen; Junyan Liu; Huixiang Shi (Chemical Engineering Journal, 2023)

Causal relationships between chronotype and risk of multiple cancers by using longitudinal data and Mendelian randomization analysis - Shanshan Tian; Longtao Huangfu; Sizhi Ai; Junwei Zheng; Le Shi; Wei Yan; Ximei Zhu; Qianwen Wang; Jiahui Deng; Yanping Bao; Suhua Chang; Lin Lu (Science China Life Sciences, 2023)

The rhizosphere soil properties and bacteria community of poplar are affected by magnetic field under salt condition - Han Wenhao; Wang Nianzhao; Hu Jihuai; Yan Kun; Ma Fengyun; Tian Huimei; Wang Yanping (Rhizosphere, 2023)

Detoxification and resource utilization of soda ash chromite ore processing residue by copper slag - Lanbin Wang; Yangming Xu; Yanping Ma; Yu Chen; Anju Yang; Guixiang Gan; Yaguang Du; Yan Sun (Process Safety and Environmental Protection, 2023)

Fractionations of heavy metals and their correlations with magnetic susceptibility in soil from a typical alluvial island in the lower yangtze river, China - Cheng Wang; Rong Ma; Jianhua Wang; Cong Zhong; Yanping Zhao; Patrick Browne (Journal of Cleaner Production, 2023)

Corn-straw-derived, pyridine-nitrogen-rich NCQDs modified Cu0.05Zn2.95In2S6 promoted directional electrons transfer and boosted adsorption and activation of CO2 for efficient photocatalytic reduction of CO2 to CO - Jinhang Yang; Yanping Hou; Jiangli Sun; Jingwen Wei; Shiming Zhang; Jiaxiang Liang; Zebin Yu; Hongxiang Zhu; Shuangfei Wang (Chemical Engineering Journal, 2023)

Microbial metabolism and humic acid formation in response to enhanced copper and zinc passivation during composting of wine grape pomace and pig manure - Yingchao Zhang; Yang Xu; Xinlong Yu; Jinkang Li; Guang Chen; Shuaijie Wang; Yanping Xu; Rui Xu; Baohai Zhang; Hongqiong Zhang (Bioresource Technology, 2023)

Nitrogen addition regulates the growth of Pinus tabuliformis by changing distribution patterns of endogenous hormones in different organs - Yuhang Peng; Keli Chen; Guoliang Wang; Jiawei Tan; Furong Wei; Yanping Ma (New Forests, 2023)

Comparative Analysis of the Expression of Resistance-Related Genes Respond to the Diversity Foliar Pathogens of Pseudostellaria heterophylla - Xiao-Ai Wang; Yanping Gao; Weike Jiang; Lu Wang; Hui Wang; Xiaohong Ou; Yang Yang; Honglin Wu; Lanping Guo; Tao Zhou; Qing-Song Yuan (Current Microbiology, 2023)

Detection of depression marker ASS1 in urine by gold nanoparticles based dual epitope-peptides imprinted sensor - Hong Wei; Zixia Wang; Yanping Wang; Jing Ma; Yan Chen; Min Guo; Yuanyuan Li; Yongling Du; Fangdi Hu (Analytica Chimica Acta, 2023)

An evolving view on food viscosity regulating gastric emptying - Yangyi Jin; Peter J. Wilde; Yingying Hou; Yanping Wang; Jianzhong Han; Weilin Liu (Critical Reviews in Food Science and Nutrition, 2023)

Simulation and experimental research on hydrodynamic performance of fully attached submarine in the surface and near the surface modes - Minmin Zheng; Yadong Liu; Youjiang Wang; Yanping He (Ocean Engineering, 2023)

In vitro and in vivo synergistic effects of hydroxychloroquine and itraconazole on Cryptococcus neoformans - Xue Wang; Xuemei Long; Songgan Jia; Jiali Zhu; Zhan Zhou; Sarah Ahmed; Yinhui Jiang; Yanping Jiang (Folia Microbiologica, 2023)

Crop productivity and soil inorganic carbon change mediated by enhanced rock weathering in farmland: A comparative field analysis of multi-agroclimatic regions in central China - Fuxing Guo; Yanping Wang; Haoyong Zhu; Chuangye Zhang; Haowei Sun; Zhuling Fang; Jing Yang; Linsen Zhang; Yan Mu; Yu Bon Man; Fuyong Wu (Agricultural Systems, 2023)

A review of metal contamination in seagrasses with an emphasis on metal kinetics and detoxification - Yanping Li; Fengyuan Chen; Ruojing Zhou; Xinqing Zheng; Ke Pan; Guanglong Qiu; Zhongjie Wu; Shiquan Chen; Daoru Wang (Journal of Hazardous Materials, 2023)

A callus-derived regeneration and Agrobacterium-mediated gene transformation developed for bilberry, Vaccinium myrtillus - Yanping Song; Wenbo Luo; Ying Wu; Xiaojie Li; Nick W. Albert; Yinhai Zhang; Xiangtao Chen; Kui Lin-Wang; Cecilia H. Deng; Zhubing Hu; Bingsong Zheng; Xiaofei Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

High expression of HOXC6 predicts a poor prognosis and induces proliferation and inflammation in multiple myeloma cells - Zhihua Li; Yaru Wang; Xiaoxu Hou; Luyao Guo; Yanling Li; Yanping Ma; Yanping Ma (Genes & Genomics, 2023)

The integration of the small‐island effect and nestedness pattern - Yanping Wang; Chuanwu Chen; Virginie Millien (Journal of Biogeography, 2023)
Aim The small‐island effect (SIE) and nestedness are two important patterns in the fields of island biogeography and community ecology. However, to date, no study has tried to integrate the SIE and nestedness pattern. Therefore, the aim of this study was to integrate these two biogeographical patterns by proposing a new integrative hypothesis. The integrative hypothesis posits that the degree of nestedness of the large island matrix will be larger than that of the small island matrix split by the threshold of the SIE. Location Global. Taxon Plants, invertebrates and vertebrates. Methods We compiled 219 global datasets with both the presence‐absence matrices and the variables of area and species richness. We also collected six island characteristics influencing the SIE and nestedness patterns, that is island type, taxonomic group, area range, the number of islands, species range and matrix fill. We applied breakpoint regressions to detect SIEs and used the metric NODF (Nestedness metric based on Overlap and Decreasing Fill) to quantify nestedness. We then employed logistic regressions and an information‐theoretic approach to determine which combination of island characteristics was important in determining whether the integrative hypothesis was supported. Results Among the 92 datasets in which SIEs were unambiguously detected, nestedness analyses showed that in 64 cases (69.6%) the values of NODFc (nestedness among sites) for the large island matrices were larger than those of the small island matrices. Matrix fill and area range were substantially important in determining whether the integrative hypothesis was supported. By contrast, island type, taxonomic group, the number of islands and species range received considerably less support. Main Conclusions Our study was the first to integrate the SIE and nestedness pattern. Overall, we found prevalent support for our integrative hypothesis. The integration of the SIE and nestedness provides new and interesting insights into these two biogeographical patterns.

Enhanced trichloroethylene biodegradation: The mechanism and influencing factors of combining microorganism and carbon‑iron materials - Jing Ma; Manxi Xie; Nan Zhao; Yue Wang; Qingqi Lin; Yanping Zhu; Yuanqing Chao; Zhuobiao Ni; Rongliang Qiu (Science of The Total Environment, 2023)

Microwave-carbon fiber cloth co-ignited catalytic degradation of waste plastic into high-yield hydrogen and carbon nanotubes - Bowen Zhang; Hui Wang; Yiyun Yang; Yanping Zhou; Bing Zhang; Kama Huang (Journal of Environmental Chemical Engineering, 2023)

Electron-buffer-mediated dual Z-scheme ZnSe/Ag2Se/AgBr heterojunction for efficient CO2 photocatalytic reduction - Ting Liang; Jingwen Wei; Shiming Zhang; Jinhang Yang; Jiangli Sun; Zuji Li; Zhihong Li; Zebin Yu; Shuangfei Wang; Yanping Hou (Journal of Environmental Chemical Engineering, 2023)

Effect of oligosaccharides as lyoprotectants on the stability of curcumin-loaded nanoliposomes during lyophilization - Hanyun Jiang; Yanping Wang; Xiankang Xu; Leiyu Deng; Lifang Feng; Jianzhong Han; Weilin Liu (Food Chemistry, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Isolation and identification of the endophytic fungus J2-3 and its disease-preventive and growth-promoting effects on cucumber - Jiantao Fu; Yuejie Wu; Xiangnan Yan; Lanying Wang; Shujing Zhang; Yanping Luo (Brazilian Journal of Microbiology, 2023)

Changes in overwintering ground of small yellow croaker ( Larimichthys polyactis ) based on MaxEnt and GARP models: A case study of the southern Yellow Sea stock - Guodong Li; Ying Xiong; Xiaming Zhong; Dade Song; Zhongjie Kang; Dongjia Li; Jianhua Tang; Yanping Wang; Lei Wu (Journal of Fish Biology, 2023)
Small yellow croaker ( Larimichthys polyactis ), a commercially essential fish commonly caught in China and South Korea, is now facing a severe decline in resources. The recruitment and surplus of L. polyactis depend selecting a suitable marine environment for overwintering. However, the international overwintering migration habit of L. polyactis limits the investigation of its overwintering environment preferences and suitable grounds. In this study, based on the distribution data of L. polyactis in the southern Yellow Sea in winter from 2010 to 2019 and ocean remote sensing data such as sea bottom temperature (SBT), sea bottom salinity, chlorophyll‐a concentration and water depth (Depth), we used the maximum entropy (MaxEnt) and the genetic algorithm for rule‐set production (GARP) models to investigate the overwintering grounds of the southern Yellow Sea stock (SYS). The jackknife test was used to assess the importance of various environmental factors. For modelling the overwintering ground distribution of SYS, the area under the curve values of both models ​were higher than 0.9. The overwintering ground was at 32°10′ N–33°48′ N, 122°30′ E–125°00′ E. The direction of its distribution was consistent with the Yellow Sea Warm Current in the southern Yellow Sea during the winter. Compared with the suitable overwintering area during 2010–2014, the highly appropriate overwintering area for SYS to overwinter decreased significantly during 2015–2019, showing a trend of moving to the east and north, related to the increase in fishing pressure and strengthening of the Yellow Sea Warm Current in recent years. Depth was the most significant factor for SYS overwintering, followed by SBT. The overwintering ground was at a depth of 40–65 m during the two periods. Additionally, the suitability of overwintering grounds in the coastal waters of south‐western South Korea has gradually increased. This study provides a scientific basis for formulating effective strategies to manage L. polyactis resources under the China–South Korea Fisheries Agreement.

Microscopic Analysis of Natural Fracture Properties in Organic-Rich Continental Shale Oil Reservoirs: A Case Study from the Lower Jurassic in the Sichuan Basin, China - Xuefeng Bai; Saipeng Huang; Xiandong Wang; Zhiguo Wang; Youzhi Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Xiaofei Fu; Lijuan Cheng; Likai Cui; et al. (Journal of Marine Science and Engineering, 2023)
Natural fractures are of paramount importance in storing carbon in shale oil reservoirs, where ultra-low porosity and permeability necessitate their essentiality for enhanced oil recovery. Therefore, comprehensively clarifying the characteristics of natural fractures in shale oil reservoirs is imperative. This paper focuses on investigating the microscopic features of natural fractures in organic-rich continental shale oil reservoirs that are commonly found in the Lower Jurassic strata of the Sichuan Basin, employing them as a representative example. Multiple methods were utilized, including mechanical testing, Kaiser testing, multi-scale CT scanning (at 2 mm, 25 mm, and 100 mm scales), and a numerical simulation of fluid seepage in fracture models. The results revealed that the in situ stress of the target seam displays the characteristic of σH > σv > σh, with σv and σh being particularly similar. The relatively high lateral stress coefficient (ranging from 1.020 to 1.037) indicates that the horizontal stresses are higher than the average level. Although the 2 mm CT scan provides a more detailed view of fractures and connected pores, it primarily exhibited more pore information due to the high resolution, which may not fully unveil additional information about the fractures. Thus, the 25 mm shale core is a better option for studying natural fractures. The tortuosity of the different fractures indicated that the morphology of larger fractures is more likely to remain stable, while small-scale fractures tend to exhibit diverse shapes. The simulations demonstrated that the stress sensitivity of fracture permeability is approximately comparable across different fracture scales. Therefore, our research can enhance the understanding of the properties of natural fractures, facilitate predicting favorable areas for shale oil exploration, and aid in evaluating the carbon storage potential of shale oil reservoirs.

An overview of the direct and indirect effects of acid rain on plants: Relationships among acid rain, soil, microorganisms, and plants - Yan Zhang; Jiahong Li; Junyan Tan; Wenbin Li; Bhupinder Pal Singh; Xunan Yang; Nanthi Bolan; Xin Chen; Song Xu; Yanping Bao; Daofei Lv; Anan Peng; et al. (Science of The Total Environment, 2023)

Oocyte Arrested at Metaphase II Stage were Derived from Human Pluripotent Stem Cells in vitro - Xiaoli Yu; Ning Wang; Xiang Wang; Hehe Ren; Yanping Zhang; Yingxin Zhang; Yikai Qiu; Hongyan Wang; Guoping Wang; Xiuying Pei; Ping Chen; Yahui Ren; et al. (Stem Cell Reviews and Reports, 2023)
Initiation of meiosis is the most difficult aspect of inducing competent oocytes differentiation from human stem cells in vitro . Human induced pluripotent stem cells (hiPSCs) and embryonic stem cells (hESCs) were cultured with follicle fluid, cytokines and small molecule to induced oocyte-like cells (OLCs) formation through a three-step induction procedure. Expression of surface markers and differentiation potential of germ cells were analyzed in vitro by flow cytometry, gene expression, immunocytochemistry, western blotting and RNA Sequencing. To induce the differentiation of hiPSCs into OLCs, cells were firstly cultured with a primordial germ cell medium for 10 days. The cells exhibited similar morphological features to primordial germ cells (PGCs), high expressing of germ cell markers and primordial follicle development associated genes. The induced PGCs were then cultured with the primordial follicle-like cell medium for 5 days to form the induced follicle-like structures (iFLs), which retained both primordial oocytes-like cells and granulosa-like cells. In the third step, the detached iFLs were harvested and transferred to the OLC-medium for additional 10 days. The cultured cells developed cumulus-oocyte-complexes (COCs) structures and OLCs with different sizes (50–150 μm diameter) and a zona pellucida. The in vitro matured OLCs had polar bodies and were arrested at metaphase II (MII) stage. Some OLCs were self-activated and spontaneously developed into multiple-cell structures similar to preimplantation embryos, indicating that OLCs were parthenogenetically activated though in vitro fertilization potential of OLCs are yet to be proved. in vitro maturation of OLCs derived from hiPSCs provides a new means to study human germ cell formation and oogenesis. Graphical Abstract

Fumigant toxicity and behavioral alterations of six plant essential oils against the red fire ant (Solenopsis invicta Buren) - Jiantao Fu; Zewen Ma; Lanying Wang; Yunfei Zhang; Yanping Luo (Environmental Science and Pollution Research, 2023)

Range restriction, climate variability and human‐related risks imperil lizards world‐wide - Chuanwu Chen; Marcel Holyoak; Junfeng Xu; Gabriel Henrique de Oliveira Caetano; Yanping Wang (Global Ecology and Biogeography, 2023)
Aims Identifying major reasons for species imperilment is a necessary step for conservation, but the degree to which we can generalize is hard for species‐rich yet less‐studied taxa, such as lizards. Here, we aim to bridge the gap by providing comprehensive analyses of the correlates and processes of species extinction and threats for global lizards. Location Global. Time period Current. Major taxa studied Lizards. Methods We compiled a dataset comprising extinction risk status, six intrinsic traits and seven extrinsic factors for 5256 lizard species. We carried out binomial distribution tests for 43 families and seven realms to check the non‐randomness in species extinction risk and used phylogenetic linear regressions to identify the key factors that relate to the extinction proneness of lizards and species subgroups. Based on the International Union for Conservation of Nature (IUCN) threat assessment, we identified major threats for global lizards and for major families and regions. Results We found strong evidence of taxonomic and geographical non‐randomness in the extinction risk of lizards. Geographical range size, human footprint and density, insular endemism, temperature and precipitation seasonality, and body size were key predictors of extinction risk, and the first three factors were also important across families and realms. Moreover, newly described species were more likely to have a restricted range size and a higher extinction risk. Globally, the most detrimental threat was habitat destruction, while overexploitation, species invasion and climate change varied widely in importance among species groups. Main conclusions Overall, we highlight the detrimental influences of range restriction, climate variability and anthropogenic threats to species persistence. We suggest that lizards are potentially at high risk of extinction owing to widespread human disturbance and that species with extinction‐prone traits require conservation prioritization. Moreover, lizards of different families and regions require different management strategies because of variation in extinction‐risk correlates and threats.

The effect of pH/PAC on the coagulation of anionic surfactant wastewater generated in the cosmetic production - Lanhe Zhang; Xiaolin Liu; Mingshuang Zhang; Tiezheng Wang; Hong Tang; Yanping Jia (Journal of Environmental Chemical Engineering, 2023)

Exploration of the metabolic flexibility of glycogen accumulating organisms through metatranscriptome analysis and metabolic characterization - Bin Zhao; Yanping Yang; Chen Zhao; Chunchun Zhang; Zhaohui Zhang; Liang Wang; Shang Wang; Jingfeng Wang (Journal of Environmental Sciences, 2023)

First kinetics verification of the useful H2Ogas inhibition on the thermal regeneration of spent activated carbon in flue gas desulfurization - Hanyu Deng; Wenzhen Cai; Lanhe Zhang; Yanping Jia; Xiaoqiang Wang; Qing Zong; Guishi Cheng; Xiaoying Hu; Changqing Dong; Ying Zhao (Fuel, 2023)

Specific protection mechanism of oligosaccharides on liposomes during freeze-drying - Leiyu Deng; Yanping Wang; Hanyun Jiang; Xiankang Xu; Jianzhong Han; Weilin Liu (Food Research International, 2023)

A general way to manipulate electrical conductivity of graphene - Liqing Chen; Nian Li; Xinling Yu; Shudong Zhang; Cui Liu; Yanping Song; Zhao Li; Shuai Han; Wenbo Wang; Pengzhan Yang; Na Hong; Sarmad Ali; et al. (Chemical Engineering Journal, 2023)

Calycosin-7-glucoside promotes mitochondria-mediated apoptosis in hepatocellular carcinoma by targeting thioredoxin 1 to regulate oxidative stress - Xiaodong Wei; Yanping Zeng; Fancheng Meng; Tingpu Wang; Hebin Wang; Yijun Yuan; Dongmei Li; Yue Zhao (Chemico-Biological Interactions, 2023)

Local thermal comfort chart for non-uniform building environments: Comparison with vehicle environments and its application - Xiaowen Su; Ongun Berk Kazanci; Zhaojun Wang; Bjarne W. Olesen; Liangliang Sun; Yanping Yuan (Building and Environment, 2023)

Computer-aided engineering of CRISPR-Cas proteins for enhanced human genome editing - Yangcan Chen; Yanping Hu; Shengqiu Luo; Xinge Wang; Bangwei Mao; Yi Chen; Jing Xu; Zhikun Li; Qi Zhou; Wei Li (Science China Life Sciences, 2023)

Osteopontin promotes microglia activation and aggravates neuromyelitis optica via interferon-gamma/nuclear factor kappa B/interleukin-12 signaling - Fengyi Chen; Yanping Wang (Molecular & Cellular Toxicology, 2023)

Inhibition of aged microplastics and leachates on methane production from anaerobic digestion of sludge and identification of key components - Xinying Wang; Yan Zhang; Yanping Zhao; Lei Zhang; Xuxiang Zhang (Journal of Hazardous Materials, 2023)

Production regions discrimination of Huangguanyin oolong tea by using the content of chemical components and rare earth elements - Shuxian Shao; Mengting Xu; Xiansheng Liao; Qin Luo; Yanping Lin; Pengjie Wang; Deyin Fang; Yibiao Huang; Shan Jin; Naixing Ye (Food Research International, 2023)

A negative-response strain sensor towards wearable microclimate changes for body area sensing networks - Jing Liu; Junze Zhang; Zeyu Zhao; Yanping Liu; Wai Cheong Tam; Zhaozhu Zheng; Xiaoqin Wang; Yuling Li; Zekun Liu; Yi Li; Gang Li (Chemical Engineering Journal, 2023)

Melatonin Antagonizes Cytokinin Responses to Stimulate Root Growth in Arabidopsis - Yanping Wang; Jinzhu Li; Li Yang; Zhulong Chan (Journal of Plant Growth Regulation, 2023)

Characteristics of volatile organic compounds and secondary organic aerosol pollution in different functional areas of petrochemical industrial cities in Northwest China - Yanping Yang; Wenkai Guo; Jian Sun; Qiang Chen; Xianhong Meng; Lina Wang; Huijie Tao; Lili Yang (Science of The Total Environment, 2023)

Removal of chlorine, microparticles and water from high-viscosity liquids by a sand filter coupling hydrocyclone - Aosong Wei; Jianping Li; Minjie Shan; Wenjie Lv; Jianqi Chen; Pengbo Fu; Yanping Liu; Weichun Xu; Li Dai; Hualin Wang (Process Safety and Environmental Protection, 2023)

Effective removal of phosphorus from high phosphorus steel slag using carbonized rice husk - Zhongliang Wang; Yanping Bao; Dazhi Wang; Min Wang (Journal of Environmental Sciences, 2023)

A magnetic adsorbent with metal-organic framework based on ammonium phosphomolybdenum heteropoly tungstate (AWP): Selective adsorption of Rb+ and Cs+ from aqueous resources and stripping with ammonium salts - Yanping Wang; Kexin Li; Liang Ma; Dezhen Fang; Miao Lu; Xiushen Ye; Haining Liu; Huifang Zhang; Xiaoli Tan; Zhijian Wu (Hydrometallurgy, 2023)

A mathematical model for phosphorus interactions and transport at the sediment-water interface in a large shallow lake - Yanping Wang; Zhaoliang Peng; Gang Liu; Hui Zhang; Xiangqian Zhou; Weiping Hu (Ecological Modelling, 2023)

Preparation of recyclable and deformable POM microfiber for oil–water separation with nature-inspired top–bottom strategy - Wenbin Jin; Jingjing Wang; Hai Wan; Yuan Liang; Shuohan Huang; Yuwei Chen; Peng Wei; Qun Shao; Yanping Wang; Yong He; Yumin Xia (Chemical Engineering Journal, 2023)

Underwater superoleophobic GO-PEI-SiO2-Hal quaternary sphere-rod nacre-inspired mesh by LBL self-assembly for high-efficiency oil-water separation - Xiaohua Tian; Sujun Tian; Lulu Wang; Yanping Yang; Ruilong Zhang; Jiangdong Dai; Jianming Pan (Applied Clay Science, 2023)

One-step self-assembly of multilayer graphene oxide via streamlined click reactions for sensitive colorimetric assays - Yanfeng Gao; Yanping Wang; Xinli Liu; Zhenxing Zhu; Zhun Li; Zhibin Zhang; Yi Yin; William Chi Shing Cho; Yujun Song; Yuzhen Wang (Analytica Chimica Acta, 2023)

Climate and management impacts on the spatiotemporal dynamics of water-carbon fluxes in the North China Plain - Xingwang Wang; Huimin Lei; Jiadi Li; Yanping Qu; Dongdong Kong; Zailin Huo (Agriculture, Ecosystems & Environment, 2023)

MnOx@N-doped carbon nanosheets derived from Mn-MOFs and g-C3N4 for peroxymonosulfate activation: Electron-rich Mn center induced by N doping - Yue Zhao; Xiaohui Zhan; Yanping Sun; He Wang; Lei Chen; Junyan Liu; Huixiang Shi (Chemosphere, 2023)

PlZFP mediates the combinatorial interactions of abscisic acid with gibberellin and ethylene during flower senescence in cut herbaceous peony - Xiaotong Ji; Yanping Yuan; Zhangzhen Bai; Meiling Wang; Lixin Niu; Daoyang Sun (Postharvest Biology and Technology, 2023)

Characteristics and origin of Lower Triassic Feixianguan Formation dolostones on the west side of Kaijiang–Liangping Trough, northeastern Sichuan Basin, China - Ling Zhou; Guangwei Wang; Ya Zhang; Yanping Qiao; Fang Hao; Rui Xu; Li Quan; Ping Wang (Marine and Petroleum Geology, 2023)

Advances in air pollution control for key industries in China during the 13th five-year plan - Xuecheng Wu; Yanping Yang; Yue Gong; Zhiwen Deng; Ying Wang; Weihong Wu; Chenghang Zheng; Yongxin Zhang (Journal of Environmental Sciences, 2023)

Advances in air pollution control for vessels in China - Yanping Yang; Yue Gong; Ying Wang; Xuecheng Wu; Zhiying Zhou; Weiguo Weng; Yongxin Zhang (Journal of Environmental Sciences, 2023)

Production of high affinity monoclonal antibody and development of indirect competitive chemiluminescence enzyme immunoassay for gentamicin residue in animal tissues - Peng Dai; Yan Zhang; Yanping Hong; Jianhua Xiong; Huaying Du; Luying Duan; Dan Wang; Yubo Wang; Weijie Deng; Bruce D. Hammock; Wuying Yang (Food Chemistry, 2023)

Photocatalytic and oxidation mechanisms of Fe–Ag@AgCl: Effect on co-existing arsenic (III) and Escherichia coli - Yanping Cui; Qian Ye; Haili Wang; Xuewen Duo; Liang Peng; Wei Dong; Xiaoxiao Cui; Yue Lu; Yajie Li (Environmental Research, 2023)

Large-flake graphene-modified biochar for the removal of bisphenol S from water: rapid oxygen escape mechanism for synthesis and improved adsorption performance - Yurong Gao; Zheng Fang; Wenhui Lin; Hanbo Chen; Amit Bhatnagar; Jianhong Li; Yanhai Xie; Yanping Bao; Junfeng Chen; Hongting Zhao; Jun Meng; Wenfu Chen; et al. (Environmental Pollution, 2023)

Luffa rootstock enhances salt tolerance and improves yield and quality of grafted cucumber plants by reducing sodium transport to the shoot - Zhixin Guo; Yanping Qin; Jingli Lv; Xiaojie Wang; Han Dong; Xiaoxing Dong; Tao Zhang; Nanshan Du; Fengzhi Piao (Environmental Pollution, 2023)

S-scheme MIL-101(Fe) octahedrons modified Bi2WO6 microspheres for photocatalytic decontamination of Cr(VI) and tetracycline hydrochloride: Synergistic insights, reaction pathways, and toxicity analysis - Shijie Li; Chunchun Wang; Yanping Liu; Yazi Liu; Mingjie Cai; Wei Zhao; Xiaoguang Duan (Chemical Engineering Journal, 2023)

Cu doping and Ti3C2OH quantum dots co-modifications of Zn3In2S6 boosted photocatalytic reduction of CO2 to CO via accelerating carriers transfer and enhancing CO2 adsorption and activation - Jinhang Yang; Yanping Hou; Jiangli Sun; Ting Liang; Tingting Zhu; Jiaxiang Liang; Xiaoqiong Lu; Zebin Yu; Hongxiang Zhu; Shuangfei Wang (Chemical Engineering Journal, 2023)

Citric Acid and Poly-glutamic Acid Promote the Phytoextraction of Cadmium and Lead in Solanum nigrum L. Grown in Compound Cd–Pb Contaminated Soils - Yu Wang; Weidong Duan; Chao Lv; Zhuangzhuang Wei; Yanping Zhu; Qi Yang; Ying Liu; Zhenguo Shen; Yan Xia; Kun Duan; Lingtong Quan (Bulletin of Environmental Contamination and Toxicology, 2023)

The roles of bacteria in resource recovery, wastewater treatment and carbon fixation by microalgae-bacteria consortia: A critical review - Qingnan Yu; Xinyu Pei; Yanping Wei; Sadiq Naveed; Siting Wang; Mengxuan Chang; Chunhua Zhang; Ying Ge (Algal Research, 2023)

An integrative approach for identification of smoking-related genes involving bladder cancer - Fang Gao; Huiqin Li; Zhenguang Mao; Yanping Xiao; Mulong Du; Shizhi Wang; Rui Zheng; Zhengdong Zhang; Meilin Wang (Archives of Toxicology, 2023)

Fcγ receptor‐mediated phagocytosis pathway was involved in phagocytosis of mIgM + B lymphocytes from largemouth bass ( Micropterus salmoides ) - Jing Wu; Yifan Nie; Jingya Wang; Guoqing Feng; Le Hao; Yanping Ma; Yugu Li; Zhenxing Liu (Journal of Fish Biology, 2023)
The potential for phagocytosis has been proven in teleost B cells, but the research on the regulatory mechanism of phagocytosis remains lacking. In this study, three largemouth bass ( Micropterus salmoides ) (15 ± 5 g) were injected intraperitoneally with Nocardia seriolae (10 5 CFU/100 μl/fish) in vivo , and their spleen was collected at 72 h post‐infection for mRNA‐seq. After the de novo assembly of the paired‐end reads, 73,622 unigenes were obtained. Gene expression profiling revealed that 2043 unigenes were differentially expressed after N. seriolae infection, comprising 1285 upregulated and 758 downregulated unigenes ( q ‐value 0.05, log2FC > |2|) of which 181 genes were involved in phagocytosis. The Kyoto Encyclopaedia of Genes and Genomes (KEGG) analysis demonstrated that 12 differentially expressed genes (DEG) associated with phagocytosis were enriched in the Fcγ receptor‐mediated phagocytosis signalling pathway. In vitro , the phagocytic ability of mIgM + B lymphocytes was validated using indirect immunofluorescence assay (IIFA) and fluorescence activating cell sorter (FACS), and the phagocytosis rates of the mIgM + B lymphocytes incubated with a Lyn inhibitor had decreased from 18.533 ± 6.00% to 11.610 ± 4.236% compared with the unblocked group. These results suggested that the Fcγ receptor‐mediated phagocytosis signalling pathway had participated in the phagocytosis of B cells and provide further insight into the role of B cells in innate immunology.

Carbonate dynamics in a tropical coastal system in the South China Sea featuring upwelling, river plumes and submarine groundwater discharge - Wei Yang; Xianghui Guo; Zhimian Cao; Jianzhong Su; Liguo Guo; Lifang Wang; Yi Xu; Tao Huang; Yan Li; Yanping Xu; Zhe Wang; Guizhi Wang; et al. (Science China Earth Sciences, 2022)

Ectopic expression of NAC transcription factor HaNAC3 from Haloxylon ammodendron increased abiotic stress resistance in tobacco - Xiashun Liu; Xingfeng Zong; Xia Wu; Hao Liu; Jvdong Han; Zhengpei Yao; Yanping Ren; Li Ma; Bo Wang; Hua Zhang (Planta, 2022)

Dynamic agricultural drought risk assessment for maize using weather generator and APSIM crop models - Yaxu Wang; Juan Lv; Hongquan Sun; Huiqiang Zuo; Hui Gao; Yanping Qu; Zhicheng Su; Xiaojing Yang; Jianming Yin (Natural Hazards, 2022)

Temporal and spatial characteristics of submesoscale motions in the Bohai Sea - Xueying Si; Tao Wang; Yanping Wang (Frontiers in Marine Science, 2022)
Submesoscale motions are ubiquitous in the ocean, playing a significant role in energy transfer, mass transport, and biogeochemical processes. However, little attention has been drawn to the submesoscale dynamics in shallow coastal waters. In the present study, submesoscale motions in the Bohai Sea, a typical shallow sea with mean depth of about 18 m, are studied using a validated high-resolution (~ 500 m) model based on Regional Oceanic Modeling System (ROMS). The results show that submesoscale structures in the Bohai Sea are mainly located in the shallow coastal regions, the Bohai Strait, the areas around islands and headlands, and mostly tend to be parallel to the isobaths. The periodic variations of submesoscale motions are closely related to the tidal, spring-neap, and seasonal cycles in the Bohai Sea. The spring-neap variations of submesoscale motions are mainly attributed to the curl of vertical mixing, which is stronger during spring tides than neap tides. Compared with winter, the stronger background horizontal and vertical density variance in summer are conducive to frontogenesis, resulting in more active submesoscale motions. The results in this study are expected to contribute to enriching our knowledge about submesoscale dynamics in shallow coastal seas.

Dual modification based on electrostatic repulsion of bentonite and SPR effect of Bi facilitate charge transfer of Bi2WO6 for antibiotics degradation - Tingting Zhu; Yanping Hou; Guofu Huang; Tian Fu; Jinhang Yang; Yutong Wang; Hanbing Zhang (Environmental Science and Pollution Research, 2022)

Interactions between organic matter and Fe (hydr)oxides and their influences on immobilization and remobilization of metal(loid)s: A review - Yanping Bao; Nanthi S. Bolan; Jinhao Lai; Yishun Wang; Xiaohu Jin; M. B. Kirkham; Xiaolian Wu; Zheng Fang; Yan Zhang; Hailong Wang (Critical Reviews in Environmental Science and Technology, 2022)

Geographic range size, water temperature, and extrinsic threats predict the extinction risk in global cetaceans - Chuanwu Chen; Thomas A. Jefferson; Bingyao Chen; Yanping Wang (Global Change Biology, 2022)
Despite the fact that cetaceans provide significant ecological contributions to the health and stability of aquatic ecosystems, many are highly endangered with nearly one‐third of species assessed as threatened with extinction. Nevertheless, to date, few studies have explicitly examined the patterns and processes of extinction risk and threats for this taxon, and even less between the two subclades (Mysticeti and Odontoceti). To fill this gap, we compiled a dataset of six intrinsic traits (active region, geographic range size, body weight, diving depth, school size, and reproductive cycle), six environmental factors relating to sea surface temperature and chlorophyll concentration, and two human‐related threat indices that are commonly recognized for cetaceans. We then employed phylogenetic generalized least squares models and model selection to identify the key predictors of extinction risk in all cetaceans, as well as in the two subclades. We found that geographic range size, sea surface temperature, and human threat index were the most important predictors of extinction risk in all cetaceans and in odontocetes. Interestingly, maximum body weight was positively associated with the extinction risk in mysticetes, but negatively related to that for odontocetes. By linking seven major threat types to extinction risk, we further revealed that fisheries bycatch was the most common threat, yet the impacts of certain threats could be overestimated when considering all species rather than just threatened ones. Overall, we suggest that conservation efforts should focus on small‐ranged cetaceans and species living in warmer waters or under strong anthropogenic pressures. Moreover, further studies should consider the threatened status of species when superimposing risk maps and quantifying risk severity. Finally, we emphasize that mysticetes and odontocetes should be conserved with different strategies, because their extinction risk patterns and major threat types are considerably different. For instance, large‐bodied mysticetes and small‐ranged odontocetes require special conservation priority.

Gene–environment interaction between circadian clock gene polymorphisms and job stress on the risk of sleep disturbances - Yuxi Wang; Min Zhao; Peixin Li; Chuancheng Wu; Yanping Lv; Yu Jiang (Psychopharmacology, 2022)

A novel antisense long non‐coding RNA participates in asexual and sexual reproduction by regulating the expression of GzmetE in Fusarium graminearum - Jie Wang; Wenping Zeng; Jiatao Xie; Yanping Fu; Daohong Jiang; Yang Lin; Weidong Chen; Jiasen Cheng (Environmental Microbiology, 2022)

Automatic identification of harmful algae based on multiple convolutional neural networks and transfer learning - Mengyu Yang; Wensi Wang; Qiang Gao; Chen Zhao; Caole Li; Xiangfei Yang; Jiaxi Li; Xiaoguang Li; Jianglong Cui; Liting Zhang; Yanping Ji; Shuqin Geng (Environmental Science and Pollution Research, 2022)

Responses of phytoplankton communities driven by differences of source water intrusions in the El Niño and La Niña events in the Taiwan Strait during the early spring - Yanping Zhong; Edward A. Laws; Jiafu Zhuang; Jingxiao Wang; Peixuan Wang; Caiyun Zhang; Xin Liu; Bangqin Huang (Frontiers in Marine Science, 2022)
The El Niño Southern Oscillation (ENSO) is one of the most important drivers of interannual variations of marine ecosystems, especially monsoonal ecosystems. The channel effect in a strait amplifies the impact of monsoons and may be an ideal area to study ecosystem responses to ENSO events. Previous studies have shown that physical processes in the Taiwan Strait (TWS) vary during the different ENSO phases, but the biological responses are still unclear. In this study, we found clear differences in the physical, chemical, and biological characteristics of the TWS between different ENSO phases based on data from satellites and field cruises during the 2015–2016 El Niño and 2017–2018 La Niña events. Although the monsoonal patterns were similar during early spring cruises during two ENSO events, the influence of the China Coastal Current (CCC), which is characterized by low sea surface temperature, low salinity, and high nutrient concentrations, was 1.5 times greater during the 2015–2016 El Niño than the 2017–2018 La Niña. The average chlorophyll a concentration was therefore higher in 2016 than that in 2018. The phytoplankton consisted mainly of diatoms, dinoflagellates, and cryptophytes during the 2015–2016 El Niño, but concentrations of those phytoplankton groups decreased, and concentrations of prasinophytes, Synechococcus , and Prochlorococcus increased during the 2017–2018 La Niña. Their influence of the CCC and warm currents were associated with the variations in phytoplankton community structure in the TWS. The results of this study enhance understanding of the responses of marine ecosystems to climate variabilities, and of the changes that climate change may bring to strait ecosystems.

Polyethylene microplastic exposure and concurrent effect with Aeromonas hydrophila infection on zebrafish - Ning Ding; Lin Jiang; Xiao Wang; Chun Wang; Yue Geng; Jianxin Zhang; Yingxue Sun; Yanping Zhang; Quan Yuan; Hong Liu (Environmental Science and Pollution Research, 2022)

Genome-wide identification of chicken bursae of Fabricius miRNAs in response to very virulent infectious bursal disease virus - Xuewei Huang; Yue Li; Xiaona Wang; Junyan Zhang; Li Wang; Han Zhou; Yanping Jiang; Wen Cui; Xinyuan Qiao; Yijing Li; Lijie Tang (Archives of Virology, 2022)

Fungal dynamic changes in naturally fermented ‘Kyoho’ grape juice - Wenjuan Zhao; Zhiming Zhang; Yuhong Gao; Xiaozhen Liu; Chaojin Du; Fuxian Ma; Sujie Wang; Wanyuan Shi; Yanping Yang; Ruyou Deng; Hanyao Zhang (Archives of Microbiology, 2022)

Degradation of sulfadiazine by UV/Oxone: roles of reactive oxidative species and the formation of disinfection byproducts - Juxiang Chen; Caiqiong Dai; Yanping Zhu; Yuqiong Gao; Wenhai Chu; Naiyun Gao; Qiongfang Wang (Environmental Science and Pollution Research, 2022)

Occurrence of polycyclic aromatic hydrocarbons (PAHs) in the seafood from an important fishing area in the East China Sea and a comparison between seafood from different origins - Wang Qian; Lu Dequan; Xiong Yiran; Peng Fei; Li Juan-ying; Wu Feng; Chu Yanping; Sun Ruihua; Tian Siquan (Environmental Monitoring and Assessment, 2022)

Development and application of a shaking table system - Chunhua Gao; Yanping Yang; Jieqiong Wang; Mengyuan Qin; Xiaobo Yuan (Arabian Journal of Geosciences, 2022)

The regulatory gene wblA is a target of the orphan response regulator OrrA in Streptomyces coelicolor - Yanping Zhu; Xinyuan Wang; Jing Zhang; Xue Ni; Xia Zhang; Meifeng Tao; Xiuhua Pang (Environmental Microbiology, 2022)
Summary Our previous study using transposon mutagenesis indicated that disruption of the putative response regulator gene orrA impacted antibiotic production in Streptomyces coelicolor . In this study, the role of OrrA was further characterized by comparing the phenotypes and transcriptomic profiles of the wild‐type S . coelicolor strain M145 and Δ orrA , a strain with an inactivated orrA gene. Chromatin immunoprecipitation using a strain expressing OrrA fused with FLAG showed that OrrA binds the promoter of wblA , whose expression was downregulated in Δ orrA . The interaction of OrrA with the wblA promoter was further validated by a pull‐down assay. Similar to Δ orrA , the deletion mutant of wblA (Δ wblA ) was defective in development, and developmental genes were expressed at similar levels in Δ orrA and Δ wblA . Although both OrrA and WblA downregulated actinorhodin and undecylprodigiosin, their roles in regulation of the calcium‐dependent antibiotic and yellow‐pigmented type I polyketide differed. sco1375 , a gene of unknown function, was identified as another OrrA target, and overexpression of either s co1375 or wblA in Δ orrA partially restored the wild‐type phenotype, indicating that these genes mediate some of the effects of OrrA. This study revealed targets of OrrA and provided more insights into the role of the orphan response regulator OrrA in Streptomyces .

Hyperspectral anomaly detection based on score-guided cooperative autoencoders - Minkai Hou; Tao Wang; Yanzhao Su; Yanping Cai; Yiting Wang (International Journal of Remote Sensing, 2022)

HrreNet: semantic segmentation network for moderate and high-resolution satellite images - Yanping Li; Lu Wang; Lei Zhang; Haiwen Chen; Shiying Wang; Xiaoying Wang (International Journal of Remote Sensing, 2022)

Detection of a major QTL and development of KASP markers for seed weight by combining QTL-seq, QTL-mapping and RNA-seq in peanut - Zhihui Wang; Liying Yan; Yuning Chen; Xin Wang; Dongxin Huai; Yanping Kang; Huifang Jiang; Kede Liu; Yong Lei; Boshou Liao (Theoretical and Applied Genetics, 2022)

X-ray Irradiation Improves Neurological Function Recovery of Injured Spinal Cord by Inhibiting Inflammation and Glial Scar Formation - Yi Wang; Yanping Niu; Fanguo Lin; Peng Su; Liesong Chen; Dong Liu; Yongming Sun (Journal of Molecular Neuroscience, 2022)

Poor evidence for host-dependent regular RNA editing in the transcriptome of SARS-CoV-2 - Jinbao Zong; Yanping Zhang; Fenfen Guo; Changyuan Wang; Hong Li; Gaoyang Lin; Wenqing Jiang; Xiaoping Song; Xiufang Zhang; Feng Huang; Min Qi; Xin Zheng (Journal of Applied Genetics, 2022)

Analysis and Health Risk Assessment of Potentially Toxic Elements in Three Codonopsis Radix Varieties in China - Ruibin Bai; Yanping Wang; Yajie Zhang; Yan Wang; Jiabing Han; Zixia Wang; Jing Zhou; Fangdi Hu (Biological Trace Element Research, 2022)

Hyperspectral anomaly detection based on adaptive weighting method combined with autoencoder and convolutional neural network - Minkai Hou; Tao Wang; Yanzhao Su; Yanping Cai; Jiping Cao (International Journal of Remote Sensing, 2022)

Dopaminergic Neurons in the Ventral Tegmental–Prelimbic Pathway Promote the Emergence of Rats from Sevoflurane Anesthesia - Yanping Song; Ruitong Chu; Fuyang Cao; Yanfeng Wang; Yanhong Liu; Jiangbei Cao; Yongxin Guo; Weidong Mi; Li Tong (Neuroscience Bulletin, 2022)

Molecular epidemiology and clinical characterization of human rhinoviruses circulating in Shanghai, 2012-2020 - Haixia Jiang; Tianyun Yang; Chunyi Yang; Yanping Lu; Zhigang Yi; Qin Zhang; Wei Wang (Archives of Virology, 2022)

Anisakidae parasitism activated immune response and induced liver fibrosis in wild anadromous Coilia nasus - Congping Ying; Xin Fang; Honglan Wang; Yanping Yang; Pao Xu; Kai Liu; Guojun Yin (Journal of Fish Biology, 2022)
Anisakidae nematode larvae is one of the most common parasites in wild anadromous Coilia nasus . This study aims to explore the mechanism of the C. nasus immune response to the parasitism of Anisakid nematode larvae. Results found that Anisakid nematode larvae parasitism caused liver injury as evidenced by histomorphology results as well as high levels of aminotransferase and aspertate aminotransferase. Furthermore, Anisakid nematode larvae parasitism induced an immune response in the host, which was characterized by the elevated populations of macrophages and neutrophils in the liver and head‐kidney in the Anisakidae‐infected group compared to the noninfected group. The expression of immunoglobulin IgM and IgD in the liver and head‐kidney was also increased in the Anisakidae‐infected group. The Anisakidae‐infected group showed higher activity of antioxidant enzymes catalase and superoxide dismutase, which indicates severe oxidative stress, and increased production of pro‐inflammatory cytokines, TNF‐α, IL‐6 as well as MCP‐1 in the liver compared with the noninfected group. As a result of inflammation, livers of hosts in the Anisakidae‐infected group showed fibrosis, and elevated expression of associated proteins including α‐smooth muscle actin, fibronectin, collagen type I and type III compared with the noninfected group. We demonstrated that Anisakid nematode larvae parasitism results in injury and fibrosis in the liver, and triggers immune cell infiltration and inflammation in the liver and head‐kidney of C. nasus . Altogether, the results provide a foundation for building an interaction between parasite and host, and will contribute to C. nasus population and fishery resource protection.

Microplastic Contamination on the Beaches of South China - Bingwen Chai; Yanping Li; Li Wang; Xiao-Tan Zhang; Yi-Ping Wan; Fengyuan Chen; Jie Ma; Wenlu Lan; Ke Pan (Frontiers in Marine Science, 2022)
Microplastics (MPs) have emerged as a pollutant of significant global concern. The sandy beach is a fragile environment that deserves our special attention with regard to MP contamination, as this area is a hotspot that accumulates large quantities of plastic waste. Notably, our current understanding of the MP distribution on beaches and the scale of contamination is far from sufficient. Hence, this study investigated the occurrence and characteristics of MPs on 14 beaches along the coast of South China. The MPs were ubiquitously distributed in the sand, most were small, less than 1 mm. A total of 18 types of polymers were identified in the sand, suggesting that diverse types of MPs are present on the beaches. Polyethylene, polypropylene, and polystyrene were the dominant types of MPs in most of our sampling sites. The MP abundance was higher in the upper layers (0–20 cm) of the beach than in the deeper layers (20–40 cm) of the sampling site when characterized by depth (Yangjiang beach). Our study demonstrates the extent and severity of MP pollution on the beaches of South China and provides implications for future remediation measures. More effort is needed to clarify the vertical distribution of MPs on beaches, especially for those MPs less than 1 μm.

Synchronous removal of tetracycline and copper (II) over Z‑scheme BiVO4/rGO/g-C3N4 photocatalyst under visible-light irradiation - Jiangli Sun; Yiyuan Rong; Yanping Hou; Lingli Tu; Qingyu Wang; Yuying Mo; Shuxuan Zheng; Zan Li; Zuji Li; Zebin Yu (Environmental Science and Pollution Research, 2022)

Fishery Status and Rebuilding of Major Economic Fishes in the Largest Freshwater Lake in China Based on Limited Data - Yang Liu; Huiyun Fu; Linlong Wang; Li Lin; Gang He; Peifeng Fu; Changlai Wang; Yanping Zhang; Bin Kang (Fishes, 2022)
Poyang Lake, the largest freshwater lake in China, possesses abundant fishery resources, but its fish stock status is still unclear. In this work, the stock status of and fishing efforts of nine major economic fishes in the Poyang Lake were estimated from 2000 to 2019 with a catch-based maximum sustainable yield (CMSY) model based on catch and resilience data. It was further predicted whether the biomass of those fishes could be restored to support maximum sustainable yield (Bmsy) under the policy of “Ten years fishing moratorium in the Yangtze River”. The results showed that goldfish Carassius auratus, grass carp Ctenopharyngodon idella, and black carp Mylopharyngodon piceus suffered from higher fishing efforts and low biomass in the past 20 years; bighead carp Hypophthalmichthys nobilis, yellow catfish Tachysurus fulvidraco, and common carp Cyprinus carpio responded differently to their fishing efforts; silver carp Hypophthalmichthys molitrix, Amur catfish Silurus asotus, and mandarin fish Siniperca chuatsi were underexploited. Six species were overfished in 2019, and their biomass would be expected to recover for sustainable exploitation during the fishing moratorium, except for M. piceus. This study provided a case study of feasible freshwater fishery evaluation in limnetic ecosystems.

SARS-CoV-2 competes with host mRNAs for efficient translation by maintaining the mutations favorable for translation initiation - Yanping Zhang; Xiaojie Jin; Haiyan Wang; Yaoyao Miao; Xiaoping Yang; Wenqing Jiang; Bin Yin (Journal of Applied Genetics, 2022)

The expression and interaction proteins analysis of BjuFKF1/LKP2 in B. juncea - Jing Zeng; Anran Wu; Yuemin Yang; Liang Zhao; Li Chen; Chuanqi Wang; Xin Yang; Yanping Chen; Shiyan Liu; Pei Luo; Junli Wang (Molecular Genetics and Genomics, 2022)

Substantial changes of chemical composition and sources of fine particles during the period of COVID-19 pandemic in Taiyuan, Northern China - Yang Wang; Yanping Wen; Yang Cui; Lili Guo; Qiusheng He; Hongyan Li; Xinming Wang (Air Quality, Atmosphere & Health, 2022)

Recombinant Avian β-Defensin Produced by Food-Grade Lactococcus as a Novel and Potent Immunological Enhancer Adjuvant for Avian Vaccine - Tingting Wang; Zhihao Wang; Jielan Mi; Wenqian Wang; Kai Li; Xiaole Qi; Yulong Gao; Li Gao; Changjun Liu; Yanping Zhang; Qing Pan; Xiaomei Wang; et al. (Probiotics and Antimicrobial Proteins, 2021)
In this study, we expressed rAvBD1-2–6-13 protein through Lactococcus lactis NZ3900, and the effects of the recombinant L. lactis NZ3900 as an immune enhancer and immune adjuvant were verified using in vivo and in vitro tests. In vitro tests revealed that recombinant L. lactis NZ3900 significantly activated the NF-κB signaling pathway and IRF signaling pathway in J774-Dual™ report cells and significantly increased the transcript levels of IL-10, IL-12p70, CD80, and CD86 in chicken PBMCs and chicken HD11 cells. In vivo experiments revealed that the immunized group supplemented with recombinant L. lactis NZ3900 as an adjuvant had significantly higher serum antibody titers and higher proliferative activity of PBMCs in the blood of the chickens immunized with NDV live and inactivated vaccines. Our study shows that the recombinant L. lactis NZ3900 has strong immunomodulatory activity both in vivo and in vitro and is a potential immune enhancer. Our work lays the foundation for the research and development of new animal immune enhancers for application in the poultry industry.

Simvastatin Blocks Reinstatement of Cocaine-induced Conditioned Place Preference in Male Mice with Brain Lipidome Remodeling - Wei Xu; Yuman He; Jiamei Zhang; Hongchun Li; Xuemei Wan; Menglu Li; Yonghai Wang; Rui Xu; Haoluo Zhang; Yanping Dai; Haxiaoyu Liu; Linhong Jiang; et al. (Neuroscience Bulletin, 2021)

Assessing risk to human health for heavy metal contamination from public point utility through ground dust: a case study in Nantong, China - Yanping Wang; Peng Qian; Dongming Li; Haifeng Chen; Xiangqian Zhou (Environmental Science and Pollution Research, 2021)

Magnetic minerals in Mid-Pleistocene sediments on the Caiwei Guyot, Northwest Pacific and their response to the Mid-Brunhes climate event - Liang Yi; Haifeng Wang; Geng Liu; Yanping Chen; Huiqiang Yao; Xiguang Deng (Acta Oceanologica Sinica, 2021)

The Innate Immune Response to Infection by Polyascus gregaria in the Male Chinese Mitten Crab (Eriocheir sinensis), Revealed by Proteomic Analysis - Yanping Yang; Fengjiao Ma; Juanjuan Dong; Lianxing Li; Ping Ren; Yuning Zhang; Yatao Wu; Yinping Wang; Kai Liu; Fang Zhang (Fishes, 2021)
The Chinese mitten crab (Eriocheir sinensis) is a representative catadromous invertebrate of the Yangtze River and a commercial species widely cultivated in China. Both cultivated and wild crabs suffer from a variety of parasites and pathogens, which can result in catastrophic economic losses in aquaculture revenue. Polyascus gregaria, a parasitic barnacle with a highly derived morphology, is specialized in invading these crabs. This study examines the immunological mechanism in E. sinensis infected with P. gregaria. Tandem mass tags (TMT), a specialized method of mass-spectrometry, was used to analyze the infection by P. gregaria resistance at the protein level. In the hepatopancreas of infected crabs, 598 proteins differentially expressed relating to physiological change, of which, 352 were upregulated and 246 were downregulated. Based on this differential protein expression, 104 GO terms and 13 KEGG pathways were significantly enriched. Differentially expressed proteins, such as ATG, cathepsin, serpin, iron-related protein, Rab family, integrin, and lectin, are associated with the lysosome GO term and the autophagy-animal KEGG pathways, both of which likely relate to the immune response to the parasitic P. gregaria infection. These results show the benefit of taking a detailed, protein-level approach to understanding the innate immune response of aquatic invertebrates to macroparasite infection.

Impact of MtrA on phosphate metabolism genes and the response to altered phosphate conditions in Streptomyces - Yanping Zhu; Peipei Zhang; Ting Lu; Xinyuan Wang; Aiying Li; Yinhua Lu; Meifeng Tao; Xiuhua Pang (Environmental Microbiology, 2021)
Summary Phosphate metabolism is known to be regulated by the PhoPR regulatory system in Streptomyces and some other bacteria. In this study, we report that MtrA also regulates phosphate metabolism in Streptomyces . Our data showed that, in Streptomyces coelicolor , MtrA regulates not only phosphate metabolism genes such as phoA but also phoP under different phosphate conditions, including growth on rich complex media without added inorganic phosphate and on defined media with low or high concentrations of inorganic phosphate. Cross‐regulation was also observed among mtrA , phoP and glnR under these conditions. We demonstrated both in vitro and in vivo binding of MtrA to the promoter regions of genes associated with phosphate metabolism and to the intergenic region between phoR and phoU , indicating that these phosphate metabolism genes are targets of MtrA. We further showed that MtrA in S . lividans and S . venezuelae has detectable regulatory effects on expression of phosphate metabolism genes. Additionally, the MtrA homologue from Corynebacterium glutamicum bound predicted MtrA sites of multiple phosphate metabolism genes, implying its potential for regulating phosphate metabolism in this species. Overall, our findings support MtrA as a major regulator for phosphate metabolism in Streptomyces and also potentially in other actinobacteria.

Dynamic sulfur–iron cycle promoted phosphorus mobilization in sediments driven by the algae decomposition - Siyuan Zhang; Yanping Zhao; Chuanqiao Zhou; Haixin Duan; Guoxiang Wang (Ecotoxicology, 2021)

Insight into the Interaction Between Microplastics and Microorganisms Based on a Bibliometric and Visualized Analysis - Yanping Jiang; Wanjun Xia; Rui Zhao; Mengge Wang; Jinfeng Tang; Yongjun Wei (Bulletin of Environmental Contamination and Toxicology, 2021)

Mechanisms, physiology, and recent research progress of gastric emptying - Weilin Liu; Yangyi Jin; Peter J. Wilde; Yingying Hou; Yanping Wang; Jianzhong Han (Critical Reviews in Food Science and Nutrition, 2021)

A semi-supervised learning method for hyperspectral imagery based on self-training and local-based affinity propagation - Haimiao Ge; Haizhu Pan; Liguo Wang; Cheng Li; Yanzhong Liu; Wenlong Zhu; Yanping Teng (International Journal of Remote Sensing, 2021)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

A novel antisense long non‐coding RNA participates in asexual and sexual reproduction by regulating the expression of GzmetE in Fusarium graminearum - Jie Wang; Wenping Zeng; Jiatao Xie; Yanping Fu; Daohong Jiang; Yang Lin; Weidong Chen; Jiasen Cheng (Environmental Microbiology, 2021)
Summary Fusarium graminearum is an important worldwide pathogen that causes Fusarium head blight in wheat, barley, maize and other grains. LncRNAs play important roles in many biological processes, but little is known about their functions and mechanisms in filamentous fungi. Here, we report that a natural antisense RNA, GzmetE‐AS , is transcribed from the opposite strand of GzmetE . GzmetE encodes a homoserine O ‐acetyltransferase, which is important for sexual development and plant infection. The expression of GzmetE‐AS was increased significantly during the conidiation stage, while GzmetE was upregulated in the late stage of sexual reproduction. Overexpression of GzmetE‐AS inhibited the transcription of GzmetE . In contrast, the expression of GzmetE was significantly increased in GzmetE‐AS transcription termination strain GzmetE‐AS ‐T. Furthermore, GzmetE‐AS ‐T produced more perithecia and facilitated the ascospore discharge, resembling the phenotype of GzmetE overexpressing strains. However, overexpression of GzmetE‐AS in ∆dcl1/2 strain cannot inhibit the expression of GzmetE , and the GzmetE nat‐siRNA is also significantly reduced in ∆dcl1/2 mutant. Taken together, we have identified a novel antisense lncRNA GzmetE‐AS , which is involved in asexual and sexual reproduction by regulating its antisense gene GzmetE through RNAi pathway. Our findings reveal that the lncRNA plays critical roles in the development of F . graminearum .

SETD4 in the Proliferation, Migration, Angiogenesis, Myogenic Differentiation and Genomic Methylation of Bone Marrow Mesenchymal Stem Cells - Xiaomin Liao; Caixia Wu; Zhongming Shao; Shuya Zhang; Yuan Zou; Keke Wang; Yanping Ha; Jingci Xing; Axiu Zheng; Zhihua Shen; Shaojiang Zheng; Junli Guo; et al. (Stem Cell Reviews and Reports, 2021)

Genetic Recombination of the Mantle Color Pattern of Two Boring Giant Clam (Tridacna crocea) Strains - Junjie Wang; Zihua Zhou; Haitao Ma; Jun Li; Yanping Qin; Jinkuan Wei; Xingyou Li; Qingliang Liao; Yunqing Li; Gongpengyang Shi; Yinyin Zhou; Yuehuan Zhang; et al. (Frontiers in Marine Science, 2021)
According to the RGB law display, the polymorphism of the giant clam mantle color pattern is through four iridocytes. The boring giant clam ( Tridacna crocea ) exhibits diverse mantle colors, including blue, green, purple, gold, and orange. In order to evaluate the genetic laws driving these mantle color patterns, a complete diallel cross between two color strains [blue strain (only blue iridocyte) and the yellow-green strain (yellow and green iridocytes)] was performed. Using a single-to-single mating system, two intra-strain crosses (BB and YY) and two reciprocal inter-strain crosses (BY and YB) were produced in triplicates. Higher fertilization rate and hatching rate were observed in all experimental groups, suggesting that there was no sperm–egg recognition barrier between the two strains. In the grow-out stage, the size of the reciprocal hybrids was larger than that of the two pure strains with a degree of heterosis. In addition, compared with the two pure strains, the hybrids have higher larval metamorphosis rate and higher survival rate. At 1 year of age, the mantle color pattern of pure strains showed 100% stable inheritance, while the reciprocal hybrids exhibited colorful patterns (a combination of blue, yellow, and green), suggesting that there was a genetic recombination of the mantle colors during the stable expression period. These results provide a theoretical basis for the formation of the mantle color of giant clam and its genetic segregation law, as well as provide guidance for genetic breeding of giant clams.

Correction to: Bat echolocation in continental China: a systematic review and first acoustic identification key for the country - David López-Bosch; Joe Chun-Chia Huang; Yanping Wang; Ana Filipa Palmeirim; Luke Gibson; Adrià López-Baucells (Mammal Research, 2021)

Bat echolocation in continental China: a systematic review and first acoustic identification key for the country - David López-Bosch; Joe Chun-Chia Huang; Yanping Wang; Ana Filipa Palmeirim; Luke Gibson; Adrià López-Baucells (Mammal Research, 2021)

Overexpression of KcNHX1 gene confers tolerance to multiple abiotic stresses in Arabidopsis thaliana - Yanqin Wang; Yuan Guo; Fen Li; Yanping Liu; Shuangxia Jin (Journal of Plant Research, 2021)

LncRNA TRHDE-AS1 inhibit the scar fibroblasts proliferation via miR-181a-5p/PTEN axis - Yanping Wei; Tingting Wang; Ningning Zhang; Yunyun Ma; Siji Shi; Ruxing Zhang; Xianzhao Zheng; Lindong Zhao (Journal of Molecular Histology, 2021)
Hypertrophic scar (HS), a fibroproliferative disorder caused by abnormal wound healing after skin injury, which is characterized by excessive deposition of extracellular matrix and invasive growth of fibroblasts. Recent studies have shown that some non-coding RNA implicated the formation of HS, but the mechanism remains unclear. In this study, we found that lncRNA TRHDE-AS1 was downregulated in HS tissues and HSFs, and the level of lncRNA TRHDE-AS1 negatively correlated with the level of miR-181a-5p in HS tissue and HSFs. Overexpressed lncRNA TRHDE-AS1 significantly suppressed miR-181a-5p level, while promoted HSFs apoptosis and inhibited HSFs proliferation. Further study shown that PTEN was a direct target of miR-181a-5p, and lncRNA TRHDE-AS1 served as a molecular sponge for miR-181a-5p to regulate the expression of PTEN. Overexpression of PTEN could eliminate lncRNA TRHDE-AS1-mediated proliferation suppression of HSFs. In conclusion, our study suggested that lncRNA TRHDE-AS1/miR-181a-5p/PTEN axis plays an important role in promoting hypertrophic scar formation, which may be effectively used as a therapeutic target for hypertrophic scar treatment.

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Area threshold and trait–environment associations of butterfly assemblages in the Zhoushan Archipelago, China - Chuanwu Chen; Aichun Xu; Yanping Wang (Journal of Biogeography, 2021)
Aim An area threshold is usually considered as the point of abrupt change in the species–area relationship (SAR). Despite their widespread existence, few studies have considered the influence of data transformations on their presence or the mechanisms that generate them. The aims of this study were thus to test for the existence of an area threshold in butterfly assemblages and to compare trait–environment associations between small and large islands split by the threshold. Location Zhoushan Archipelago, China. Taxon Butterflies. Methods We used the line‐transect method to survey butterflies on 42 islands from July to August 2014. We also collected data on three commonly used ecological traits of butterflies (wingspan, wing loading and body weight). We transformed the butterfly datasets into three types (log‐log, semi‐log and untransformed) and fitted each of them using a set of breakpoint regression models. We then split all islands into small and large islands based on the area threshold and analysed the trait–environment associations for each island group. Results Two‐slope breakpoint models performed best for log‐log and semi‐log transformed datasets. However, the former exhibited a steep‐shallow shape with an area threshold of 0.820 km 2 and the latter was in shallow‐steep shape with a threshold of 17.022 km 2 . By contrast, no threshold was detected when using the untransformed power model. Moreover, for small islands, small area and large isolation were positively correlated with species with large wing loading and body weight. For large islands, however, the perimeter to area ratio (PAR) was significantly and positively related to wing loading. Main conclusions We found that data transformations may influence the detection of area thresholds. Trait–environment analyses can further provide novel and mechanistic insights into processes generating area thresholds. We urge that the influence of data transformations and ecological traits of species should be explicitly considered in future studies.

Clinical features and prognostic factors of patients with COVID-19 in Henan Province, China - Qianqian Zhang; Zheng Wang; Yanping Lv; Jiang Zhao; Qiang Dang; Dongfeng Xu; Dongxiang Zhao; Haiyang Liu; Ziqi Wang; Xingru Zhao; Zhiwei Xu; Xiaoju Zhang (Human Cell, 2021)

Probiotic Potential and Wide-spectrum Antimicrobial Activity of Lactic Acid Bacteria Isolated from Infant Feces - Xing Wang; Weidong Wang; Haoxin Lv; Hua Zhang; Yuan Liu; Miao Zhang; Yanping Wang; Zhongfang Tan (Probiotics and Antimicrobial Proteins, 2021)

Contamination, distribution, and risk assessment of antibiotics in the urban surface water of the Pearl River in Guangzhou, South China - Chang Wang; Yanping Zhao; Shuang Liu; Qin Xiao; Weixin Liang; Yumei Song (Environmental Monitoring and Assessment, 2021)

Molecular evolution and pathogenicity of chicken anemia virus isolates in China - Yue Li; Nana Yan; Yongqiang Wang; Aijing Liu; Changjun Liu; Xingge Lan; Bo Yang; Yulong Gao; Honglei Gao; Xiaole Qi; Hongyu Cui; Kai Li; et al. (Archives of Virology, 2021)

Effects of Rhein-8-O-β-D-glucopyranoside on the Biofilm Formation of Streptococcus mutans - Yaochao Zhang; Yong Zhu; Yanping Zuo; Chengfang Tang; Fang Zhou; Xiaoming Cui; Lin Wang (Current Microbiology, 2021)

Research on the Establishment and Application of the Environmental Health Indicator System of Atmospheric Pollution in China - Qiong Wang; Liangzhong Li; Yanping Zhang; Qian Cui; Yuanzheng Fu; Wanying Shi; Qin Wang; Dongqun Xu (Bulletin of Environmental Contamination and Toxicology, 2021)

Diversity of gut microbiomes in marine fishes is shaped by host‐related factors - Qi Huang; Ronia C. Sham; Yu Deng; Yanping Mao; Chunxiao Wang; Tong Zhang; Kenneth M. Y. Leung (Molecular Ecology, 2020)
Microorganisms in the gastrointestinal tract of animals play vital roles in food digestion, homeostasis and immune response regulation. Globally, there are 33,700 fish species, representing almost half of all vertebrate diversity and a wide range of physiologies, ecologies and life histories. To investigate gut microbiomes with high coverage, we performed 16S rRNA gene amplicon sequencing with 115 samples of 20 common marine fish species. The fish gut microbiome is a remarkably simple community with low microbial diversity (a maximum of 300 amplicon sequence variants only) and has up to 70% of unknown species in some fish species. The gut microbial community structure was significantly shaped by the combined influence of host‐associated factors, including the fish taxon ( p R 2 = 0.16, ω 2 = 0.04), feeding habit ( p R 2 = 0.06, ω 2 = 0.02) and trophic level ( p R 2 = 0.04, ω 2 = 0.01), although the influence was subtle with a small effect size. The core gut microbiomes of different feeding habits were also previously discovered in animal‐associated and corresponding habitat samples. Certain energy metabolism pathways were enriched in herbivore/omnivore and zooplanktivore/zoobenthivore fishes, whereas lipid metabolism and glycan metabolism were enriched in zoobenthivore/piscivore fishes. Moreover, substantial taxonomic variability was found between the gut microbiomes of fish and animals, indicated by their low degree of shared microbiota. The data and observations reported herein pave the way for further investigations on the co‐evolution of fish gut microbiomes and their hosts, the physiological functions of gut microorganisms and the development of probiotics for improving the nutrition and health of aquaculture fish species.

Retention of nitrogen and phosphorus in Lake Chaohu, China: implications for eutrophication management - Yanping Wang; Xiangzhen Kong; Zhaoliang Peng; Hui Zhang; Gang Liu; Weiping Hu; Xiangqian Zhou (Environmental Science and Pollution Research, 2020)

Comparative analysis of the gut microbiota of grass carp fed with chicken faeces - Famin Ke; Yanping Gao; Li Liu; Chun Zhang; Qin Wang; Xiaowei Gao (Environmental Science and Pollution Research, 2020)

The prediction of water conducted zone in coal mining by Internet of things perception - Zhenguo Yan; Xintan Chang; Yanping Wang (Arabian Journal of Geosciences, 2020)

High plant species richness and stable climate lead to richer but phylogenetically and functionally clustered avifaunas - Na Wang; Lingfeng Mao; Xueting Yang; Xingfeng Si; Yanping Wang; Wolf L. Eiserhardt; Gang Feng (Journal of Biogeography, 2020)
Aims Glacial–interglacial climate stability and contemporary climate could affect bird diversity through their direct effects on diversification and physiological tolerance, and indirect effects on plant species richness, which could provide more food and ecological niches. This study aims to quantitatively assess the direct and indirect effects of these drivers on species richness, phylogenetic and functional structure of bird assemblages. Location Mainland China. Taxon Birds. Methods Ordinary least squares models and simultaneous autoregressive models were used to test the associations between glacial–interglacial climate anomaly, contemporary climate, plant species richness, elevation range and species richness, phylogenetic structure, functional structure of bird assemblages in mainland China. Structural equation models were used to distinguish between direct and indirect effects of these variables on bird diversity. Results High bird species richness with phylogenetically and functionally clustered structure occurred in regions with more plant species and stable glacial–interglacial climate. Notably, the phylogenetically clustered bird assemblages were composed of young lineages. Contemporary precipitation and elevation range affected bird diversity through their indirect effects on plant species richness. Main Conclusions These findings suggest that more plant species and stable glacial–interglacial climate may promote bird diversity through their effects on in situ diversification and species dispersal rate in southwestern China. Therefore, the well‐preserved plant and bird diversity through the long‐term climate fluctuations should be of great importance of biodiversity conservation in China.

Pseudorabies virus encephalitis in humans: a case series study - Siyuan Fan; Hongxun Yuan; Lei Liu; Hongfang Li; Shengnan Wang; Weili Zhao; Yihan Wu; Pei Wang; Yafang Hu; Jun Han; Yanli Lyu; Wuchao Zhang; et al. (Journal of NeuroVirology, 2020)

Genetic dynamics of earlier maturity group emergence in south-to-north extension of Northeast China soybeans - Mengmeng Fu; Yanping Wang; Haixiang Ren; Weiguang Du; Deliang Wang; Rongjun Bao; Xingyong Yang; Zhongyan Tian; Lianshun Fu; Yanxi Cheng; Jiangshun Su; Bincheng Sun; et al. (Theoretical and Applied Genetics, 2020)

Suburban Building Detection from Optical Remote Sensing Images Based on a Deformation Adaptability Model - Fukun Bi; Jie Zhang; Fengqian Pang; Mingming Bian; Yanping Wang (Journal of the Indian Society of Remote Sensing, 2020)

New Insights on ‘GALA’ Apple Fruit Development: Sugar and Acid Accumulation: A Transcriptomic Approach - Hongxia Tao; Hanqing Sun; Yufei Wang; Xuena Song; Yanping Guo (Journal of Plant Growth Regulation, 2020)

Context-aware MDNet for target tracking in UAV remote sensing videos - Fukun Bi; Mingyang Lei; Yanping Wang (International Journal of Remote Sensing, 2020)

The Diversity of Associated Microorganisms in Different Organs and Rhizospheric Soil of Arctium lappa L. - Yanping Xing; Yanyun Yang; Liang Xu; Ning Hao; Rong Zhao; Jiahao Wang; Shengnan Li; Dachuan Zhang; Tingting Zhang; Tingguo Kang (Current Microbiology, 2020)

Effects of Bacillus Subtilis-Zinc on Rats with Congenital Zinc Deficiency - Yanping Huang; Baowei Wang; Guodong Liu; Wenhua Ge; Mingai Zhang; Bin Yue; Min Kong (Biological Trace Element Research, 2020)

Characterizing the effects of hypoxia on the metabolic profiles of mesenchymal stromal cells derived from three tissue sources using chemical isotope labeling liquid chromatography-mass spectrometry - Qiaoling Pan; Dan Wang; Deying Chen; Yanni Sun; Xudong Feng; Xiaowei Shi; Yanping Xu; Xian Luo; Jiong Yu; Yang Li; Hongcui Cao; Liang Li (Cell and Tissue Research, 2020)

Levels of human cytomegalovirus miR-US25-1-5p and miR-UL112-3p in serum extracellular vesicles from infants with HCMV active infection are significantly correlated with liver damage - Jing Zhang; Yujing Huang; Qing Wang; Yanping Ma; Ying Qi; Zhongyang Liu; Jingui Deng; Qiang Ruan (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Sulfate-enhanced degradation of Rhodamine B in the hydrogen peroxide/hydroxylamine system - Shengli Wang; Linlin Yan; Xiaohui Guan; Yanping Jia; Lianfa Song; Haifeng Zhang (Environmental Chemistry Letters, 2019)

Microbial reduction of bromate: current status and prospects - Xinyue Lv; Dan Wang; Waheed Iqbal; Bo Yang; Yanping Mao (Biodegradation, 2019)

Long-term variation of storm surge-associated waves in the Bohai Sea - Yanping Wang; Yongling Liu; Xinyan Mao; Yutao Chi; Wensheng Jiang (Journal of Oceanology and Limnology, 2019)

The Growth Rate, Immune Status, Duodenal Development, and Cecal Microbial Diversity of 24-Day-Old Offspring of SD Rats Received Bacillus subtilis-Cu or CuSO4 During Pregnancy and Lactation Periods - Guodong Liu; Baowei Wang; Yanping Huang; Kailing Li; Wenhua Ge; Mingai Zhang; Bin Yue; Min Kong (Biological Trace Element Research, 2019)

Impact of the quasi-biweekly oscillation on the super typhoon tracks in winter over the western North Pacific - Yanping Shi; Yan Du; Zesheng Chen; Chunzai Wang (Climate Dynamics, 2019)

Beraprost sodium mitigates renal interstitial fibrosis through repairing renal microvessels - Shulin Li; Yanping Wang; Lu Chen; Zhuojun Wang; Guodong Liu; Bangjie Zuo; Caixia Liu; Dong Sun (Journal of Molecular Medicine, 2019)

The distribution of plants and seed dispersers in response to habitat fragmentation in an artificial island archipelago - Jiajia Liu; Ferry Slik; David A. Coomes; Richard T. Corlett; Yanping Wang; Maxwell Wilson; Guang Hu; Ping Ding; Mingjian Yu (Journal of Biogeography, 2019)
Aim Small, old‐growth forest fragments generally have more small‐seeded plants than large patches, due to the disappearance of large seed dispersing vertebrates. This pattern may differ for secondary forest fragments where differential migration ability rather than persistence of seed dispersers may be driving plant community assembly. In this study, we investigated the effect of habitat fragmentation on seed dispersers and plant community structure in regenerating forests. Location The Thousand Island Lake, China. Taxon Plants, birds and mammals. Methods We compiled diversity and abundance data for birds and mammals on islands in the Thousand Island Lake, China. We also surveyed the secondary plant communities and measured seed dispersal traits. Results Community‐weighted mean seed size of woody plants decreased with island size. This pattern was related to compositional difference of the dispersers. We found that mammal diversity and abundance was only weakly or not related to island size; whereas bird diversity and abundance increased strongly with island size. Density of bird‐dispersed plants was significantly positively related with island size. Since birds tend to disperse smaller seeds than mammals, the trend in seed size may have been a consequence of the shift in relative abundance of the two disperser guilds. Main Conclusions Differential responses of seed dispersers to habitat fragmentation may lead to pervasive shifts in the plant community structure of regenerating forest fragments. Our study highlights the importance of keeping large continuous forests in order to retain mammals and their dispersal capabilities.

Comparative physiological and metabolomic analyses reveal natural variations of tulip in response to storage temperatures - Yanping Wang; Huimin Zhao; Yaping Wang; Siyuan Yu; Yuchao Zheng; Wen’en Wang; Zhulong Chan (Planta, 2019)

Cefquinome-Loaded Microsphere Formulations in Protection against Pneumonia with Klebsiella pneumonia Infection and Inflammatory Response in Rats - Shaoqi Qu; Cunchun Dai; Fenfang Yang; Tingting Huang; Zhihui Hao; Qihe Tang; Haixia Wang; Yanping Zhang (Pharmaceutical Research, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Inhibiting Histamine Signaling Ameliorates Vertigo Induced by Sleep Deprivation - Shuxia Qian; Yanping Wang; Xiaoling Zhang (Journal of Molecular Neuroscience, 2019)

Genetic diversity and pathogenicity dynamics of Magnaporthe oryzae in the Wuling Mountain area of China - Xin Xu; Wu Yang; Ke Tian; Jie Zheng; Xinqiong Liu; Kai Li; Wei Lu; Yanping Tan; Yonghua Qin; Chuntai Wang (European Journal of Plant Pathology, 2019)

Characterization of a novel RNA virus from the phytopathogenic fungus Leptosphaeria biglobosa related to members of the genus Mitovirus - Yong Wang; Zhiyong Xu; Jiasen Cheng; Yanping Fu; Daohong Jiang; Jiatao Xie (Archives of Virology, 2019)

Establishment and evaluation of a model for predicting 3-month mortality in Chinese patients with hepatic encephalopathy - Yanping Cui; Shan Guan; Jie Ding; Yukai He; Qingfang Li; Sikui Wang; Huiling Sun (Metabolic Brain Disease, 2019)

Inheritance and Molecular Marker for Flowering Time in Radish (Raphanus sativus L.) - Qingbiao Wang; Yanping Wang; Li Zhang (Plant Molecular Biology Reporter, 2018)

The effects of air temperature and precipitation on the net primary productivity in China during the early 21st century - Qianfeng Wang; Jingyu Zeng; Song Leng; Bingxiong Fan; Jia Tang; Cong Jiang; Yi Huang; Qing Zhang; Yanping Qu; Wulin Wang; Wei Shui (Frontiers of Earth Science, 2018)

The BET bromodomain inhibitor i-BET151 impairs ovarian cancer metastasis and improves antitumor immunity - Ai Liu; Dianxia Fan; Yanping Wang (Cell and Tissue Research, 2018)

Probiotic Properties and Cellular Antioxidant Activity of Lactobacillus plantarum MA2 Isolated from Tibetan Kefir Grains - Wei Tang; Chao Li; Zengguo He; Fen Pan; Shuo Pan; Yanping Wang (Probiotics and Antimicrobial Proteins, 2018)

The complete chloroplast genome sequence of the wild Chinese chestnut (Castanea mollissima) - Lili Cheng; Wugang Huang; Yanping Lan; Qingchang Cao; Shuchai Su; Zhijun Zhou; Jinbao Wang; Jianling Liu; Guanglong Hu (Conservation Genetics Resources, 2018)

The importance of accounting for imperfect detection when estimating functional and phylogenetic community structure - Xingfeng Si; Marc W. Cadotte; Yuhao Zhao; Haonan Zhou; Di Zeng; Jiaqi Li; Tinghao Jin; Peng Ren; Yanping Wang; Ping Ding; Morgan W. Tingley (Ecology, 2018)
Incorporating imperfect detection when estimating species richness has become commonplace in the past decade. However, the question of how imperfect detection of species affects estimates of functional and phylogenetic community structure remains untested. We used long‐term counts of breeding bird species that were detected at least once on islands in a land‐bridge island system, and employed multi‐species occupancy models to assess the effects of imperfect detection of species on estimates of bird diversity and community structure by incorporating species traits and phylogenies. Our results showed that taxonomic, functional, and phylogenetic diversity were all underestimated significantly as a result of species’ imperfect detection, with taxonomic diversity showing the greatest bias. The functional and phylogenetic structure calculated from observed communities were both more clustered than those from the detection‐corrected communities due to missed distinct species. The discrepancy between observed and estimated diversity differed according to the measure of biodiversity employed. Our study demonstrates the importance of accounting for species’ imperfect detection in biodiversity studies, especially for functional and phylogenetic community ecology, and when attempting to infer community assembly processes. With datasets that allow for detection‐corrected community structure, we can better estimate diversity and infer the underlying mechanisms that structure community assembly, and thus make reliable management decisions for the conservation of biodiversity.

Evolution, functional differentiation, and co-expression of the RLK gene family revealed in Jilin ginseng, Panax ginseng C.A. Meyer - Yanping Lin; Kangyu Wang; Xiangyu Li; Chunyu Sun; Rui Yin; Yanfang Wang; Yi Wang; Meiping Zhang (Molecular Genetics and Genomics, 2018)

Colonization and Gut Flora Modulation of Lactobacillus kefiranofaciens ZW3 in the Intestinal Tract of Mice - Zhuqing Xing; Wei Tang; Ying Yang; Weitao Geng; Rizwan Ur Rehman; Yanping Wang (Probiotics and Antimicrobial Proteins, 2018)

Improved isolation of cadmium from paddy soil by novel technology based on pore water drainage with graphite-contained electro-kinetic geosynthetics - Xianqiang Tang; Qingyun Li; Zhenhua Wang; Yanping Hu; Yuan Hu; Miklas Scholz (Environmental Science and Pollution Research, 2018)

Assessment of Corneal Biomechanical Properties with Inflation Test Using Optical Coherence Tomography - Like Wang; Lei Tian; Yanping Huang; Yifei Huang; Yongping Zheng (Annals of Biomedical Engineering, 2018)

Do seasonal species assemblages differ in their biogeography? Evidence from the spatial structure of bird communities on land‐bridge islands - Chuanwu Chen; Marcel Holyoak; Xingfeng Si; Yanping Wang; Ping Ding (Journal of Biogeography, 2018)
Aim We tested the effects of season and migratory status (residents‐versus‐seasonal migrants) on island biogeography of bird assemblages through partitioning beta diversity into richness and turnover components and community nestedness metrics. We predicted that total beta diversity, the richness component of beta diversity and community nestedness will be lower for bird assemblages in winter than in summer, and lowest of all for winter visitors. These predictions were derived from published ideas about resource availability, movement and habitat choice in birds in different seasons. Location Thousand Island Lake, China. Methods Bird species were sampled using line transects on 36 islands during five breeding and winter seasons (2009−2014). Birds were grouped into assemblages of winter residents, winter visitors and summer residents. Associations between beta diversity partitioning, island area, isolation and habitat richness were tested using partial Mantel correlations. We complemented these tests with measures of nestedness and null model approaches. Results Contrary to expectation, beta diversity, nestedness and difference of beta diversity or its components from null models were higher for winter residents than either summer resident or winter visitor assemblages. As predicted, winter visitors showed little association with habitat richness, and beta diversity was rarely different from null communities. Summer residents had the highest correlations of beta diversity components with habitat richness, but showed the lowest level of total beta diversity, a low richness component and were anti‐nested (less nested than random). Main conclusions Substantial differences were found in the biogeography of winter‐versus‐summer residents, and seasonal visitor (migratory)‐versus‐resident bird assemblages, which match expectations derived from bird biology and population ecology. Summer residents highlighted the role of habitat‐related niche differences, whereas winter residents showed area‐related selective extinction. By contrast, winter visitors appeared to be more randomly distributed.

Differences in root-associated bacterial communities among fine root branching orders of poplar (Populus × euramericana (Dode) Guinier.) - Qitong Wang; Nian Wang; Yanping Wang; Qingkui Wang; Baoli Duan (Plant and Soil, 2017)

Aboveground and belowground litter have equal contributions to soil CO2 emission: an evidence from a 4-year measurement in a subtropical forest - Qingkui Wang; Youzhi Yu; Tongxin He; Yanping Wang (Plant and Soil, 2017)

The occurrence, exposure and risk assessment of perfluoroalkyl acids in food from mainland, China - Xinxuan Wang; Ruobing Zhang; Hong Zhang; Yanping Wang (Food Additives & Contaminants: Part A, 2017)

Root order-dependent seasonal dynamics in the carbon and nitrogen chemistry of poplar fine roots - Hongying Chen; Yufeng Dong; Tan Xu; Yanping Wang; Huatian Wang; Baoli Duan (New Forests, 2017)

Synthesis and biological evaluation of novel anti-hepatitis C virus (HCV) agents: 2-hydroxylphenethyl sulfanyl-oxopyrimidines - Daochun Wu; Yue Feng; Hua Wang; Junfeng Yang; Xian Chen; Yueping Wang; Christopher Cong Lai; Yufang Zhang; Cong Li; Xueshan Xia; Yanping He (Medicinal Chemistry Research, 2017)

The complete chloroplast genome sequence of the endangered Chinese endemic tree Corylus fargesii - Guanglong Hu; Lili Cheng; Yanping Lan; Qingchang Cao; Xueqiang Wang; Wugang Huang (Conservation Genetics Resources, 2017)

Nestedness of butterfly assemblages in the Zhoushan Archipelago, China: area effects, life-history traits and conservation implications - Aichun Xu; Xufang Han; Xuemei Zhang; Virginie Millien; Yanping Wang (Biodiversity and Conservation, 2017)

Bmi1 Regulates the Proliferation of Cochlear Supporting Cells Via the Canonical Wnt Signaling Pathway - Xiaoling Lu; Shan Sun; Jieyu Qi; Wenyan Li; Liman Liu; Yanping Zhang; Yan Chen; Shasha Zhang; Lei Wang; Dengshun Miao; Renjie Chai; Huawei Li (Molecular Neurobiology, 2017)

Social and environmental influences on tartary buckwheat (Fagopyrum tataricum Gaertn.) varietal diversity in Yunnan, China - Mary Saunders Bulan; Jiangchong Wu; Eve Emshwiller; Mark E. Berres; Joshua L. Posner; Duoyi Peng; Xinhui Wang; Junfang Li; David E. Stoltenberg; Yanping Zhang (Genetic Resources and Crop Evolution, 2017)

Expression of lycopene biosynthesis genes fused in line with Shine-Dalgarno sequences improves the stress-tolerance of Lactococcus lactis - Xiangrong Dong; Yanping Wang; Fengyuan Yang; Shanshan Zhao; Bing Tian; Tao Li (Biotechnology Letters, 2017)

Molecular variation and expansion of a rice black-streaked dwarf virus population based on analysis of segment 1 in Jining, China - Yu Zhou; Qingchang Meng; Yanping Chen; Jirong Wu; Zhuanfang Hao; Zhenhua Wang; Degui Zhang; Mingshun Li; Hongjun Yong; Shihuang Zhang; Xinhai Li; Jianfeng Weng (Archives of Virology, 2016)

Salicylic acid-induced antioxidant protection against low temperature in cold-hardy winter wheat - Jing Yu; Jing Cang; Yanping Li; Ru Huang; Qiuwei Lu; Xiutian Wang; Lijie Liu; Qinghua Xu; Kejian Zhang (Acta Physiologiae Plantarum, 2016)

On empty islands and the small‐island effect - Yanping Wang; Virginie Millien; Ping Ding (Global Ecology and Biogeography, 2016)
Aim The small‐island effect (SIE) has become a widely accepted part of the theoretical framework of island biogeography. A major criticism of SIE studies is the exclusion of empty islands from analyses. However, the generality and underlying factors determining the role of empty islands in generating SIEs remain obscure because few published datasets include islands with no species. The aim of this study was thus to evaluate the prevalence and underlying factors determining the role of empty islands in generating SIEs. Location Global. Methods We compiled 278 datasets that included empty islands. For each dataset, we compared the fit of a logarithmic model with two breakpoint models separately for all the islands and for datasets excluding empty islands to determine the role of empty islands in generating SIEs. We then employed multinomial logistic regressions and an information‐theoretic approach to determine which combination of island characteristics was important in determining the role of empty islands in generating SIEs. Results Among 211 datasets with adequate fits, the exclusion of empty islands changed the evidence for an SIE in 68 cases (32.2%). SIEs were quite prevalent, both for all the islands (104 cases, 49.3%) and for datasets excluding empty islands (73 cases, 34.6%). Our results were not consistent with the hypothesis that excluding empty islands would increase the evidence for an SIE. Model selection and relative variable importance indicated that the number of empty islands, the minimum area of empty islands and area ratio were important variables that determined the role of empty islands in generating SIEs. Main conclusions Our study demonstrates that the effect of empty islands in generating SIEs is quite prevalent. The exclusion of empty islands is thus an important methodological shortcoming for the detection of SIEs. We conclude that, for the robust detection of SIEs, empty islands should not be excluded in future studies.

Functional and bioinformatics analysis of an exopolysaccharide-related gene (epsN) from Lactobacillus kefiranofaciens ZW3 - Jingrui Wang; Wei Tang; Yongna Zheng; Zhuqing Xing; Yanping Wang (Archives of Microbiology, 2016)

A single mutation in the PBC loop of VP2 is involved in the in vitro replication of infectious bursal disease virus - Xiaole Qi; Xiang Gao; Zhen Lu; Lizhou Zhang; Yongqiang Wang; Li Gao; Yulong Gao; Kai Li; Honglei Gao; Changjun Liu; Hongyu Cui; Yanping Zhang; et al. (Science China Life Sciences, 2016)

Molecular identification of Kiss/GPR54 and function analysis with mRNA expression profiles exposure to 17α-ethinylestradiol in rare minnow Gobiocypris rarus - Yanping Yang; Jiancao Gao; Cong Yuan; Yingying Zhang; Yongjing Guan; Zaizhao Wang (Molecular Biology Reports, 2016)

Environmental behaviors of phenolic acids dominated their rhizodeposition in boreal poplar plantation forest soils - Yanping Wang; Chuanrong Li; Qingkui Wang; Huatian Wang; Baoli Duan; Guangcan Zhang (Journal of Soils and Sediments, 2016)

Impact of Biological Treatment Techniques on Perfluoroalkyl Acids Emissions in Municipal Sewage - Xinxuan Wang; Ruobing Zhang; Hong Zhang; Long He; Jincan Shen; Zhifang Chai; Bo Yang; Yanping Wang (Water, Air, & Soil Pollution, 2016)

A Comprehensive Analysis of Carotenoid Cleavage Dioxygenases Genes in Solanum Lycopersicum - Yanping Wei; Hongjian Wan; Zhiming Wu; Rongqing Wang; Meiying Ruan; Qingjing Ye; Zhimiao Li; Guozhi Zhou; Zhuping Yao; Yuejian Yang (Plant Molecular Biology Reporter, 2016)

Effects of organic matter content and composition on ammonium adsorption in lake sediments - Li Zhang; Shengrui Wang; Lixin Jiao; Yanping Li; Jiachun Yang; Rui Zhang; Shuang Feng; Juan Wang (Environmental Science and Pollution Research, 2016)

Cyclic utilization of HP-β-CD in the bioconversion of cortisone acetate by Arthrobacter simplex - Yanbing Shen; Fang Wang; Yanping Wang; Qing Zhao; Min Wang (Biotechnology Letters, 2016)

Particle-Associated Ambient Benzo[a]pyrene and Levels of Urinary 1-Hydroxypyrene in a Non-occupationally Exposed Population of Adults and Children in Lanzhou, China - Yunjiang Yu; Qiong Wang; Liangzhong Li; Zien Liu; Peng Sun; Yanping Zhang; Haipeng Lin; Mingdeng Xiang; Hui Li; Bigui Lin (Bulletin of Environmental Contamination and Toxicology, 2016)

Enhancing saccharification of wheat straw by mixing enzymes from genetically-modified Trichoderma reesei and Aspergillus niger - Yanping Jiang; Alexandra Vivas Duarte; Joost van den Brink; Ad Wiebenga; Gen Zou; Chengshu Wang; Ronald P. de Vries; Zhihua Zhou; Isabelle Benoit (Biotechnology Letters, 2016)

QTL mapping for flowering time in different latitude in soybean - Sijia Lu; Ying Li; Jialin Wang; Peerasak Srinives; Haiyang Nan; Dong Cao; Yanping Wang; Jinliang Li; Xiaoming Li; Chao Fang; Xinyi Shi; Xiaohui Yuan; et al. (Euphytica, 2015)

Pharmacodynamics and Pharmacokinetics of Levobupivacaine Used for Epidural Anesthesia in Patients with Liver Dysfunction - Juhong Ran; Yanping Wang; Fangkun Li; Wei Zhang; Minyu Ma (Cell Biochemistry and Biophysics, 2015)

Insights into tetracycline adsorption onto kaolinite and montmorillonite: experiments and modeling - Yanping Zhao; Xueyuan Gu; Shiyin Li; Ruiming Han; Guoxiang Wang (Environmental Science and Pollution Research, 2015)

Genomic organization of a novel victorivirus from the rice blast fungus Magnaporthe oryzae - Lihua Tang; Yanping Hu; Lijiang Liu; Songsong Wu; Jiatao Xie; Jiasen Cheng; Yanping Fu; Guoming Zhang; Juntao Ma; Yongli Wang; Liyan Zhang (Archives of Virology, 2015)

Effect of amino acid sequence variations at position 149 on the fusogenic activity of the subtype B avian metapneumovirus fusion protein - Bingling Yun; Yanni Gao; Yongzhen Liu; Xiaolu Guan; Yongqiang Wang; Xiaole Qi; Honglei Gao; Changjun Liu; Hongyu Cui; Yanping Zhang; Yulong Gao; Xiaomei Wang (Archives of Virology, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Effects of active, passive, and combined smoking on cervical cancer mortality: a nationwide proportional mortality study in Chinese urban women - Jingmei Jiang; Haiyu Pang; Boqi Liu; Philip C. Nasca; Biao Zhang; Yanping Wu; Wei Han; Margaret Gates; Tao Lu; Xiaonong Zou; Fang Xue; Lei Hou; et al. (Cancer Causes & Control, 2015)

Antagonism of miRNA-21 Sensitizes Human Gastric Cancer Cells to Paclitaxel - Bo Jin; Yanping Liu; Haijiang Wang (Cell Biochemistry and Biophysics, 2015)

Erratum to: Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Exploring the Wnt Pathway-Associated LncRNAs and Genes Involved in Pancreatic Carcinogenesis Driven by Tp53 Mutation - Qi Wang; He Jiang; Chen Ping; Ruizhe Shen; Tingting Liu; Juanjuan Li; Yuting Qian; Yanping Tang; Shidan Cheng; Weiyan Yao; Lifu Wang (Pharmaceutical Research, 2015)

The Noninvasive Detection of RARβ2 Promoter Methylation for the Diagnosis of Prostate Cancer - Tong Zhang; Lei Zhang; Qinggong Yuan; Xiangling Wang; Yi Zhang; Jinhua Wang; Yanping Zhang (Cell Biochemistry and Biophysics, 2015)

Erythropoietin (EPO) Protects Against High Glucose-Induced Apoptosis in Retinal Ganglional Cells - Yunxiao Wang; Hui Zhang; Yanping Liu; Ping Li; Zhihong Cao; Yu Cao (Cell Biochemistry and Biophysics, 2015)

Molecular characterization of PXR and two sulfotransferases and hepatic transcripts of PXR, two sulfotransferases and CYP3A responsive to bisphenol A in rare minnow Gobiocypris rarus - Jiancao Gao; Yingying Zhang; Yanping Yang; Cong Yuan; Fang Qin; Shaozhen Liu; Yao Zheng; Zaizhao Wang (Molecular Biology Reports, 2014)

Composition and spectroscopic characteristics of dissolved organic matter extracted from the sediment of Erhai Lake in China - Yanping Li; Shengrui Wang; Li Zhang; Haichao Zhao; Lixin Jiao; Yali Zhao; Xiaosong He (Journal of Soils and Sediments, 2014)

Overexpression of CDK5 in Neural Stem Cells Facilitates Maturation of Embryonic Neurocytes Derived from Rats In Vitro - Hongyu Quan; Xiyan Wu; Yanping Tian; Yun Wang; Chengren Li; Hongli Li (Cell Biochemistry and Biophysics, 2014)

The Role of ABA in the Maturation and Postharvest Life of a Nonclimacteric Sweet Cherry Fruit - Hao Luo; ShengJie Dai; Jie Ren; CaiXia Zhang; Ying Ding; Zhuang Li; Yufei Sun; Kai Ji; Yanping Wang; Qian Li; Pei Chen; Chaorui Duan; et al. (Journal of Plant Growth Regulation, 2014)

Physical-Chemical Properties of Collagens from Skin, Scale, and Bone of Grass Carp ( Ctenopharyngodon idellus ) - Haibo Wang; Yanping Liang; Haiyin Wang; Hanjun Zhang; Min Wang; Liangzhong Liu (Journal of Aquatic Food Product Technology, 2014)

CRP Gene polymorphism contributes genetic susceptibility to dyslipidemia in Han Chinese population - Wenbin Wei; Song Yang; Yingru Qiu; Hairu Wang; Xianghai Zhao; Yanping Zhao; Yun Li; Ming Wu; Yanchun Chen; Wen Wang; Xiaoming Shi; Sijun Liu; et al. (Molecular Biology Reports, 2014)

Association study of common variations of FBN1 gene and essential hypertension in Han Chinese population - Jinfeng Chen; Song Yang; Xianghai Zhao; Jiahui Shen; Hairu Wang; Yanchun Chen; Yanni Ji; Wen Wang; Wei Zhou; Xuecai Wang; Junming Tang; Xiangfeng Lu; et al. (Molecular Biology Reports, 2014)

Transcriptome-wide analysis of dynamic variations in regulation modes of grapevine microRNAs on their target genes during grapevine development - Chen Wang; Xiangpeng Leng; Yanyi Zhang; Emrul Kayesh; Yanping Zhang; Xin Sun; Jinggui Fang (Plant Molecular Biology, 2014)

Estrogen deficiency reduces the dentinogenic capacity of rat lower incisors - Tao Xu; Ming Yan; Yanping Wang; Zhanwei Wang; Lizhe Xie; Chunbo Tang; Guangdong Zhang; Jinhua Yu (Journal of Molecular Histology, 2014)

Dissipation, residues, and risk assessment of spirodiclofen in citrus - Haibin Sun; Congyun Liu; Siwei Wang; Yanping Liu; Mingjin Liu (Environmental Monitoring and Assessment, 2013)

Dopamine transporter availability in heroin-dependent subjects and controls: longitudinal changes during abstinence and the effects of Jitai tablets treatment - Ying Liu; Mei Han; Xingdang Liu; Yanping Deng; Yu Li; Jie Yuan; Rongbin Lv; Yuankai Wang; Guangming Zhang; Jinlong Gao (Psychopharmacology, 2013)

Identification and characterization of two novel transcription units of porcine circovirus 2 - Zhangzhao Gao; Qinfang Dong; Yonghou Jiang; Tanja Opriessnig; Jingxiu Wang; Yanping Quan; Zongqi Yang (Virus Genes, 2013)

Dissipation and residue of azoxystrobin in banana under field condition - Siwei Wang; Haibin Sun; Yanping Liu (Environmental Monitoring and Assessment, 2013)

Dissipation and Residue of Spinosad in Zucchini Under Field Conditions - Yanping Liu; Haibin Sun; Siwei Wang (Bulletin of Environmental Contamination and Toxicology, 2013)

Transcriptional Regulation of Genes Encoding Key Enzymes of Abscisic Acid Metabolism During Melon (Cucumis melo L.) Fruit Development and Ripening - Yufei Sun; Pei Chen; Chaorui Duan; Pang Tao; Yanping Wang; Kai Ji; Yin Hu; Qian Li; Shengjie Dai; Yan Wu; Hao Luo; Liang Sun; et al. (Journal of Plant Growth Regulation, 2013)

Estrogen deficiency inhibits the odonto/osteogenic differentiation of dental pulp stem cells via activation of the NF-κB pathway - Yanping Wang; Ming Yan; Yan Yu; Jintao Wu; Jinhua Yu; Zhipeng Fan (Cell and Tissue Research, 2013)

Therapy with Astragalus polysaccharides rescues lipotoxic cardiomyopathy in MHC-PPARα mice - Wei Chen; Wenjie Chen; Yanping Xia; Xuelan Zhao; Hao Wang; Maohua Yu; Yiming Li; Hongying Ye; Yu Zhang (Molecular Biology Reports, 2013)

Associations Between EEG Beta Power Abnormality and Diagnosis in Cognitive Impairment Post Cerebral Infarcts - Yanping Wang; Xiaoling Zhang; Junjun Huang; Minchu Zhu; Qiaobing Guan; Chunfeng Liu (Journal of Molecular Neuroscience, 2013)

Overlapping transcription structure of human cytomegalovirus UL140 and UL141 genes - Yanping Ma; Mali Li; Bo Zheng; Ning Wang; Shuang Gao; Lin Wang; Ying Qi; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2013)

Impact of mercury on denitrification and denitrifying microbial communities in nitrate enrichments of subsurface sediments - Yanping Wang; Heather A. Wiatrowski; Ria John; Chu-Ching Lin; Lily Y. Young; Lee J. Kerkhof; Nathan Yee; Tamar Barkay (Biodegradation, 2013)

Transcription characteristics of the human cytomegalovirus UL13 gene - Ning Wang; Yanping Ma; Mali Li; Shuang Gao; Lin Wang; Ying Qi; Yaohua Ji; Zhengrong Sun; Qiang Ruan (Archives of Virology, 2013)

Kefir and Health: A Contemporary Perspective - Zaheer Ahmed; Yanping Wang; Asif Ahmad; Salman Tariq Khan; Mehrun Nisa; Hajra Ahmad; Asma Afreen (Critical Reviews in Food Science and Nutrition, 2013)

RETRACTED ARTICLE: Isolation and analysis of homoeologous genes encoding gibberellin 2-oxidase 3 isozymes in common wheat - QIUFANG CHEN; HUIYUAN YA; SHIMING LI; YANPING YANG; GUANGYONG QIN; XUELI AN; DAOWEN WANG; KUNPU ZHANG; ZHEN JIAO (Journal of Genetics, 2012)

Molecular cloning, expression profile, polymorphism and the genetic effects of the dopamine D1 receptor gene on duck reproductive traits - Cui Wang; Shijun Li; Chuang Li; Yanping Feng; Xiuli Peng; Yanzhang Gong (Molecular Biology Reports, 2012)

Reference gene selection for qPCR in Ammopiptanthus mongolicus under abiotic stresses and expression analysis of seven ROS-scavenging enzyme genes - Jing Shi; Meiqin Liu; Junna Shi; Guangshun Zheng; Yanping Wang; Jinyu Wang; Yuzhen Chen; Cunfu Lu; Weilun Yin (Plant Cell Reports, 2012)

Dissipation and Residue of Myclobutanil in Lychee - Yanping Liu; Haibin Sun; Fengmao Liu; Siwei Wang (Bulletin of Environmental Contamination and Toxicology, 2012)

Growth inhibition and apoptotic effect of alpha-eleostearic acid on human breast cancer cells - Tingting Zhang; Yanping Gao; Yu Mao; Quanbo Zhang; Caiyu Lin; Ping Lin; Jie Zhang; Xiujie Wang (Journal of Natural Medicines, 2012)

Human cytomegalovirus RL13 gene transcripts in a clinical strain - Mali Li; Yanping Ma; Yaohua Ji; Rong He; Ying Qi; Zhengrong Sun; Ning Wang; Shuang Gao; Qiang Ruan (Virus Genes, 2011)

Genomic Differences Between Actinobacillus pleuropneumoniae Serotypes 5b and 3 and their Distribution and Transcription Among 15 Serotypes - Feng Yang; Fang Xie; Yuwen Jiang; Suqing Li; Yanping Xing; Yu Wang; Xin Feng; Wenyu Han; Liancheng Lei (Current Microbiology, 2011)

Inactivation of the extracytoplasmic function sigma factor Sig6 stimulates avermectin production in Streptomyces avermitilis - Libin Jiang; Yanping Liu; Pan Wang; Ying Wen; Yuan Song; Zhi Chen; Jilun Li (Biotechnology Letters, 2011)

Tetracycline adsorption on kaolinite: pH, metal cations and humic acid effects - Yanping Zhao; Jinju Geng; Xiaorong Wang; Xueyuan Gu; Shixiang Gao (Ecotoxicology, 2011)

Stratification of Archaeal communities in shallow sediments of the Pearl River Estuary, Southern China - Lijing Jiang; Yanping Zheng; Jinquan Chen; Xiang Xiao; Fengping Wang (Antonie van Leeuwenhoek, 2011)

RNA interference-mediated silencing of iASPP induces cell proliferation inhibition and G0/G1 cell cycle arrest in U251 human glioblastoma cells - Guilin Li; Renzhi Wang; Jun Gao; Kan Deng; Junji Wei; Yanping Wei (Molecular and Cellular Biochemistry, 2011)

Genetic variation in the GCKR gene is associated with non-alcoholic fatty liver disease in Chinese people - Zhen Yang; Jie Wen; Xiaoming Tao; Bin Lu; Yanping Du; Mei Wang; Xuanchun Wang; Weiwei Zhang; Wei Gong; Charlotte Ling; Songhua Wu; Renming Hu (Molecular Biology Reports, 2011)

Genetical and molecular analysis reveals a cooperating relationship between cytoplasmic male sterility- and fertility restoration-related genes in Oryza species - YanPing Tan; ShaoQing Li; HongWei Xie; ShiHua Duan; Ting Wang; YingGuo Zhu (Theoretical and Applied Genetics, 2011)

Genome-wide analysis of primary auxin-responsive Aux/IAA gene family in maize (Zea mays. L.) - Yijun Wang; Dexiang Deng; Yunlong Bian; Yanping Lv; Qin Xie (Molecular Biology Reports, 2010)

Transcription pattern of UL131A-128 mRNA in clinical strains of human cytomegalovirus - Zhengrong Sun; Gaowei Ren; Yanping Ma; Ning Wang; Yaohua Ji; Ying Qi; Mali Li; Rong He; Qiang Ruan (Journal of Biosciences, 2010)

Contribution of bovine lactoferrin inter-lobe region to iron binding stability and antimicrobial activity against Staphylococcus aureus - Xuejing Bai; Da Teng; Zigang Tian; Yanping Zhu; Yalin Yang; Jianhua Wang (BioMetals, 2010)

Caveolin-1 restoration by cholesterol enhances the inhibitory effect of simvastatin on arginine vasopressin-induced cardiac fibroblasts proliferation - Shaowei Liu; Yanping He; Yufeng Dou; Haichang Wang; Ling Tao; Lianyou Zhao; Fujun Shang; Hui Liu (Molecular and Cellular Biochemistry, 2009)

Mutation in the RGD motif decreases the esterase activity of Xcc_est - Jianjun Wang; Yanping Cao; Guojun Zheng (Biotechnology Letters, 2009)

Diagnostic value of HCMV pp65 antigen detection by FCA for symptomatic and asymptomatic infection: compared to quantification of HCMV DNA and detection of IgM antibody in infants - Zhengrong Sun; Xiangshi Ceng; Zhiqin Mao; Jidong Wang; Qing Liu; Yaohua Ji; Yanping Ma; Ying Qi; Rong He; Qiang Ruan (Medical Microbiology and Immunology, 2009)

Gametophytically alloplasmic CMS line of rice (Oryza sativa L.) with variant orfH79 haplotype corresponds to specific fertility restorer - Shaoqing Li; Yanping Tan; Kun Wang; Cuixiang Wan; Yingguo Zhu (Theoretical and Applied Genetics, 2008)

Preparation and some properties of cholesterol oxidase from Rhodococcus sp. R14-2 - Chengtao Wang; Yanping Cao; Baoguo Sun; Baoping Ji; M. J. Robert Nout; Ji Wang; Yonghuan Zhao (World Journal of Microbiology and Biotechnology, 2008)

Alteration of integrin-associated protein (CD47) on experimental porcine eperythrozoonosis - Wei Li; Ning Du; Binrui Xu; Weixing Dong; Zhe Qu; Yong Wang; Yanping Sui (Veterinary Research Communications, 2008)

Overexpression of SBPase enhances photosynthesis against high temperature stress in transgenic rice plants - Lingling Feng; Kun Wang; Yang Li; Yanping Tan; Jin Kong; Hui Li; Yangsheng Li; Yingguo Zhu (Plant Cell Reports, 2007)

The isolation and initial characterization of mercury resistant chemolithotrophic thermophilic bacteria from mercury rich geothermal springs - Aspassia D. Chatziefthimiou; Melitza Crespo-Medina; Yanping Wang; Costantino Vetriani; Tamar Barkay (Extremophiles, 2007)

Impacts of climatic factors on runoff coefficients in source regions of the Huanghe River - Liqun Chen; Changming Liu; Yanping Li; Guoqiang Wang (Chinese Geographical Science, 2007)

Genomic comparison of Yersinia pestis and Yersinia pseudotuberculosis by combination of suppression subtractive hybridization and DNA microarray - Xiaoyi Wang; Dongsheng Zhou; Long Qin; Erhei Dai; Jianguo Zhang; Yanping Han; Zhaobiao Guo; Yajun Song; Zongmin Du; Jin Wang; Jun Wang; Ruifu Yang (Archives of Microbiology, 2006)

The Influence of Mycobacterium tuberculosis Sigma Factors on the Promotion Efficiency of ptpAt Promoter in Mycobacterium smegmatis - Jianqiang Lei; Hongmei Zhang; Chunlan Wu; Xiaolei Wang; Yanping Yang; Xuelian Zhang; Yishu Huang; Honghai Wang (Current Microbiology, 2005)

A glycosynapse in myelin? - Joan M. Boggs; Huimin Wang; Wen Gao; Dina N. Arvanitis; Yanping Gong; Weixian Min (Glycoconjugate Journal, 2004)

Effective induction of immune tolerance by portal venous infusion with IL-10 gene-modified immature dendritic cells leading to prolongation of allograft survival - Ming Zhang; Quanxing Wang; Yushan Liu; Yanping Sun; Guoshan Ding; Zhiren Fu; Zhilian Min; Youhua Zhu; Xuetao Cao (Journal of Molecular Medicine, 2004)